Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Molecular mechanisms and regulatory networks of salt stress tolerance in plants - Muhammad Usman; Li Wang; An Xiaojuan; Zixing Sun; Fei Yu; Philippe Gallusci; Ruie Liu; Caixi Zhang (Plant Science, 2026)

Tectonothermal imprints of Ediacaran Pan-African Orogeny in the Bakoshi-Gadanya area, Nigeria: Constraints from apatite chemical and U-Pb-Nd isotopes - Safiyanu Muhammad Elatikpo; Huan Li; Thomas J. Algeo; Rabiu Abubakar; Nuerkanati Madayipu; Usman Mohammed (Journal of Geochemical Exploration, 2026)

Development and validation of a simple and Robust LC-MS/MS method for the determination of Tutin in honey and its application to market samples from the United Arab Emirates - Shaima M. Askar; Abdelaziz Elgamouz; Amaresha Shetty; Asma M. Askar; Muhammad Usman; Mohammed A. Meetani (Food and Humanity, 2026)

High prevalence of ESBL encoding genes in enterobacterales isolated from hospital and environmental wastewater in Pakistan- One Health challenge - Muhammad Usman Qamar; Muhammad Rizwan; Fatima Tuz Zahra; Faiqa Arshad; Asma Ejaz; Aatika; Sana Rehman; Zikria Saleem (Molecular Biology Reports, 2026)

Multi-modal therapeutic approaches to inflammatory bowel disease: plant-derived compounds, nanoparticle drug delivery systems, and gene-based interventions - Arooj Komal; Doua Ilyas; Muhammad Usman Khan; Muhammad Khalil ur Rehman; Tayyaba Hassan; Hina Ayub; Nokhba Naqi; Noor Ullah; Umair Ilyas (Molecular Biology Reports, 2026)

High frequency and prognostic significance of TP53 promoter methylation in Pakistani glioblastoma patients - Ahad Naveed; Noor Muhammad; Afshan Khanum; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2026)

Green manure and chemical fertilizer optimization to mitigate greenhouse gas emission: A solution towards sustainable and climate-resilient agriculture - Tahir Shah; Muhammad Sufhan Tahir; Yunli Tang; Azeem Ahmad; Usman Zulfiqar; Muhammad Fraz Ali; Hao Yang; Weidong Cao; Dabin Zhang; Yajun Gao (Soil Ecology Letters, 2026)

Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Urea-loaded biochar at optimal pyrolysis temperature reshapes soil microbial communities to improve nitrogen use efficiency and mitigate environmental pollution in water spinach (Ipomoea aquatica Forsk.) - Muhammad Usman Ghani; Mengjun Li; Jian Shen; Yingting Gong; Ronghui Wang; Yinghui Xu; Muhammad Kamran; Shree Prakash Pandey; Shaoying Ai (Soil and Tillage Research, 2026)

Beyond toxicity: Systems-level virulence of entomopathogenic fungi in termite social immunity - Hafiz Muhammad Usman; Hammad Hassan; Arshad Ali; Mohammad Mazharul Karim; Ali Hassan; Min Lu (Journal of Invertebrate Pathology, 2026)

Next-generation hybrid membranes integrating MXene and MOF architectures for energy-efficient water treatment - Saleem Raza; Luqman Ali; Muhammad Usman Hameed; Sidra Khalid; Sundas Shoukat; Mamuna Ahmad; Liguo Shen; Ghafar Ali; Imran Shakir (Desalination, 2026)

Per- and polyfluoroalkyl substances: Environmental occurrence, health impacts, and advanced removal technologies - Mustapha Saheed; Mohsen Salma; Usman Abdullahi Rakiya; Abubakar Ladio Hassana; Lukman Asiya Muhammad; Jimoh Oladejo Tijani; Ambali Saka Abdulkareem; Muhammad Muhammad Ndamitso; Kehinde Shola Obayomi; Guillermo Díaz-Sainz; Jianhua Zhang (Colloids and Surfaces C: Environmental Aspects, 2026)

Artificial intelligence and financial systems as enablers of the circular economy in European countries: Unlocking the strategic role of natural resources and renewable energy - Yimamu Abasi; Yongming Huang; Muhammad Usman; Rakhshanda Kousar (Sustainable Production and Consumption, 2026)

Evolution of Maastrichtian paleoproductivity along the southern Tethys margin (Jordan): From upwelling to runoff - Maria Ardila-Sanchez; Jihede Haj Messaoud; Amir Kalifi; Khalil Ibrahim; Muhammad Usman; Israa S. Abu-Mahfouz; Samer Aljurf; Volker Vahrenkamp; John H. Powell; Frans van Buchem (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Advancing plastic waste-to-hydrogen: A cross-technology framework integrating eco-technoeconomic analysis, catalyst stability benchmarking and knowledge mapping - Usman Bello; Haruna Adamu; Muhammad Faizan; Abdul Aziz Jallow; Maryem Ourimi; Roa’a Alzoubi; Shafirah Samsuri; Abdul Gani Abdul Jameel; Mohammad Nahid Siddiqui (Journal of Environmental Chemical Engineering, 2026)

Microbial diversity enhancement in a bio-electro-fenton system driven by sediment microbial fuel cells for photocatalytic PAHs degradation in antibiotics applicate soil-water systems - Muhammad Usman; Zenhua Zhao; Muhammad Adnan; Muhammad Ibrahim; Olive Mekontchou Yemele; Ghulam Abbas Ashraf; Mukhtorjon Karimov; Alisher Abduvokhidov; Naoufel Ben Hamadi (Journal of Environmental Chemical Engineering, 2026)

Boosting low-temperature CO2 methanation through Ni/ZrO2 catalyst-NaA zeolite interplay - Inam Ullah; Syed Musab Ahmed; Hao Lou; Zeeshan Abbasi; Zubair Ahmad; Muhammad Usman; Wenlong Wu; Zhandong Wang (Journal of Environmental Chemical Engineering, 2026)

How geopolitical risks, green finance, and environmental technologies dynamics shape energy trilemma in BRICS economies? - Muhammad Usman; Yongming Huang; Muhammad Sohail Amjad Makhdum; Daniel Balsalobre-Lorente (Energy Policy, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

Smartphone-integrated Ti2C quantum dots-alginate hydrogel patch for colorimetric monitoring of sweat total antioxidant capacity - Danyang Xiao; Dejia Hu; Yifeng Shi; Bufeng Liang; Muhammad Usman; Yaqi Sang; Shiqi Mao; Yan Li (Chemical Engineering Journal, 2026)

Exogenous hesperidin orchestrates antioxidant defense, osmolyte metabolism, and nutrient homeostasis to mitigate heavy metal toxicity in canola - Sherjeel Hashmat; Humaira Yasmeen; Bakhrom Jobborov; Muhammad Imran; Mohammed S. Alotaibi; Hossam S. El-Beltagi; Usman Zulfiqar; Amna Batool; Umer Farooq (BioMetals, 2026)

Ascorbic and citric acids mitigate cadmium stress and reduce metal accumulation in spinach grown in alkaline calcareous soil - Saira Hameed; Muhammad Nadeem; Muhammad Ashar Ayub; Muhammad Shabaan; Usman Zulfiqar; Hossam S. El-Beltagi; Dilrabo Kodirova; Dilafruz Solieva; Abdumurod Sattarov; Mashael Daghash Alqahtani; Abdulrahman Alasmari (BioMetals, 2026)

Phytochemical profiles and therapeutic potentials of Thalictrum species in Africa and Asia: a structured review with evidence quality assessment and strategic framework for drug discovery - Sagir Mustapha; Lukman Mustapha; Suciati Suciati; Kayatri Govindaraju; Irma Wati Ngadimon; Muhammad Luqman Nordin; Mustapha Mohammed; Hamza Lawal; Hasiya Usman Jibrilla; Nabil Abdulkarim; Ahmad Khusairi Azemi (Plant Biosystems, 2026)

Effectiveness of machine learning and deep learning techniques for multi-horizon weather forecasting - Abdullah Sami; Muhammad Bilal; Usman Habib; Adeel Ashraf Cheema (Meteorology and Atmospheric Physics, 2026)

Turning trash into treasure: bioactive peptides from food waste–a decade of progress in extraction, purification, and applications: a systematic review - Muhammad Bilal; Muhammad Usman; Maratab Ali; Samee-Ullah; Faryal Shaukat; Muhammad Arslan; Zhihua Li; Xiaobo Zou; Yemin Guo; Xia Sun (Critical Reviews in Food Science and Nutrition, 2026)

Microbial fermentation of cereals: nutritional, techno-functional, and compositional transformations toward data-driven process optimization - Yufeng Lin; Emad Karrar; Shahidul Islam; Zhao Jin; Usman Muhammad; Minwei Xu (Critical Reviews in Food Science and Nutrition, 2026)

The speed–precision paradox in seeding technology: a system-level review of regime transitions, validation gaps, and energy trade-offs - Saddam Hussain; Zhaoyu Rui; Junyan He; Zhao Zhang; Mustafa Mhamed; Muhammad Faheem; Seyed Mohamad Javidan; Muhammad Usman Farid; Alaa Saeed; Mahmoud A. Abdelhamid (Computers and Electronics in Agriculture, 2026)

Exploring the epidemiology of Newcastle disease in Northern Nigeria: A mixed approach - Mayowa Peter Olabode; Usman Adamu Rayyanu; Victoria Isioma Ifende; Ismaila Shittu; Rebecca Paul Weka; Isabella Monne; Matthew Yakop Gukut; Ladi Amos Chabiri; Yakubu Joel Atuman; Judith Dizot Bakam; Falmata Haruna Bwala; Zenaba Mahamat Kodo; et al. (Preventive Veterinary Medicine, 2026)

Molecular mechanisms and integrated breeding strategies for durable resistance to rice blast and other major pathogens - Daud Ali Shah; Muhammad Usama Younas; Zameer Hussain Jamali; Usman Zulfiqar; Mohammed S. Alotaibi; Mayank Anand Gururani; Owais Iqbal (Physiological and Molecular Plant Pathology, 2026)

A systematic review evaluating outcomes of ICU night downgrades in critically ill surgical patients: Towards improving patient safety - Philip Lee; Francis Cruz; Caitlin Tweedie; Quratulain Amin; Muhammad Usman Awan; Logan Rogers; Minna Haddadi; Chadwick P Smith; Adel Elkbuli (Next Research, 2026)

Effect of predatory pressure on behavior of termite Reticulitermes chinensis - Hammad Hassan; Ali Hassan; Taqi Raza; Hafiz Muhammad Usman; Arshad Ali; Jinli Ding; Qiuying Huang; Min Lu (Journal of Insect Physiology, 2026)

3D-printed architecture enhances Rhizopus fermentation of soybean meal - Qianqian Zhu; Muhammad Usman; Wenxue Chen; Haiming Chen; Minwei Xu (Food Bioscience, 2026)

Retraction notice to “Effect of soil texture and zinc oxide nanoparticles on growth and accumulation of cadmium by wheat; a life cycle study” [Environ. Res. 216 (2023)114397] - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Tahir Abbas; Muhammad Ashar Ayub; Asif Naeem; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Muhammad Javid Qamar; Shafaqat Ali (Environmental Research, 2026)

Cyclic Use of Wastewater and Canal Water Improves Maize Growth while Reducing Heavy Metal Accumulation in Soil - Shaikh Amjad Salam; Muhammad Qasim; Hossam S. El-Beltagi; Usman Zulfiqar; Mohammed S. Alotaibi; Nozimakhon Khodjimurodova; Kabulzhan Azizov; Nazih Y. Rebouh (Water, Air, & Soil Pollution, 2026)

Influence of Temperature and Hydrogen Peroxide Treatment on the Physiochemical and Adsorptive Characteristics of Rice Stalk Biochar for Cadmium Remediation: A Sustainable Solution - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Awais Ahmad; Waed Alahmad; Mohammed S. Alotaibi; Saqer S. Alotaibi; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Comparative Analysis of Multidrug Resistance and Virulence in Interconnected Clinical and Environmental Salmonella Strains from Karachi, Pakistan - Yamina Usmani; Rabia Ilyas; Sidrah Asghar; Moatter Zehra; Zulfiqar Ali Mirani; Rao Muhammad Abid Khan; Shabana Usman Simjee; Ayaz Ahmed (Current Microbiology, 2026)

Synergistic role of biochar, AMF, and PGPR in enhancing drought tolerance and productivity of wheat (Triticum aestivum L.) - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Islem Abid; Awais Ahmad; Vusala Ismayilova; Manal Abdulaziz Binobead; Rashid Iqbal (Cereal Research Communications, 2026)

Meta-analytic evaluation of pyrethroid impacts on mammalian reproductive outcomes across 62 studies - Afzal Nimra; Mahnoor Usman; Javaireya Khan; Hanan Afzal; Amina Gull; Safdar Sidra; Ali Afzal; Muhammad Babar Khawar (Toxicology and Environmental Health Sciences, 2026)

Enhancing resource productivity and system sustainability on the Qinghai-Tibetan Plateau: a type-temporal-spatial coupling approach for forage-livestock balance - Jing Zhang; Nurlan Serekpayev; Muhammad Usman; Naeem Ahmad; Muhammad Bilal Hafeez; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Plant and Soil, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Polymeric membrane technologies for wastewater treatment and valorization: Advancing sustainable and circular water systems - Mustapha Saheed; Usman Benedict Shama; Abdullahi Karimatu Lami; Elijah Yanda Shaba; Kehinde Shola Obayomi; Awe Omoniyi Babajide; Jimoh Oladejo Tijani; Ambali Saka Abdulkareem; Muhammad Muhammad Ndamitso (Journal of Environmental Sciences, 2026)

A multi-dimensional accounting framework to resolve the grassland-livestock paradox on the Qinghai-Tibetan Plateau - Jing Zhang; Naeem Ahmad; Muhammad Bilal Hafeez; Muhammad Usman; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Global and Planetary Change, 2026)

Chelation driven interface engineering of Cu-Zn/ZrO2 catalysts for low barrier CO2 hydrogenation to methanol - Khalid Alyami; Nagaraju Pasupulety; Majed A. Alamoudi; Seetharamulu Podila; Muhammad Usman (Fuel, 2026)

Ti-MOF anchored polyaniline network on separator: A dual-function strategy for polysulfide immobilization and redox enhancement in Li-S batteries - Abdul Majid Khan; Yasir Shah; Fakhar Zaman; Rashida Yahya; Safdar Abbas; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2026)

Abscisic acid promotes sweet cherry fruit cracking dependent on cell wall disassembly - Ruie Liu; Li Wang; Zixing Sun; Zhuo Yan; Xiaojuan An; Wanxia Sun; Honglin Nong; Muhammad Usman; Zuoyan Qin; Songtao Jiu; Long Chen; Yaqin Wu; et al. (Food Research International, 2026)

Community benefit agreement preferences for energy development offshore California, Oregon, and Washington: Insights from a choice-based conjoint experiment - Hossain Ahmed Taufiq; Gregory Joseph Stelmach; Umama Rahman; Muhammad Usman Amin Siddiqi; Hilary Boudet (Energy Policy, 2026)

Alleviation of salinity induced toxicity in quinoa (Chenopodium quinoa Willd.) through ascorbic acid application - Muhammad Faisal Maqsood; Tahira Fatima; Rehana Kanwal; Fozia Farhat; Muhammad Shahbaz; Muhammad Jamil; Saba Shafqat; Muhammad Asif; Muhammad Hamza Maqsood; Maryam Tariq; Usman Zulfiqar; Muhammad Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Evaluation of Heavy Metal Tolerant Plant Growth Promoting Pseudomonas Strains for Improving the Growth of Eggplant (Solanum Melongena L.) under Lead (Pb) Stress - Uzma Ambreen; Muhammad Shabaan; Muhammad Junaid Sarwar; Mehreen Malik; Saira Sulaman; Hafiz Naeem Asghar; Usman Zulfiqar; Hossam S. El-Beltagi; Gamal Awad El-Shaboury; Arzu Bakhshaliyeva; Abdulrahman Alasmari (Water, Air, & Soil Pollution, 2026)

Spatiotemporal variability of particulate organic carbon in relation to chlorophyll-a and sea surface temperature in the Arabian Gulf - Md Masudur Rahman; Roman Shults; Rajendran Sankaran; Wanchang Zhang; Mahfuzur Rahman; Muhammad Usman (Ocean Dynamics, 2026)

Therapeutic evaluation of myricetin in experimental arthritis: modulation of inflammatory signaling and oxidative stress pathways - Iqra Ijaz; Tasleem Akhtar; Usman aftab; Nadia Naseem; Muhammad Shahzad; Haleema Sohail; Sumetha Yaseen (Inflammopharmacology, 2026)

Exploring ethyl methane sulphonate induced, L-cysteine HCl resistant Bacillus subtilis putative mutant and its immobilization for enhanced acetoin synthesis - Muhammad Usman Ahmad; Sikander Ali; Noor Ul Ain; Nabeera Shahzadi; Maryam Mustaid; Mahwish Arshad; Sadaf Ahmad; Bakar Bin Khatab Abbasi; Ali Irfan; Yousef A. Bin Jardan (Archives of Microbiology, 2026)

Harnessing machine learning to decode the energy–economy–environment trilemma: insights from renewable and non-renewable energy use in Pakistan - Muhammad Qayyum; Minhaj Ali; Muhammad Waleed Hassan; Usman Mehmood (Environment, Development and Sustainability, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Retraction Note: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

Left behind: forgone medical care due to transportation barriers among adults with physical impairments and disabilities that prevent physical activity in small and rural communities - Jiahe Bian; Wei Li; Xiao Li; Sun Quan; Andong Chen; Sinan Zhong; Muhammad Usman; Samuel Dominic Castiglione Towne; Muyang Li; Bahar Dadashova; Xinyue Ye; Marcia G. Ory (Travel Behaviour and Society, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Oxygen-regulated cascade fermentation to improve the quality of wet Spirulina by off-flavor mitigation, bioactivity enhancement, and coordinated control of biogenic amines - Kerui Su; Bingyu Shi; Anqi Zhao; Beixiao Zhang; Zhihao Fan; Muhammad Usman; Qi Wang; Xuejing Duan; Hanyu Dong; Ayesha Shahid; Jingliang Xu (International Journal of Food Microbiology, 2026)

Phosphoric Acid Outperforms Diammonium Phosphate (DAP) in Cadmium Toxicity Alleviation by Decreasing Bioavailability and Optimizing Maize Physiology in Contaminated Alkaline Soil - Nadeem Sarwar; Mujahid; Muhammad Akhtar; Imtiaz Ahmed; Wajid Mahboob; Muhammad Imran Tipu; Muhammad Rashid Shaheen; Mashael Daghash Alqahtani; Usman Zulfiqar (Water, Air, & Soil Pollution, 2026)

The Evolution of Organoids: From Discovery to Cutting-Edge Applications - Javeria Umber; Uzair Ahmed; Tazeem Fatima; Muhammad Qasim; Usman Ali Ashfaq; Muhammad Shareef Masoud (Stem Cell Reviews and Reports, 2026)

RNA-Seq analysis reveals potential salt- and drought stress tolerance-associated genes in advanced long-day onion breeding lines - Muhammad Daniyal Junaid; Usman Khalid Chaudhry; Fatih Hanci; Zahide Neslihan Öztürk; Ali Fuat Gökçe (Protoplasma, 2026)

The dynamic interaction between the semi-circular canyon and a nearby building with a rigid foundation surrounded by flexible bearing layers under incident SH waves - Nasir Abbas; Jebran Saleem; Zeeshan Haider; Darakshan Zahra; Muhammad Lawal Usman (Innovative Infrastructure Solutions, 2026)

Synergistic effects of spent mushroom substrate and biochar on enhanced humification and heavy metal passivation during rapeseed straw composting - Jinfeng He; Jingyi Fu; Shanshuai Chen; Xiaoyong Liao; Huaqin Xu; Muhammad Usman Khan; Weiwei Huang (Applied Soil Ecology, 2026)

Poly 3-hydroxybutyrate production from corncobs fortified with sugarcane molasses: optimization and recovery strategies - Sikander Ali; Muhammad Arshad; Sibtain Ahmed; Saima Shahzad Mirza; Khayala Mammadova; Muhammad Usman Ahmad; Yousaira Masud (World Journal of Microbiology and Biotechnology, 2026)

Machine and deep learning for sentinel-based land use and land cover change detection: a systematic review and future outlook - Anam Nigar; Yang Li; Muhammad Yousuf Jat Baloch; Sedra Shafi; Abdullahi Garba Usman (Environmental Monitoring and Assessment, 2026)

Dual-template structure-based design of novel harmine derivatives as EGFR inhibitors for colorectal cancer therapy - Sagir Yusuf Ismail; Murtala Muhammad; Tasiu Abdulmumin Mikail; Zakari Nuhu Lambu; Bishir Usman (In Silico Pharmacology, 2026)

Transboundary smog dynamics: A spatiotemporal assessment of brick kiln emission impacts in Central Punjab, Amritsar, and Ferozepur - Ayesha Naz; Muhammad Farooq Iqbal; Muhammad Imran Shahzad; Muhammad Usman; Bilal Hassan (Urban Climate, 2026)

Effect of split applications of silicon nanoparticles and conventional sources of Si on growth, antioxidant enzymes, and cadmium uptake in wheat under Cd stress - Muhammad Aamer Maqsood; Nimra Ashraf; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Refaat A. Abohassan (South African Journal of Botany, 2026)

Neural network-driven exploration of wave phenomena in ocean and fluid environments - Usman Younas; Fengping Yao; Jan Muhammad (Ocean Engineering, 2026)

Investigating the higher-dimensional dynamical perspective of the Boiti–Leon–Manna–Pempinelli equation for modeling complex wave interactions in fluid systems - Jianglong Shen; Jan Muhammad; Usman Younas (Ocean Engineering, 2026)

Advances in functional carbon composites for electrochemical energy conversion and catalysis: Design strategies, mechanisms and future prospects - Luqman Ali; Muhammad Usman Hameed; Xingfen Huang; Saleem Raza; Abdul Majid Khan; Mashkoor Ahmad; Akif Safeen; Imran Shakir (Journal of Environmental Chemical Engineering, 2026)

Biomass-derived biochar as a precursor for graphene-like carbon materials via slow pyrolysis: A review - Illa Rizianiza; Eny Kusrini; Ahmad Indra Siswantara; Muhammad Aziz; Ponky Ivo; Imam Jauhari Maknun; Rendika Rumaldin Ichsan; Kuntum Khoiro Ummatin; Anwar Usman (Journal of Environmental Chemical Engineering, 2026)

Unveiling the role of environmental policy stringency and informatization in shaping the e-waste landscape in Europe - Ahmed Usman; Syed Muhammad Mudassir Abbas Naqvi; Ilhan Ozturk; Ali Hassan (Journal of Environmental Chemical Engineering, 2026)

Comparative cradle-to-application life cycle assessment of hydrogen pathways: Role of ethanol purity and end-use efficiency in SOFCs and hydrogen engines - Muhammad Usman; Yasuko Yanagida; Tetsuya Yamada (Journal of Cleaner Production, 2026)

Gas adsorption behavior in organic-rich carbonate source rocks: Insights into hydrogen storage, methane recovery, and CO2 sequestration in oil shales - Muhammad Usman; Muhammad Ali; Tawanda Matamba; Alireza Keshavarz; Stefan Iglauer; Hussein Hoteit; Volker Vahrenkamp (Fuel, 2026)

Circular valorization of agricultural, industrial, and post-consumer waste into fiber-reinforced composites for environmental sustainability - Muhammad Usman Shahid; Muhammad Noman Shahid; Zulfiqar Ahmad; Hafiz Muhammad Abdullah; Muhammad Muzammil Azad (Environmental Research, 2026)

Retraction notice to “Assessment of hepatotoxicity and nephrotoxicity in Cirrhinus mrigala induced by trypan blue - an azo dye” [Environ. Res. 215 (2022) 114120] - Bilal Hussain; Muhammad Sajad; Hassan Usman; Khalid A. Al-Ghanim; Mian Nadeem Riaz; Aydin Berenjian; Shahid Mahboob; Pau Loke Show (Environmental Research, 2026)

Investigating thermal performance of PCM-integrated solar windows with multi-discharging modes in a humid subtropical climate - Muzaffar Ali; Ubaid ur Rehman; Nadeem Ahmed Shiekh; Hafiz Muhammad Adeel Hassan; Muhammad Usman; Andrea Ferrantelli; Müslüm Arıcı (Energy and Buildings, 2026)

Synergistic interfacial engineering in MXene/NiCoSe2/NCS heterostructure for rapid charge transfer in supercapacitors - Wenhao Chen; Lin Sun; Bin He; Muhammad Usman; Yulong Ying; Longhua Li; Yu Liu (Chemical Engineering Journal, 2026)

Two-stage A/O process decontaminates urea and total nitrogen in textile printing wastewater: Focus on combined Na2SO4 and Na2S2O4 salinity - Faheem Ahmed Ghori; Xumeng Lin; Ying Wu; Yimei Cheng; Ling Xiong; Hong Chen; Muhammad Usman Ghani; Gang Xue (Bioresource Technology, 2026)

Sustainable valorization of date waste to renewable fuels and chemicals: Data-driven biorefinery analysis and techno-economic insight - Usman Bello; Haruna Adamu; Muhammad Faizan; Maryem Ourimi; Roa'a Alzoubi; Abdulaziz Jallow; Mohammad Nahid Siddiqui; Abdul Gani Abdul Jameel (Bioresource Technology Reports, 2026)

Preparation, characterization and flocculation performance of fungi-nanoparticle conjugates for efficient harvest of Chlorella vulgaris - Muhammad Hizbullahi Usman; Abdulrahman Sahabi; Muhammad Bello; Aliyu Ibrahim Dabai (Bioresource Technology Reports, 2026)

Widespread declining trends of snow water resources and their driving factors in water towers of Indus River - Giovanna Grossi; Rubina Ansari; Muhammad Usman Liaqat (Regional Environmental Change, 2026)
The importance of seasonal snowpack in sustaining water resources for both ecological systems and anthropogenic activities is undeniable. Yet these vital systems are highly fragile and particularly susceptible to the impacts of human activities and climate change. The present study assesses the space–time variation in maximum snow water equivalent (SWEmax) and maximum daily snowmelt (SMmax) in terms of magnitude and timing and their response to variations in elevation, seasonal precipitation, and temperature which serve as an insightful indicator of hydrological change in snow water resources. The proposed framework combines long term daily snow water equivalent (SWE) and snowmelt data with multiple snow metrics, trend analysis, and attribution to seasonal temperature and precipitation, and is applied across the headwaters of the Indus River (Upper Indus Basin) for the period 1979–2019. Results show that the widespread loss in snow water resources has occurred across most parts of the UIB in recent decades especially at mid elevation and their trends are not linearly related to elevation and are highly heterogeneous between sub-basins. However, contrasting results are observed for cold dessert areas of UIB. Snow dominated basins, e.g., Jhelum, Chenab, and Swat, are the hotspots for the change in snow water resources, with significantly reduced and earlier snowpack and snowmelt peaks. These changes are primarily driven by temperature and precipitation, with their relative importance varying based on elevation and sub-basin characteristics. Specifically, the influence of precipitation and temperature on SWEmax is more strongly dependent on elevation, while winter melt (FMmax) is more influenced by sub-basin location. In contrast, SMmax exhibits variations in relative importance across both elevation and sub-basin scales. Negative changes in snow water resources in these mid-elevation zones have strong implications for downstream water availability.

Arbuscular Mycorrhizal Fungi and Leonardite alter fatty acid and amino acid biosynthesis in sunflower grains - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Sajad Ali; Zeeshan Ahmed; Khairiah Mubarak Alwutayd; Rashid Iqbal (Plant Molecular Biology, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nonlinear wave dynamics of soliton neuron model: a high-fidelity computational investigation - Usman Younas; Jan Muhammad (Modeling Earth Systems and Environment, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Effects of strigolactone-modified biochars on wheat (Triticum aestivum L.) germination and soil nutrient dynamics in alkaline soil - Ghulam Murtaza; Muhammad Usman; Wael Elmenofy; Hanan M. Alharbi; Khairiah Mubarak Alwutayd; Mohammad K. Alharbi; Rashid Iqbal (Cereal Research Communications, 2026)

Enhancement of maize drought resilience using nano-buckminsterfullerenes and plant growth-promoting rhizobacteria: insights into pigment stability, oxidative stress reduction, and yield - Ghulam Murtaza; Muhammad Usman; Najmaldin Ezaldin Hassan; Zeeshan Ahmed; Awais Ahmad; Khairiah Mubarak Alwutayd; Wael Elmenofy; Hassan Mehmood; Rashid Iqbal (Cereal Research Communications, 2026)

Adaptive role of silicon in enhancing crop resilience and yield under stressful environments: A new window for stress management - Ghulam Murtaza; Muhammad Rizwan; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Rashid Iqbal; Akash Tariq; Gang Deng (Plant Biosystems, 2026)

Artificial intelligence unleashes the wisdom of ancient ranches: Returning grasslands to the grasslands - Jing Zhang; Muhammad Usman; Fujiang Hou; Zhibiao Nan (Agricultural Systems, 2026)

In situ biotransformation of synthetic glutamate to γ-amino butyric acid by an auxotrophic Lactococcus lactis in polysorbate-mediated thermoaerobic process - Siaknder Ali; Kinza Arif; Qaiser Farid Khan; Muhammad Usman Ahmad; Ifrah Shabbir; Iram Liaqat; Tawaf Ali Shah; Gehan M. Elossaily; Yousef A. Bin Jardan (Biodegradation, 2026)

Synergistic application of biochar and mercury-resistant Bacillus cereus enhances phytoremediation efficiency and stress tolerance in sorghum (Sorghum bicolor L.) grown in mercury-contaminated soil - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal (Biodegradation, 2026)

Insecticidal and antibacterial potential of Croton tiglium functionalized zinc oxide nanoparticles - Arshad Ali; Ali Hassan; Imran Afzal; Hammad Hassan; Kirshan Chand; Hafiz Muhammad Usman; Xiaolong Liu; Min Lu (International Journal of Tropical Insect Science, 2026)

Bioconversion of L-phenylalanine to L-dopaquinone by Aspergillus oryzae: a scalable model for neurological precursor synthesis - Nasir Ali; Sikander Ali; Sibtain Ahmed; Muhammad Usman Ahmad; Muhammad Arshad; Abdusamat Rasulov; Otabek Kuziev (World Journal of Microbiology and Biotechnology, 2026)

A new species of Lobothallia (Megasporaceae) from the cold semi-arid regions of Gilgit-Baltistan, Pakistan - Uswa Fatima Ahmad; Muhammad Usman; Najam ul Sehar Afshan; Abdul Nasir Khalid (Biologia, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Investigating the wave dynamics and interaction structures: Exploring the Benney-Roskes/Zakharov-Rubenchik model in the oceanic atmosphere - Jianglong Shen; Jan Muhammad; Usman Younas (Ocean Engineering, 2026)

Unlocking sustainable fuel pathways in thermo-catalytic hydrogenation of CO2 to ethanol: progress, challenges, and future Prospects - Sameera Shafi; Nazia Siddiqui; Aniz Chennampilly Ummer; Muhammad Usman; Tahir Rasheed (Fuel, 2026)

Amine-appended bimetallic MOF-74 for highly selective and energy-efficient CO₂ capture under vacuum swing adsorption - Rodynah A. Alabdulhadi; Shabnam Khan; Md Delowar Hossain; Aamir Hanif; Mohammed Ahmed Sanhoob; Mohd Yusuf Khan; Mosim Ansari; Aasif Khan; Muhammad Usman; Saleh AlMansour; Aasif Helal (Chemical Engineering Journal, 2026)

Impact of drying temperature-induced protein conformational changes on the regulation of intermolecular interactions and gelation in pea starch-Spirulina composite gel - Kerui Su; Bingyu Shi; Anqi Zhao; Beixiao Zhang; Zhihao Fan; Muhammad Usman; Qi Wang; Xuejing Duan; Hanyu Dong; Ayesha Shahid; Jingliang Xu (Carbohydrate Polymers, 2026)

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Nature’s arsenal unleashed: Senegalia modesta derived thymol halts cancer progression by suppressing proangiogenic genes - Komal Khalid; Mehr Un Nissa Bashir; Muhammad Usman Rashid; Naila Malkani (Natural Product Research, 2026)

Synergistic effects of volatile interactions on the pyrolysis gas and aromatic hydrocarbons formation during multi-component medical waste pyrolysis - Chao Liao; Aijun Li; Yongda Huang; Muhammad Usman; Yuhang Zheng; Qian Deng; Yicheng Lei; Hong Yao (Process Safety and Environmental Protection, 2026)

Mapping risk areas for the occurrence of Peste des petits ruminants in the Plateau, Bauchi, and Kano states in Nigeria by combining expert knowledge and field surveys on animal mobility - Sandra I. Ijoma; Asma Mesdour; Rayyanu A. Usman; Muhammad-Bashir Bolajoko; Chika Nwosuh; Marion Bordier; Arnaud Bataille; Adeiza M. Abdulrahman; Wesley D. Nafarnda; Andrea Apolloni; Elena Arsevska (Preventive Veterinary Medicine, 2026)

Copper complexation and chromium reduction by dissolved organic matter derived from microplastics - Muhammad Usman; Ling Ding; Chengyi Liu; Xinran Qiu; Bin Zhang; Xujun Liang; Xuetao Guo (Journal of Water Process Engineering, 2026)

Electrodialysis for sustainable water desalination: Principles, applications, challenges, and future directions - Subhan Mahmood; Numan Mahmood; Muhammad Usman Liaquat; Faizan Ikhlaq; Hamza Shehzad; Shun Yao (Journal of Environmental Chemical Engineering, 2026)

Increased cutting frequency coupled with mineral nitrogen fertilization enhances forage productivity and reduces greenhouse gas intensity in an arid legume-grass cultivated grassland - Muhammad Usman Ghani; Shanning Lou; Jiao Ning; Muhammad Kamran; Awais Shakoor; Wanhe Zhu; Fujiang Hou (Field Crops Research, 2026)

Role of Nano-Silicon, Nano-Biochar, and Irrigation Strategies in Managing Tellurium Toxicity: Implications for Soil Microbiota, Wheat Yield, and Food Safety - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Zeeshan Ahmed; Rehman Habib; Javed Iqbal; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Decoding core molecular mechanisms of heat-stress tolerance in Brassica napus using transcriptomics and machine learning - Muhammad Ikram; Muhammad Farhan; Behnam Derakhshani; Sunjeet Kumar; Aliya Ayaz; Naveed Khan; Enerand Mackon; Babar Usman; Si Chengcheng; Pingwu Liu (Plant Cell Reports, 2026)

Integrative Omics and Biotechnological Strategies to Enhance Crop Salinity Tolerance - Muhammad Usman; Li Wang; Wanxia Sun; Xiaojuan An; Zixing Sun; Fei Yu; Ruie Liu; Caixi Zhang (Journal of Plant Growth Regulation, 2026)

Application of Melatonin and Bacillus halotolerans Mitigated the Cadmium and Lead Induced Toxicity in Brassica carinata by Improving the Growth and Defense System of the Plant - Namra Batool; Asia Nosheen; Humaira Yasmin; Rabia Naz; Paul A. Correa; Syed Muhammad Usman Shah Kazmi (Journal of Plant Growth Regulation, 2026)

Retraction Note: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2026)

Synergistic effects of foliar selenium nanoparticles and aged cellulose-derived biochar on PAH immobilization and spinach health in contaminated soils - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Zeeshan Ahmed; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Environmental Geochemistry and Health, 2026)

Effects of Exposure to Differentially Stressed Pinus sylvestris Seedlings on the Susceptibility of Receivers to Feeding by the Large Pine Weevil - Sara Mashhadi Meyghani; Muhammad Usman Rasheed; James D. Blande (Journal of Chemical Ecology, 2026)
Plants release volatile organic compounds (VOCs) in response to herbivory or damage as part of an indirect defence strategy. These broadly defined damage-induced plant volatiles (DIPVs), include herbivore-induced plant volatiles (HIPVs). DIPVs elicit defence-related responses in neighbouring plants, which may influence herbivore behaviour. Although DIPVs have been studied in conifers, little is known about how they influence neighbouring plants and shape subsequent interactions with herbivores. We tested whether DIPVs released by damaged Scots pine ( Pinus sylvestris ) seedlings alter the susceptibility of undamaged receivers to feeding by the large pine weevil ( Hylobius abietis ). A two-stage experiment examined the effects of exposure to VOCs from mechanically damaged, pine weevil-damaged, sawfly-damaged, and undamaged seedlings on neighbouring receivers. In the first stage, receivers were exposed to VOCs for seven days. VOC emissions from receivers were collected and analysed using gas chromatography–mass spectrometry. Analyses revealed treatment-specific volatile profiles. In the second stage, weevil orientation was tested, and receiver susceptibility evaluated by quantifying bark damage area using digital photograph analysis and classification of feeding-damage type as superficial or deep. Weevils first oriented towards the control receivers most frequently before being found in greater numbers on receivers exposed to DIPVs from mechanically damaged and weevil-damaged neighbours. Towards the end of the experiment, they were found on receivers exposed to sawfly-induced DIPVs. The control group had more deep damage than superficial damage, whereas all DIPV exposure groups had more superficial than deep feeding spots, suggesting that prior VOC exposure may result in surface-level feeding. These findings show that DIPVs can trigger changes in receivers that influence pine weevil orientation and feeding behaviour.

Role of Acacia bark biochar in the growth of Ocimum basilicum L. under cadmium stress - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal; Hossam S. El-Beltagi; Mashael Daghash Alqahtani; Usman Zulfiqar (Biodegradation, 2026)

Combined application of 5-ALA and nitric oxide improves lead detoxification and antioxidant defense in barley - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Wael Elmenofy; Muhammad Aamir Manzoor; Rashid Iqbal (Biodegradation, 2026)

Microbial production and biocatalytic docking of pectin lyase for green oil extraction in biorefinery applications - Sikander Ali; Saba Mahboob; Ishtiaq Ahmad; Muhammad Usman Ahmad; Hafiza Kanwal; Sundas Sharif; Khayala Mammadova; Muhammad Arshad (Archives of Microbiology, 2026)

Bacterial biological control agents and resistance resources to enhance defense and morphological attributes of Capsicum annuum against Fusarium wilt - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Muhammad Sagheer; Ye Xia (Journal of Plant Pathology, 2026)
Fusarium wilt (c.o. Fusarium oxysporum f. sp. capsici ( Foc ) is one of the major disasters during chilli production, which causes tremendous yield losses under suitable climatic conditions worldwide. One of our research aims was to investigate the incidence of Fusarium wilt disease, with a special reference to the climatic conditions in various chilli growing areas of Punjab, Pakistan, in 2020–2022. For these purposes, three major chilli growing areas were surveyed. All the investigated climatic factors, such as air and soil temperature, relative humidity, rainfall, wind speed, and soil moisture, positively correlated with disease development. The highest disease incidence was recorded in District Lahore (69%), followed by a disease incidence of 31.8% in Chiniot and 16% in Kasur. In our study, two years’ screening (2020-21 and 2021-22) of thirty different chilli varieties/advanced lines was carried out to find out the source of resistance against Fusarium wilt. Among them, only two varieties (Sayban and HP-1810 F1) showed resistance responses, but six varieties (Maxi, PR-0921, BS Hari Rani, FS-1, Janbaz-F1, and Sitara 80) were highly susceptible to Fusarium wilt of chilli. For the disease management with biocontrol agents (BCAs), Bacillus subtilis (MU_Bs09) was found the most effective in inhibiting pathogen mycelial growth (82.68%) and reducing disease incidence (75.88%) under both lab and greenhouse experiments, followed by Streptomyces palmae (MU_Sp19) and Pseudomonas simiae (MU_Ps13). Also, treatment with Bacillus subtilis (MU_Bs09) significantly enhanced the production of some biochemical enzymes and compounds, including catalases, phenolics, H₂O₂, and chlorophyll. In addition, Bacillus subtilis (MU_Bs09) improved the plant morphological attributes, such as fresh weight, dry weight, plant height, and yield per plant when treated at three different concentrations. The related enhancements were followed by Streptomyces palmae (MU_Sp19) and Pseudomonas simiae (MU_Ps13). In conclusion, cultivating resistant plant varieties is one of the most effective strategies to combat Fusarium wilt. In addition, applying soil drenching with beneficial microbes, such as Bacillus subtilis strain MU_Bs09, can be one effective strategy for managing Fusarium wilt through enhancing plant antioxidant activity and other constitutive defense mechanisms.

Advances in fulvic acid extraction from lignite: techniques, challenges, and applications - Iqra Yousaf; Lizhen Gao; Iffat Riaz; Sidra Pervaiz; Muhammad Usman (Environmental Monitoring and Assessment, 2026)

Retraction Note: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2026)

Molecular prevalence, genetic diversity and effect of Toxoplasma gondii infection on the hematological parameters of various bird species - Tauqir Un Nisa; Fatima Mushtaq; Humaira Zulfiqar Ali Gondal; Naila Amjad; Muhammad Usman; Muhammad Ali; Muhammad Latif; Hira Muqaddas; Furhan Iqbal (Biologia, 2026)

Arbuscular mycorrhizal symbiosis Drives rhizosphere-regulated drought tolerance in maize - Ghulam Murtaza; Muhammad Usman; Khairiah Mubarak Alwutayd; Rashid Iqbal (Rhizosphere, 2026)

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Exploring the mechanisms of charged polysaccharides in regulating the microstructure, texture, and rheology of camellia oleosomes-based meat analogs - Shahzad Farooq; Abdullah; Muhammad Ijaz Ahmad; Usman Ali; Sumeng Wei; Jiawen Xue; Tin Nyawe Nyawe Hlaing; Quancai Sun; Ye Peng; Hui Zhang (Food Hydrocolloids, 2026)

Synergistic multifaceted effects of tea saponin concentration on the foaming properties of wheat aqueous phase protein: A next-generation approach to food foam production - Usman Ali; Shahzad Farooq; Muhammad Ijaz Ahmad; Quancai Sun; Ye Peng; Meiyu Chen; Hui Zhang (Food Hydrocolloids, 2026)

Transient mixed convection in coaxial pipes with temperature-dependent variable density - Bakhtawar Bibi; Ali B.M. Ali; Muhammad Ashraf; Ghulam Rasool; Muhammad Usman Rashid; Abduvali Sottarov (Dynamics of Atmospheres and Oceans, 2026)

RETRACTED: Deepcluster: A selective and stable strategy to predict the AuPt-based high entropy alloy nanoclusters via deep reinforcement learning - Muhammad Usman; Muhammad Umar Farooq; Fuyi Chen (Chemical Engineering Journal, 2026)

Improving anaerobic digestion of sewage sludge to renewable natural gas by the Advanced Pretreatment & Anaerobic Digestion technology (APAD): Pilot testing - Birgitte K. Ahring; Fuad Ale Enriquez; Muhammad Usman Khan; Peter Valdez; Francesca Pierobon; Timothy E. Seiple; Richard Garrison (Chemical Engineering Journal, 2026)

Modelling adoption of camera-based safety monitoring systems in construction: an extended technology acceptance model approach using PLS-SEM - Nawal Manzoor; Hilal Khan; Muhammad Usman Hassan; Khursheed Ahmed; Muhammad Umer Zubair (Innovative Infrastructure Solutions, 2026)

Synthesis of biocompatible novel multi-tailed indole-based resorcinarene for effective delivery of quercetin against multidrug-resistant S. aureus - Khadija Rehman; Tasmina Kanwal; Muhammad Hasnain; Rukesh Maharjan; Wajeeha Muzafar; Komal Rao; Salim Saifullah; Shabana Usman Simjee; Muhammad Raza Shah (Archives of Microbiology, 2026)

Correction: Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

A toolkit for the assessment of training needs and gaps of the national Veterinary Services in field epidemiology - Imadidden Musallam; Julio Pinto; Ravi Bandara Dissanayake; Muhammad Usman Zaheer; Zaidoun Hijazeen; Wafa’a Ramadneh; Iqbal Qatananni; Esam Hawa; Majed Hawaowsheh; Ehab Abu-Basha; Aida binti Muhid; Jamaliah binti Senawi; et al. (The Veterinary Journal, 2026)

Multifunctional bio-composite hydrogels: PolyAMPs-tuned hydroxyapatite-PVA/gelatin systems development and characterization - Anum Ayub Awan; Waheed Miran; Muhammad Bilal Khan Niazi; Zakir Hussain; Aqeel Afzal; Usman Liaqat (Sustainable Chemistry and Pharmacy, 2026)

Corrigendum to ‘Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads’ [International Journal of Refrigeration 181 (2026) 111–125] - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Fe-and Mg-functionalized chicken manure biochar immobilized Cd, Cr, and Pb in aged soil and decreased their leaching into groundwater - Yasir Hamid; Qiang Lin; Muhammad Saqib Rashid; Muhammad Usman; Yonglong Chen; Esmat F. Ali; Hamada Abdelrahman; Temoor Ahmed; Sabry M. Shaheen; Sang Soo Lee; Xiaoe Yang (Groundwater for Sustainable Development, 2026)

Valorisation of medical waste through the staged pyrolysis: effect of pyrolysis conditions on chlorine removal and product formation - Yuhang Zheng; Tong Zhang; Aijun Li; Yongda Huang; Muhammad Usman; Qian Deng; Chao Liao; Yi Huang; Hong Yao (Fuel, 2026)

Phytochemical diversity and functional food relevance of Citrus limon and Citrus limetta - Muhammad Usman Zahid; Khazeena Atta; Azmat Zahra; Faiza Rasheed; Waqas Khan Kayani (Food Bioscience, 2026)

Dissecting Microplastics Stress: Impacts of Type, Size, and Dose on Nutrient Cycling, Growth, and Antioxidant Defense System in Maize Plant - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Aamer Maqsood; Saddam Hussain (Water, Air, & Soil Pollution, 2026)

Remediation of Water Contaminated by Toxic Metals with Multi-metal/Co-doped Modified Biochars - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Muhammad Qasim; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Lala Gurbanova; Mehdi Rahimi (Water, Air, & Soil Pollution, 2026)

Synergistic Role of Plant Growth-Promoting Rhizobacteria and Zinc Ferrite Nanoparticles in Mitigating Mercury Stress in Chickpea (Cicer arietinum L.) - Waqar Younas; Hina Khan; Humera Amin; Sami Ullah; Abd Ullah; Usman Ali; Muhammad Nafees; Fazal Amin; Iftikhar Ahmed; Tanveer Hussain; Mohamed Taha Yassin; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

A study on genus Termitomyces with description of two new species and a new record from Pakistan - Amatu Rehman; Muhammad Usman; Ayesha Nawaz; Iqra Rauf; Khetab Ullah; Malka Saba; Najam ul Sehar Afshan; Abdul Nasir Khalid (Plant Systematics and Evolution, 2026)

Neural network assisted symbolic analysis and simulation of nonlinear dynamical equation - Jan Muhammad; Fengping Yao; Usman Younas (Modeling Earth Systems and Environment, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Integrating organic and inorganic amendments to enhance wheat growth, physiology and antioxidant activity while reducing cadmium accumulation - Ahmad Ali; Zaffar Malik; Muhammad Abdul Basit; Abubakar Dar; Usman Zulfiqar; Dilnoza Sotiboldiyeva; Muydinjon Muminov; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Zinc-regulated growth, chlorophyll, and antioxidant activity drive biofortification in rice varieties - Hafiza Ammara; Asma Zulfiqar; Ammara Saleem; Rehana Sardar; Usman Zulfiqar; Muhammad Aown Sammar Raza; Muhammad Faisal Maqsood; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Germination-driven modifications in pulse carbohydrates for optimized 3D food printing inks and structures - Muhammad Usman; Yu Lu; Zhao Jin; Jiajia Rao; Minwei Xu (Food Chemistry, 2026)

Performance comparison and sustainability assessment of mesoporous FAU zeolites for the plastic upcycling - Muhammad Usman Azam; Nanbyen George Kim; Auguste Fernandes; M. Filipa Ribeiro; Waheed Afzal; Inês Graça (Chemical Engineering Journal, 2026)

Nanobubble-enabled wetting control in membrane distillation via interfacial modulation - Mingyi Jia; Jianhao Qian; Muhammad Usman Farid; Jehad A. Kharraz; Shadi W. Hasan; Samir Kumar Khanal; Alicia Kyoungjin An (Chemical Engineering Journal, 2026)

Disease-resistant grape hybrid development through embryo rescue techniques - Qandeela Nigar; Mahmood ul Hassan; Rashid Mehmood Rana; Irfan Ali; Muhammad Usman Raja; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Ficus deltoidea Preserves Hippocampal Neuronal Integrity and Redox Balance in Oxidative Stress-Driven Alzheimer’s Disease-Like Rat Model - Alhaji Modu Bukar; Che Mohd Nasril Che Mohd Nassir; Michael Ayuba; Sushmita Devi Manoharan; Abdulhamid Sani Usman; Babagana Isa Umar; Zaw Myo Hein; Mohamad Aris Mohd Moklas; Muhammad Zulfadli Mehat; Hafizah Abdul Hamid (Molecular Neurobiology, 2026)

Neuroprotective Effects of Ficus deltoidea in Alzheimer’s Disease-Like Rat Model: Insights from Behavior, Histology, and Amyloid Pathology - Abdulhamid Sani Usman; Sushmitaa Dhevii Manoharan; Che Mohd Nasril Che Mohd Nassir; Hafizah Abdul Hamid; Zaw Myo Hein; Anwar Norazit; Jayakumar Murthy; Murizal Zainol; Mohd Amir Kamaruzzaman; Samaila Musa Chiroma; Muzaimi Mustapha; Mohamad Aris Mohd Moklas; et al. (Molecular Neurobiology, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Sustainable self-compacting concrete incorporating industrial waste SCMs: a state-of-the-art review on rheology, durability, microstructural and mechanical performance - Muhammad Khuzaima Qureshi; Hilal Khan; Mati Ullah Shah; Zamil Bin Zahid; Saif Ur Rehman; Raja Dilawar Riaz; Muhammad Usman; Junaid Ahmad; In-Ho Kim (Innovative Infrastructure Solutions, 2026)

Pathogenic CDKN2A germline variants are rare in a cohort of unselected pancreatic cancer patients from Pakistan - Shumaila Arif; Noor Muhammad; Humaira Naeemi; Muhammad Usman Rashid (Familial Cancer, 2025)

Corrigendum to “Microplastic assessment in remote and high mountain lakes of Gilgit Baltistan, Pakistan” [Chemosphere 365 (2024) 143283] - Maryem Mehboob; Rachid Dris; Bruno Tassin; Johnny Gasperi; Muhammad Usman Khan; Riffat N. Malik (Chemosphere, 2025)

Performance comparison of complete mix reactor and static mixer in ballasted flocculation - Muhammad Qasim; Muhammad Naveed Afridi; Salman Ali Suhail; Usman Pervaiz Khan; Imtiaz Afzal Khan; Jong-Oh Kim (Chemosphere, 2025)

Laboratory and greenhouse endophytic colonization of tomato by three entomopathogenic fungal isolates for the management of Tetranychus urticae and field efficacy trials - Waqas Wakil; Maria C. Boukouvala; Nickolas G. Kavallieratos; Aqsa Naeem; Syed Adnan Haider; Muhammad Usman Ghazanfar; Pasco B. Avery (Crop Protection, 2025)

Halotolerant PGPRs attenuate salinity stress in maize through differential expression of stress-related genes and regulated Na+/K+ homeostasis - Tahira Yasmeen; Muhammad Saleem Arif; Aqeel Ahmad; Muhammad Usman; Mohsin Tariq; Waqas Haider; Afira Syrish (South African Journal of Botany, 2025)

Climate-responsive cropland dynamics in Indus Basin: A comprehensive SDM assessment with intra-seasonal variability - Fatima Ilyas; Muhammad Azmat; Swera Javed; Shakil Ahmad; Muhammad Arshad; Muhammad Usman Rashid; Saeed Ahmad Asad (Science of The Total Environment, 2025)

Genotoxic and oxidative stress assessment of heavy metal contaminated soil and water in human blood and bovine milk samples from the different industrial zones of Punjab, Pakistan - Muhammad Muddassir Ali; Furqan Awan; Muhammad Usman Jamil; Muhammad Ijaz; Asad Ullah; Wasim Shehzad (Journal of Trace Elements in Medicine and Biology, 2025)

Starvation-induced metabolic adaptations in immobilized Desertifilum tharense BERC-3 for improved nutrient recovery from swine wastewater - Muhammad Usman; Md. Asraful Alam; Kerui Su; Anqi Zhao; Muhammad Aamer Mehmood; Zhang Beixiao; Ayesha Shahid; A.E. Solovchenko; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

Green innovations and its dual impact on economic growth and environmental sustainability: Evidence from Vietnam - Ha Van Trung; Fan Fei; Patita Paban Mohanty; Muhammad Usman (Journal of Environmental Management, 2025)

Cyclotriphosphazene-derived oxygen-rich N, P-codoped carbon nanosheets for high-performance supercapacitor electrodes - Abdul Majid Khan; Muhammad Waqar Hameed; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2025)

Structuring camellia seed-derived oleosomes for the fabrication of meat analogs using transglutaminase: Structural, functional, and rheological properties - Shahzad Farooq; Muhammad Ijaz Ahmad; Shijie Zheng; Usman Ali; Yipeng Zhang; Jiawen Xue; Yang Li; Cui Shixiu; Hui Zhang (Food Hydrocolloids, 2025)

Cellulose-based bioplastic replacement of single use plastic bags in the collection and treatment of food waste via anaerobic digestion for a zero-waste circular economy - Jonathan T.E. Lee; Muhammad Usman Khan; Jingxin Zhang; Kendra H.Y. Ho; S.J. Chew; Alvin W.L. Ee; Jie Bu; Yong Wei Tiong; Xiangzhou Yuan; Yong Sik Ok; Birgitte K. Ahring; Yen Wah Tong (Chemical Engineering Journal, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Optimizing tree crown density of finite coastal vegetation patches for enhanced tsunami mitigation - Fakhar Muhammad Abbas; Ali Abdullah Zaid Aldrees; Sohail Iqbal; Amina; Muhammad Atiq Ur Rehman Tariq; Naveed Anjum; Mujahid Iqbal; Usman Ghani; Ghufran Ahmed Pasha (Natural Hazards, 2025)

Mapping the non-coding RNA landscape in ataxia telangiectasia: a scoping review of ATM dependent miRNA and lncRNA dysregulation - Muhammad Junaid Iqbal; Usman Ameen; Hamza Tanveer; Laraib Israr; Anastasia Ricci; Gianluca Morganti; Muhammad Jawad Khan; Michele Menotta (Molecular Biology Reports, 2025)
Ataxia-Telangiectasia (A-T) is caused by biallelic Ataxia-Telangiectasia Mutated (ATM) protein mutations and is hallmarked by neurodegeneration, immunodeficiency and cancer susceptibility. Emerging work suggests that non-coding RNAs are integral to the ATM driven DNA damage response, yet the scope of non-coding RNA perturbation in A-T has not systematically mapped. This study is done to chart and synthesize all primary evidence on ncRNA dysregulation in A-T and to identify mechanistic gaps and research priorities. The evidence base comprises a total of five studies focused exclusively on microRNAs and long non-coding RNAs. Baseline sequencing of 20 patients revealed consistent downregulation of miR-195-5p, miR-30a-5p and miR-342-3p. Low dose γ-irradiation of ATM-null lymphoblastoid cell lines produced an exaggerated bidirectional shift (8 microRNAs upregulated, 6 downregulated) versus wild-type, whereas primary T-cells showed largely ATM independent rises of miR-34a-5p and miR-182-5p. A lymphoblastoid cell lines study distinguished 22 recessive or dominant radiation-responsive microRNAs. Long non-coding RNAs profiling identified 149 transcripts that require functional ATM for induction and three uniquely upregulated in A-T cells. No circular RNA study in A-T is observed till date. The ncRNA research in A-T is nascent with five studies present a miRNA dysregulation and an ATM-dependent lncRNA surge that is lost in A-T, but leave circRNAs, neuronal tissues and functional validation unexplored. Intermediate dose stress models, total and small RNA-seq under DNA damage and oxidative stress, and CRISPR rescue/knockout screens in patient derived organoids are immediate priorities for exploring the role of ncRNAs as therapeutic targets in A-T.

Association of PD-1 immune checkpoint polymorphisms with oral cancer risk: results from a Pakistani case-control study - Iqra Mubeen; Arifa Shabbir; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Muhammad Usman Rashid; Naila Malkani (Molecular Biology Reports, 2025)

Beyond traditional diagnosis: aptamer-based microRNA detection for the early diagnosis of periodontitis - Muhammad Usman Ashraf; Khairul Mohd Fadzli Mustaffa; Nurul Wahida Mohd Hasan; Maaz Anwer Memon; Danial Qasim Butt; Rizwan Mahmood; Wan Nazatul Shima Shahidan (Molecular Biology Reports, 2025)

Cystic fibrosis in Pakistan: population harbouring rare variants non-responsive to CFTR modulators and the dilemma of poor health facilities - Anum Safdar; Muhammad Usman Ghani; Iqbal Bano; Tahir Mehmood; Hassan Rafique; Muhammad Farooq Sabar; Ali Akbar; Rehan Sadiq Shaikh (Molecular Biology Reports, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Acid-Modified Biochar Mitigates Salt Stress in Maize by Enhancing Nutrient Availability and Antioxidant Defense System Under Variable Salt-Affected Soils - Hiba Shaghaleh; Tahira Akram; Muhammad Zia-ur-Rehman; Muhammad Usman; Yousef Alhaj Hamoud; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Basmah M. Alharbi; Awatif M. Abdulmajeed (Journal of Soil Science and Plant Nutrition, 2025)

Improving Nitrogen Efficiency and Photosynthesis in Wheat Using integrated Nitrogen Management and Modified Geometry - Uzair Ahmed; Muhammad Waseem Abbas; Jalal Bayar; Irshad Ali Khan; Aneela Tahmeed; Muhammad Mehran Anjum; Nawab Ali; Gul Roz Khan; Hazrat Usman; Mahmoud F. Seleiman (Journal of Soil Science and Plant Nutrition, 2025)

Unraveling the impact of Anabaena azotica and Nostoc flagelliforme on wheat performance under saline-alkali soil and combined abiotic stresses - Obaid Ur Rehman; Xinjuan Hu; Shijiang Cao; Feifei Zhu; Muhammad Abdur Rehman Shah; Muhammad Uzair; Bin Zou; Cunsheng Zhang; Mei Zhao; Usman Majeed; Shuhao Huo (Algal Research, 2025)

Physio-biochemical alterations and phytoremediation potential of hemp cultivated in ciprofloxacin (CIP)-contaminated soil: groundbreaking and enduring solution - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Javed Iqbal; Hassan Mehmood; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Gamal Awad El-Shaboury; Rashid Iqbal (Biodegradation, 2025)

Advances in bacterial chromium biosorption: current perspectives and future directions - Abdullahi Adamu Faggo; Bashar Haruna Gulumbe; Nazeef Idris Usman; Tirmizhi Munkaila Abubakar; Kadai Alhaji Lawan; Musbahu Abdullahi Bagwai; Kabir Hassan Sambo; Muhammad Bello; Mubarak Hassan Ismail; Wada Nafiu (Environmental Science and Pollution Research, 2025)

Phytochemical composition and antitumor activity of a new arctic lichen Anamylopsora pakistanica - Vojislav Đukić; Muhammad Usman; Abdul Nasir Khalid; Anja Manojlović; Milan Zarić; Petar Čanović; Radica Živković-Zarić; Nedeljko Manojlović (Natural Product Research, 2025)

Machine learning-driven dynamic prediction and optimization for ammonia recovery in membrane distillation system - Ying Bi; Minjian Li; Muhammad Usman Farid; Alicia Kyoungjin An (Water Research, 2025)

The fate of soil microbial communities under seasonal and continuous yak grazing in alpine meadows of Qinghai-Tibetan Plateau - Muhammad Usman; Lan Li; Muhammad Kamran; Mengyuan Wang; Fujiang Hou (Soil and Tillage Research, 2025)

When farmers’ knowledge matters: Improving epidemiological understanding of Peste des petits ruminants in northern Nigeria - Zenaba MAHAMAT KODO; Usman Adamu RAYYANU; Mayowa Peter OLABODE; Victoria Isioma IFENDE; Rebecca Paul WEKA; Matthew Yakop GUKUT; Alexis DELABOUGLISE; Ismaila SHITTU; Yakubu Joel ATUMAN; Judith Dizot BAKAM; Falmata Haruna BWALA; Ladi Amos CHABIRI; et al. (Preventive Veterinary Medicine, 2025)

Corrigendum to “Exploring mechanisms of resistance to fludioxonil in Colletotrichum fructicola” [Pesticide Biochemistry and Physiology 208 (2025) 106284] - Hafiz Muhammad Usman; Mohammad Mazharul Karim; Ayesha Kanwal; Qin Tan; Muhammad Dilshad Hussain; Wei-Xiao Yin; Yong Wang; Chao-Xi Luo (Pesticide Biochemistry and Physiology, 2025)

Synergistic PMS activation by SnBi@ZrC under visible light for enhanced organic pollutant removal - Rana Mohsin Ali; Jie Wang; Tianhong Zhou; Yue Tian; Muhammad Usman; Hamza Khaliq; Muhammad Adnan; Zunaira Nasir; Ghulam Abbas Ashraf; Yusuke Yamauchi (Journal of Water Process Engineering, 2025)

Influence of organic matter and mineral composition on carbonate source rock wettability: Implications for CO2 geostorage - Muhammad Usman; Nurudeen Yekeen; Muhammad Ali; Mujahid Ali; Alireza Keshavarz; Stefan Iglauer; Volker Vahrenkamp (Fuel, 2025)

Stabilization of sesame oil-in-water emulsions by synergistic complexation of tea saponin and gum arabic: Stability and rheological characterization - Usman Ali; Shahzad Farooq; Muhammad Ijaz Ahmad; Quancai Sun; Ye Peng; Meiyu Chen; Hui Zhang (Food Chemistry, 2025)

Multi-objective fuzzy fractional-order BELBIC for semi-active seismic control in non-linear building structures - Muhammad Usman Saeed; Peizhen Li; Said Elias (Engineering Structures, 2025)

Recent progress in biomass polymer based hydrogel membranes for adsorption and photocatalytic pollutants removal: fabrication, challenges and future perspectives - Muhammad Usman Hameed; Luqman Ali; Ayesha Ahmad; Pei Zhang; Saleem Raza; Sikandar Khan; Wei-Ren Liu; Zainab Amjad (Desalination, 2025)

Advances in anaerobic digestate management: functions and impacts of carbon and iron-based additives - Shuaishuai Ma; Xiaona Yu; Budi Mandra Harahap; Muhammad Usman Khan; Huiban He; Yafan Cai (Bioresource Technology, 2025)

Seed priming as a mitigation strategy for drought stress: Impacts on germination, growth, and antioxidant activity in sweet pepper (Capsicum annuum L.) - Sami Ullah; Muhammad Khalid; Muhammad Nafees; Fazal Amin; Sidra Khan Durrani; Usman Ali (Biocatalysis and Agricultural Biotechnology, 2025)

Evidential neural network and metaheuristic optimization algorithms for sustainable biomass utilization in bioethanol and bio-based chemical production - Jamilu Usman; Abdulhayat M. Jibrin; Muhammad A. Ahmad; A.G. Usman; Dahiru Lawal; M. Amin Mir; Sani I. Abba; Isam H. Aljundi (Biocatalysis and Agricultural Biotechnology, 2025)

Estimation of genome-wide patterns of homozygosity, heterozygosity and inbreeding in crossbred dairy cattle population in Pakistan - Fakhar Un Nisa; Muhammad Usman; Asad Ali; Muhammad Basil Ali; Haiba Kaul; Muhammad Asif; Raphael Mrode; Zahid Mukhtar (Tropical Animal Health and Production, 2025)

Response of tomato growth and transpiration under adequate elevated CO2 concentrations coupled with irrigation regimes - Muhammad Akhlaq; Henglu Miao; Chuan Zhang; Run Xue; Haofang Yan; Muhammad Usman Hameed; Jun Li; Jiangtao Ren; Junaid Nawaz Chauhdary; Muhammad Mahmood Ur Rehman (Irrigation Science, 2025)

Legume-grass intercropping at low nitrogen input: Achieving the dual goals of lower greenhouse gas emissions and high quality forage productivity in the arid region - Muhammad Kamran; Min Zhang; Qianmin Jia; Muhammad Usman; Moazma Waris; Shenghua Chang; Fujiang Hou (Agriculture, Ecosystems & Environment, 2025)

Impacts of seasonal grazing on soil enzymes, physicochemical properties, and vegetation in alpine meadows - Barkat Ali; Haozhe Zheng; Muhammad Usman; Weikang Zhao; Fujiang Hou (Agriculture, Ecosystems & Environment, 2025)

Phytochemical characterization and bioactivity evaluation of Himalayan lichen Usnea lapponica Vain.: antioxidant, antibacterial, and antibiofilm effects - Anja Manojlović; Abdul Nasir Khalid; Muhammad Usman; Olgica Stefanović; Nevena Đukić; Nedeljko Manojlović; Jovica Tomović (Natural Product Research, 2025)

Biobased carbon quantum dots: An emerging nano-enabled paradigm for pesticide removal and sustainable plant protection - Usman Arshad; Dan Chen; Haichao Cao; Chao Feng; Linwei Liu; Muhammad Amjad Ali; Zhang Wanhong; Yishan Li; Lijun Jiang; Jinguang Yang (Science of The Total Environment, 2025)

Corrigendum to: “Substitution of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China” [J Hazard Mater 465 (2024) 1–14 133118] - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2025)

A double-edged sword? Exploring the heterogeneous effects of industrialization, energy efficiency, and disaggregated financial development on environmental management - Zhou Li; Muhammad Usman; Muhammad Sohail Amjad Makhdum; Abdulrahman Alomair (Journal of Environmental Management, 2025)

Magnetic biochar for the remediation of arsenic contaminated water: A complete guide of science, synthesis, and solutions - Yasir Hamid; Yonglong Chen; Muhammad Haris; Muhammad Usman; Bilal Hussain; Muhammad Saqib Rashid; Temoor Ahmed; Muhammad Noman; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2025)

Mesozoic Muslim Bagh-Khanozai ophiolite mélange in the western Pakistan: implications for the tectonic evolution of the Neo-Tethys Ocean - Akram Ullah Khan; Yunpeng Dong; Saif Ur Rehman; Bo Hui; Muhmmad Usman; Muhammad Panezai (Journal of Asian Earth Sciences, 2025)

Optimizing cutting and mix-cropping improves forage yield and quality of cultivated grassland in a semi-arid environment - Muhammad Usman Ghani; Muhammad Kamran; Shree Prakash Pandey; Jiao Ning; Shanning Lou; Wanhe Zhu; Fujiang Hou (European Journal of Agronomy, 2025)

Genetic Enhancement of Sugar Recovery Percentage in Commercial Sugarcane by Inducing Sweet Sucrose Isomerase Gene III (SSGIII) - Mudassar Fareed Awan; Usman Arif; Muhammad Farhan Sarwar; Momna Toqeer Dar; Safia Obaidur Rab (Sugar Tech, 2025)

Analytical solutions of the eighth-order (3+1)-dimensional Kac–Wakimoto equation modeling waves in ocean engineering - Jan Muhammad; Ghulam Hussain Tipu; Usman Younas (Modeling Earth Systems and Environment, 2025)

Kaempferol alleviates cypermethrin induced reproductive toxicity in rats via Nrf2-mediated antioxidant and apoptotic regulation with histopathological evidence: in vivo and in silico study - Fahad Kabeer; Shaista Anjum; Atique Ahmed Behan; Muhammad Usman; Nazima Yousaf khan; Muhammad Azeem; Hafiz Misbah Ud Din; Muhammad Adeel Arshad; Sadaf Nazir; Shiping Cheng; Jameel Ahmed Buzdar (Journal of Molecular Histology, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Field-based evaluation of sugarcane bagasse biochar for managing root-knot nematodes in tomato - Maria Fayyaz; Amjad Abbas; Usman Arshad; Farrukh Azeem; Faiz Ahmad Joyia; Abdelaziz Hajjaji; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Optimizing diagnostic & management strategies for common arrhythmias in critically Ill surgical patients: A scoping review - Philip M. Lee; Kirk D. Dourvetakis; Andrew Ford; Minna Haddadi; Muhammad Usman Awan; Alexander Brown; Joseph Ibrahim; Adel Elkbuli (Next Research, 2025)

Exploring climate pollutants levels and variations in Islamabad's built-environment: A nature-based policy framework for sustainable emissions management - Hajra Qadeer; Muhammad Usman Khan; Zafeer Saqib; Riffat Naseem Malik (Journal of Environmental Management, 2025)

Isolation, Identification, biochemical and molecular characterization of potential source of enterotoxigenic strains of Staphylococcus aureus from the bovine raw and mastitis milk - Sikander Ali; Farzana Nazir; Muhammad Usman Ahmad; Hira Sarfraz; Abid Sarwar; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Areej A. Alhhazmi; Abeer M. Alghamdi; Fakhria A. Al-Joufi (International Dairy Journal, 2025)

Agent free pillaring engineering of interlayer spacing of Ti3C2 MXene layers for energy conversion and photothermal desalination - Min Wei Boey; Muhammad Ahmad; Jiawei Sun; Sai Kishore Ravi; Xue Wang; Muhammad Usman Farid; Alicia Kyoungjin An (Chemical Engineering Journal, 2025)

Evaluating the cooling potential of urban green spaces in Faisalabad integrating invest urban cooling model with multisource remote sensing data - Hafiz Abdul Basit Zaid; Usman Mahmood Mughal; Muhammad Amin; Meer Muhammad Sajjad; Muhammad Farhan; Amir Sattar; Shujaat Ali; Mujtaba Ali; Qurat ul Ain (Theoretical and Applied Climatology, 2025)

Biochemical validation for the therapeutic use of Plumeria rubra in coagulation disorders: a study combining in silico, in vitro, and in vivo approaches - Imran Ahmad Khan; Muhammad Anwar; Sarmad Frogh Arshad; Athar Hussain; Muhammad Usman; Mohammed Nadeem Ansari; Hasan Junaid Arshad; Asma Shah Rukh; Qurat Ul Ain; Maliha Khalid Khan (Protoplasma, 2025)

Tropical-extratropical interactions: the atmospheric dynamics behind Dubai's extreme precipitation in April 2024 - Muhammad Latif; Muhammad Usman; Abdul Malik; Sateesh Masabathini; Burhan Ahmad; Luqman Atique; Fatima Alhammadi; Ibrahim Hoteit (Natural Hazards, 2025)

Prediction of compressive strength of stone dust-based fly ash bricks: experimental study and advanced machine learning algorithm - Mehtab Alam; Adil Khan; Muhammad Umar; Tauqir Ahmed; Ahmad Yar Mazari; Muhammad Usman Arshad (Innovative Infrastructure Solutions, 2025)

Geostatistical and multivariate analysis of phosphate evolution and its relationship with heavy metals in shallow groundwater in a Semi-Arid Basin - Saadu Umar Wali; Noraliani Binti Alias; Abdulqadir Abubakar Usman; Abdullahi Umar; Nasiru Muhammad; Ismail Usman Kaoje; Buhari Samaila; Basiru Aliyu; Habiba Muhammad Ladan; Mudassiru Atiku; Sa’ad Ibrahim (Earth Science Informatics, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Unlocking complex interplay between economic growth, trade openness, financial development, environmental degradation, and environmental sustainability in Bangladesh and Pakistan - Ayesha Khan; Muhammad Zia ur Rehman; Sajjad Ahmad Baig; Muhammad Usman (Environment, Development and Sustainability, 2025)

Review on sea water quality (SWQ) monitoring using satellite remote sensing techniques (SRST) - Md Masudur Rahman; Roman Shults; Surya Prakash Tiwari; Arfan Arshad; Muhammad Usman; Asif Raihan; Md Fatin Ishraque (Marine Pollution Bulletin, 2025)

Sustainable immobilization strategy for Desertifilum tharense BERC-3 on corncobs to enhance biomass production and high-value metabolites - Muhammad Usman; Md Asraful Alam; Ayesha Shahid; Zhang Beixiao; Aqib Zafar Khan; Anqi Zhao; A.E. Solovchenko; Muhammad Aamer Mehmood; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

A review of temperature and key parameters influencing the hydrolysis-methanogenesis balance in anaerobic digestion - Huiban He; Xiaotian Chen; Zhang Peng; Zijian Zhang; Xiurong Ren; Shuaishuai Ma; Muhammad Usman Khan; Zongjun Cui; Xufeng Yuan (Fuel, 2025)

Enhanced catalytic stability for L-Dopa synthesis through cross-linking of Al₂O₃ nanocrystals with Bacillus subtilis tyrosine hydroxylase - Areesha Batool; Sikander Ali; Aneeba Rashid; Muhammad Usman Ahmad; Saba Sana; Luiza C. Campos (World Journal of Microbiology and Biotechnology, 2025)
This study focuses on enhancing L-Dopa synthesis by producing tyrosine hydroxylase from Bacillus subtilis SDSC-Env-i6 and its conjugation with aluminium oxide (Al₂O₃) nanoparticles. The free enzyme exhibited moderate activity, which was significantly improved through nanoparticle conjugation. Structural characterisation confirmed successful binding, with Al₂O₃ nanoparticles showing a crystalline nature and sizes ranging from 124 to 130 nm. Compared to the free enzyme, the Al₂O₃-conjugated tyrosine hydroxylase demonstrated markedly enhanced catalytic activity, reaching up to 15.3 ± 0.05 U/mL under optimised conditions. In contrast, maximum activities for the free enzyme were 5.5 ± 0.05 U/mL and 6.3 ± 0.11 U/mL in the presence of CuCl₂ and CaCl₂, respectively. The cross-linked enzyme also showed superior stability and efficiency across varying conditions. L-Dopa production was significantly higher with the conjugated enzyme, yielding between 0.531 and 1.105 mg/mL under optimised incubation conditions. These values were notably greater than those achieved using the free enzyme across different pH levels, volumes, and incubation times. Spectroscopic and microscopic analyses confirmed the integrity and functionality of the enzyme-nanoparticle complex. The observed improvements in both enzyme activity and L-Dopa yield were statistically significant ( p ≤ 0.05), underscoring the potential of Al₂O₃ nanoparticle-conjugated tyrosine hydroxylase as an efficient and scalable biocatalyst for commercial L-Dopa production. Determination of kinetic parameters showed maximum V max /K m (1.25 × 10 6 ) was observed when immobilized tyrosinase activity was characterized with tyrosine as substrate, with significant K cat value of 1.48 × 10 18 s − 1 .

Microbial Synthesis of ZnO Nanoparticles: A Green Strategy for Mitigating Wastewater Stress in Wheat (Triticum aestivum) - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Hafiz Muhammad Rizwan; Muhammed Umair Hassan; Muhammad Irfan; Muhammad Adnan; Faisal Mahmood (Water, Air, & Soil Pollution, 2025)

Effect of MXenes, nZVI and Acacia-wood Biochar Treatments on Bioavailability Pb and Fractions in Calcareous-polluted Soils - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Usman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal (Water, Air, & Soil Pollution, 2025)

Impact Analysis of Climate Change, Socioeconomic Development, and Hydropower Generation on Water Availability in the Chitral River Basin Using Water Evaluation and Planning (WEAP) Model - Bushra Zaman; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem; Muhammad Kaleem Sarwar; Muhammad Waseem; Mudassar Iqbal; Shakeel Hayat; Khalil Ahmed; Muhammad Usman (Water Conservation Science and Engineering, 2025)
Water, energy, and food are three major issues of concern because of the rapid growth of the population and economy, which are exacerbated by climate change. The disparity between the availability and demand of water is largely driven by domestic and agricultural uses, and it is important to evaluate its impact on hydropower generation. This study aims to integrate climate change, socioeconomic development, and hydropower generation analysis using the water evaluation and planning model (WEAP). This study uses the CMIP6 model to make future projections under shared socioeconomic pathways (SSPs). This study examined the projections of water demand under different scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) using the MPI-ESM1-2HR climate change model. In the reference year 2000, domestic water demand stood at 15 MCM, escalating to 54 MCM under the SSP5-8.5 scenario. Concurrently, agricultural water demand, which was 93.72 MCM in 2000, is projected to surge to 197.35 MCM by 2050. Based on expected future changes in streamflow, the results show that Golen Gol’s hydropower potential varies with the effects of socioeconomic and climatic changes. However, the fluctuation in hydropower generation is more prominent during June and July, leading to an increase in hydropower in future scenarios. The study findings suggest that by 2050, the combination of population growth and agricultural expansion will substantially escalate water demand, posing risks to both the environment and human populations. Consequently, adopting enhanced irrigation methods, refining agricultural techniques, and erecting water conservation and retention infrastructures could effectively mitigate these challenges. To formulate sustainable water management strategies, it is advised to further utilize the integrated water–energy–food nexus approach, strengthened by merging WEAP with the energy modeling program Low Emissions Analysis Platform (LEAP) for hydropower generation.

Numerical modelling of vadose zone flow for a shallow groundwater wetland using HYDRUS-1D - Muhammad Usman; Lloyd H. C. Chua; Kim N. Irvine; Lihoun Teang (Modeling Earth Systems and Environment, 2025)
This study employs HYDRUS-1D for modelling the vadose zone processes in a shallow groundwater wetland. HYDRUS-1D is based on Richards equation whose numerical solution heavily relies on reliable data derived from soil water retention curves. This modelling was supported by extensive field and laboratory measurements. Both disturbed and undisturbed soil samples were collected at the four depths for determination of particle size distribution, bulk density, saturated hydraulic conductivity, and saturated water content. The van Genuchten retention curves were used to describe the relationship between pressure head and water content; model parameters were optimized through inverse modelling with initial estimates of residual water content, shape parameters (α and n) obtained from ROSETTA model 3 (provided in HYDRUS-1D) and saturated water content and saturated hydraulic conductivity, determined from laboratory tests. Independent measurements of soil moisture and soil tension measured both in the field and laboratory fit well with the water retention curve obtained from the optimized ROSETTA parameters. Model performance in simulating measured water contents was good (average RMSE = 0.02 m 3 /m 3 ) during calibration and validation (0.01 m 3 /m 3 and 0.03 m 3 /m 3 for two independent periods). Water content in upper soil layers was strongly influenced by atmospheric conditions, while groundwater level has the most influence in the bottom layers. Evapotranspiration was found out to be the dominant process in summer with total flux higher than that of infiltration while in winter evapotranspiration was relatively lower, even though still higher than infiltration.

Wave propagation and multistability analysis to the modified fractional KDV-KP equation in diversity of fields - Jan Muhammad; Usman Younas (Modeling Earth Systems and Environment, 2025)

Synthesis, biological evaluation, and in silico studies of chalcone-based ketamine derivatives with preferential COX-2 inhibitory activity - Syed Muzzammil Masaud; Humaira Nadeem; Abida Shamim; Muhammad Kazim Zargaham; Usman Shareef; Sana Ayaz; Babar Murtaza (Medicinal Chemistry Research, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

Adaptive responses of trees to industrial pollution: modulation of leaf anatomical, physio-biochemical, and heavy metal accumulation traits in urban biotopes - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Mansoor Javaid; Usman Zulfiqar; Nafosat Djonibekova; Anarjan Matkarimova; Hesham S. Almoallim; Mohammad Javed; Shafeeq Ur Rahman (Environmental Monitoring and Assessment, 2025)

Elucidating the synergistic activity of biocontrol agents in combating Xanthomonas citri pv. malvacearum and promoting of physio-chemical responses in cotton - Usman Arshad; Yaxing Feng; Muhammd Raheel; Waqas Ashraf; Muhammad Amjad Ali; Iqra Naeem; Kexin Liu (Physiological and Molecular Plant Pathology, 2025)

Biogenic silver nanoparticles to control rice blast caused by Magnaporthe oryzae - Muhammad Shahid; Paul K. Goetze; Usman Shafqat; Young-Ki Jo (Physiological and Molecular Plant Pathology, 2025)

Scalable interlinked hierarchical porous biochar-nanosheets for efficient removal of thallium from aquatic environment - Haitao Ren; Zainab Amjad; Atif Saleem; Muhammad Usman; Kukybayeva Dina; Muhammad Haris; Junkang Guo (Journal of Hazardous Materials, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Rapid synthesis of charged covalent organic framework for sustainable reverse osmosis membranes - Umar H. Nuhu; Niaz Ali Khan; Ijaz Hussain; Mengying Long; Billel Salhi; Nadeem Baig; Ismail Abdulazeez; Khan Alam; Sikandar Khan; Muhammad Usman; Umer Zahid; Isam H. Aljundi (Desalination, 2025)

Protective effects of hydroethanolic extract of Mentha longifolia L. leaves against hepato-renal toxicity induced by furan exposure: In vivo and In silico studies - Meryem Tourabi; Asmae EL. Ghouizi; El Hassania Loukili; Abderrazak Aboulghazi; Otmane Zouirech; Farhan Siddique; Ahmed Elfallaki Elidrissi; Muhammad Usman Qamar; Ahmad Mohammad Salamatullah; Abdulaziz Abdullah Alsahli; Mohammed Bourhia; Badiaa Lyoussi; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Probabilistic seismic loss estimation for residential buildings in Pakistan - Sajid Mehmood; Zainulabideen Ali Khan; Fawad Ahmed Najam; Muhammad Usman (Natural Hazards, 2025)

Synergistic Effects of 5-Ureidohydantoin, Rhizobacteria and Non-wood-Based Biochar on Barley Productivity Under Drought and Multiple Toxic Metals Stress - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Abdul Razzaq; Iram Saba; Gang Deng; Zeeshan Ahmed; Abdel-Rhman Z. Gaafar; Trobjon Makhkamov; Lala Gurbanova; Rashid Iqbal (Current Microbiology, 2025)

The environmental impacts via life cycle assessment of activated carbon produced by Fiddlewood and Jacaranda biomass - Muhammad Amin; Hamad Hussain Shah; Muhammad Usman; Muhammad Azhar Iqbal (Clean Technologies and Environmental Policy, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

First report of Curvularia hawaiiensis causing leaf spot disease of grape in Pakistan - Muhammad Usman Ali; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Owais Iqbal; Muhammad Hamza Furqan; Ahmad Nawaz; Hamza Tariq; Ghalib Ayaz Kachelo; Nasir Ahmed Rajput (Journal of Plant Pathology, 2025)

Characterising the Urban Heat Island in a low-rise indigenous city using remote sensing - Muhammad Usman; Janet E. Nichol; Ayman M. Abdallah; Muhammad Bilal (Urban Climate, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

Tailored synthesis of heterojunction CuNTiO2 and g-C3N4 composite for advanced degradation of 1,2,4-trichlorobenzene under visible light - Olive Mekontchou Yemele; Zhenhua Zhao; Ervice Ymele; Abduelrahman Adam Omer; Muhammad Usman; Liling Xia; Cedric Karel Fonzeu Monguen; Teng Binglu; Franck Ghislain Emani (Journal of Water Process Engineering, 2025)

Staged pyrolysis of medical waste for high-value product generation: Impact of inter-component interactions on chlorine migration and light compounds formation - Yuhang Zheng; Tong Zhang; Aijun Li; Yongda Huang; Muhammad Usman; Chao Liao; Qian Deng; Hong Yao (Journal of Cleaner Production, 2025)

Exogenous Application of Nitrogen (N) and Potassium (K) Improves Drought Tolerance in Plants: A Review - Saira Sulaman; Muhammad Nadeem; Muhammad Shabaan; Sule Orman; Muhammad Anwar-ul-Haq; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)
With rising climate anomalies and deterioration of ecological balance, water shortage has emerged as a major environmental problem faced by mankind, which has considerably limited agricultural productivity worldwide. Drought stress generates an insidious hazard by destabilizing global hydrological cycle and due to its increased frequency, severity and associated adverse impacts on climate conditions, drought has obtained attention world over. Exposure to severe and acute drought stress disturbs physiological functioning of plants and inhibits the efficiency of photosynthetic system. As a result, lesser photosynthate production causes lower plant biomass and yield. Hence, it is imperative to sustain and improve plant growth and productivity under water shortage conditions to minimize its dreadful impacts. Current review summarizes the adverse impacts of drought stress on various agricultural crops, its alleviation strategies and various adaptations encountered by plants under drought stress. More importantly, current review emphasizes the beneficial roles played by macronutrients such as nitrogen (N) and potassium (K) in alleviating the adverse impacts of drought stress. As these essential nutrients have reportedly been involved in alleviating the negative impacts of drought stress on plant growth and therefore, major information in the current review article revolves around the N and K supply to the plant under drought stress. In addition, current review necessitates the use of optimum doses of N and K fertilizers to ensure maximum resource utilization efficiency and increased drought resilience.

Zinc Biofortification in Cereal Crops: Overview and Prospects - Muhammad Fraz Ali; Lijuan Ma; Sidra Sohail; Usman Zulfiqar; Tajamul Hussain; Xiang Lin; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Numerical investigations on RC beam-column structures under collapse phenomenon—a simplified finite element approach - Aleem Ullah; Abdul Qadir Bhatti; Attiq Ur Rahman Dogar; Girum Urgessa; Muhammad Usman (Innovative Infrastructure Solutions, 2025)

A comprehensive review on the bioactivity and pharmacological attributes of Withania somnifera - Muhammad Usman Khalid; Muhammad Tauseef Sultan; Iqra Baig; Asad Abbas; Ahmad Mujtaba Noman; Abdellah Zinedine; Elena Bartkiene; João Miguel Rocha (Natural Product Research, 2025)

Metal sulfides in aged-coarse sands tailings facilitate naphthenic acids removal from oil sands process water - Muhammad Arslan; Muhammad Usman; Mohamed Gamal El-Din (Water Research, 2025)

CO2 agitation combined with magnetized biochar to alleviate “ammonia inhibited steady-state”: Exploring the mechanism by combining metagenomics with macroscopic indicators - Jiadong Yu; Muhammad Usman; Fan Liu; Franziska Schäfer; Yuhan Shen; Zehui Zheng; Yafan Cai (Water Research, 2025)

High soil bacterial diversity increases the stability of the community under grazing and nitrogen - Muhammad Usman; Mengyuan Wang; Yang Liu; Lan Li; Xiumin Zhang; Tianhao Xiao; Fujiang Hou (Soil and Tillage Research, 2025)

Simultaneous removal of PFAS and cadmium from different water matrices using regenerable carbonaceous adsorbents - Aaifa Chaudhary; Muhammad Usman; Ondřej Mašek; Stefan Haderlein; Khalil Hanna (Journal of Water Process Engineering, 2025)

Synergistic defect engineering and z-scheme heterojunction in ultrasonication assisted CuFe LDH and carbon vacancies modified g-C3N4 composite for electrocatalytic water splitting and photocatalytic dye degradation - Muhammad Usman; Khurram Imran Khan; Samia; Sidra Khalid; Faiq Saeed; Abdul Wahab; Muhammad Sajjad Asghar; Ahmad Althobaiti; Alsharef Mohammad; Haitao Dai (Journal of Water Process Engineering, 2025)

Evaluation of cotton (Gossypium hirsutum L.) seed longevity and deterioration: Physiological and biochemical aspects in relation to moisture contents during storage in different module systems - Faryal Fatima; Ehsan Khalid; Irfan Afzal; Muhammad Usman; Muhammad Ather Nadeem; Muhammad Kamran (Journal of Stored Products Research, 2025)

Effect of Spirulina platensis on the structure and aggregation of gluten proteins to improve texture and physiochemical properties of wheat noodles - Kerui Su; ZhiHao Fan; Muhammad Usman; Anqi Zhao; Hanyu Dong; Xuejing Duan; Longfei Weng; Ayesha Shahid; Jingliang Xu (Food Hydrocolloids, 2025)

Thermally efficient hydrophobic zirconia ceramic nanofiber membrane for enhanced membrane distillation performance - Min Wei Boey; Shahid Ali Khan; Xiaolu Li; Jiawei Sun; Muhammad Usman Farid; Alicia Kyoungjin An (Chemical Engineering Journal, 2025)

Mapping sagebrush volatile chemotypes along an elevational gradient - Richard Karban; Muhammad Usman Rasheed; Mikaela Huntzinger; Patrick Grof-Tisza; James Blande (Plant Ecology, 2025)

Gender Perspectives in Environmental Initiatives across Developing Countries - Ilyas Ahmad; Muhammad Usman; Shahbaz Imran; Wang Yue (Environmental Management, 2025)

Combined asymmetric influences of renewable energy consumption and categorical economic policy uncertainty on economic growth in Japan: New insights from QQR and KRLS approaches - Sanjeet Singh; Gagan Deep Sharma; Magdalena Radulescu; Muhammad Usman; Daniel Balsalobre-Lorente (Environment, Development and Sustainability, 2025)

Biomonitoring and phytoremediation potential of Conocarpus erectus (Buttonwood) for mitigating air pollution from highway traffic - Akkasha Azam; Ummar Iqbal; Zartasha Usman; Muhammad Sharif; Muhammad Faisal Gul; Nargis Naz; Ifrah Nawaz; Farooq Ahmad (Chemosphere, 2025)

First report of Botryosphaeria wangensis, Colletotrichum nymphaeae, Diaporthe eres, and Geotrichum candidum causing postharvest fruit rot of plums (Prunus salicina) in China - Yu-Ru Wang; Bo-Ying Huang; Hafiz Muhammad Usman; Khadija Javed; Fatimah Al-Otibi; Kevin D. Hyde; Yong Wang (Crop Protection, 2025)

Bolstering environmental sustainability in the BRICS countries: The role of natural resources, energy diversity, and human capital in sustainable development - Yongming Huang; Sherkhanov Ulugbek; Muhammad Usman (Journal of Environmental Management, 2025)

Development and exploration of casein-based nano-encapsulation of mangiferin for cow milk allergy management and immunomodulation - Muhammad Junaid Anwar; Aneela Hameed; Muhammad Usman Khan; Aimen Mazhar; Hafiz Muhammad Irfan Manzoor (Food Bioscience, 2025)

Environmental risk factors for all-cause dementia, Alzheimer's disease dementia, vascular dementia, and mild cognitive impairment: An umbrella review and meta-analysis - Aaron Jones; Muhammad Usman Ali; Alexandra Mayhew; Komal Aryal; Rebecca H. Correia; Darly Dash; Derek R. Manis; Atiya Rehman; Megan E. O'Connell; Vanessa Taler; Andrew P. Costa; David B. Hogan; et al. (Environmental Research, 2025)

Improved damage assessment of bridges using advanced signal processing techniques of CEEMDAN-EWT and Kernal PCA - Hamza Ahsan Abdullah; Muhammad Usman Hanif; Muhammad Usman Hassan; Janita Mahnoor Shahid; Shaukat Ali Khan; Ather Ali (Engineering Structures, 2025)

Recent progress in 2D-MXene-based membranes for water treatments; fabrication, properties, and advanced desalination application - Muhammad Usman Hameed; Zainab Amjad; Basem Al Alwan; Atef El Jery; Hassan M.A. Hassan; Luqman Ali; Ayesha Ahmad; Sikandar Khan; Saleem Raza (Desalination, 2025)

Manipulating electron shuttling in photo fermentative biohydrogen production from lignocellulosic biomass through engineered Z-scheme photo nanocatalysts - Muhammad Usman; Faiqa Nadeem; Farzana Jabeen; Muneeb Ur Rahman; Hina Ramzan; Muhammad Shahzaib; Zhiping Zhang; Nadeem Tahir (Chemical Engineering Journal, 2025)

Utilizing different food cultures for wastewater treatment and enhanced power generation in microbial fuel cells - Tariq Nawaz Chaudhary; Shaheryar Ahmed; Muhammad Usman; Ali O.M. Maka; Shafqat Rasool; Mohammad Ghaleeh; Baixin Chen (Biomass and Bioenergy, 2025)

Selecting Relevant Features for Random Forest-Based Crop Type Classifications by Spatial Assessments of Backward Feature Reduction - Talha Mahmood; Muhammad Usman; Christopher Conrad (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
Random Forest (RF) is a widely used machine learning algorithm for crop type mapping. RF’s variable importance aids in dimension reduction and identifying relevant multisource hyperspectral data. In this study, we examined spatial effects in a sequential backward feature elimination setting using RF variable importance in the example of a large-scale irrigation system in Punjab, Pakistan. We generated a reference classification with RF applied to 122 SAR and optical features from time series data of Sentinel‑1 and Sentinel‑2, respectively. We ranked features based on variable importance and iteratively repeated the classification by excluding the least important feature, assessing its agreement with the reference classification. McNemar’s test identified the critical point where feature reduction significantly affected the RF model’s predictions. Additionally, spatial assessment metrics were monitored at the pixel level, including spatial confidence (number of classifications agreeing with the reference map) and spatial instability (number of classes occurring during feature reduction). This process was repeated 10 times with ten distinct stratified random sampling splits, which showed similar variable rankings and critical points. In particular, VH SAR data was selected when cloud-free optical observations were unavailable. Omitting 80% of the features resulted in an insignificant loss of only 2% overall accuracy, while spatial confidence decreased by 5%. Moreover, the crop map at the critical point exhibited an increase in spatial instability from a single crop to 1.28. McNemar’s test and the spatial assessment metrics are recommended for optimized feature reduction benchmarks and identifying areas requiring additional ground data to improve the results.

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Nanoparticle-Mediated Phytohormone Interplay: Advancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Fozia Farhat; Saher Nawaz; Muhammad Ahmad (Journal of Crop Health, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

UBEM-SER: Role of sufficiency, efficiency and renewable in the decarbonization of commercial building stock at city scale - Usama Perwez; Muhammad Haseeb Rasool; Imran Aziz; Usman Zia (Sustainable Cities and Society, 2025)

Do political cooperations and regulations manage Africa's sustainable mineral policy? - Mehmet Akif Destek; Muhammad Usman; Najia Saqib (Resources Policy, 2025)

Exploring mechanisms of resistance to fludioxonil in Colletotrichum fructicola - Hafiz Muhammad Usman; Mohammad Mazharul Karim; Ayesha Kanwal; Qin Tan; Muhammad Dilshad Hussain; Wei-Xiao Yin; Yong Wang; Chao-Xi Luo (Pesticide Biochemistry and Physiology, 2025)

Enhanced charge transferring through defects-mediated metal‑carbon nanocomposites for efficient dye degradation under visible light - Muneeb Ur Rahman; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Hina Ramzan; Nimra Nadeem; Zhiping Zhang; Nadeem Tahir (Journal of Water Process Engineering, 2025)

Highly efficient degradation of norfloxacin by using Co3O4-CeO2 as a heterogeneous catalyst through peroxymonosulfate activation: Characterization, catalytic performance and mechanism - Muhammad Rafiq; Raza Ullah; Adeel Ahmed; Xin Liu; Muhammad Usman; Qinghua Cao; Muhammad Adnan; Muhammad Fayaz; Waqas Haider; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Energy balance modelling of snow and ice melt for the Naltar catchment (Karakoram, Pakistan) in future climate - Muhammad Usman Liaqat; Ana Casanueva; Rubina Ansari; Giovanna Grossi; Roberto Ranzi (Journal of Hydrology, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Spatial insights into microplastics and heavy metals levels, and risks in wastewater irrigated surface soils of Okara, Pakistan: Microplastics sizes impacts on heavy metals distribution using structure equation model - Sana Rubab; Muhammad Usman Khan; Maryem Mehboob; Riffat Naseem Malik (Environmental Pollution, 2025)

Enhancing irrigation scheduling by application efficiency estimations and soil moisture simulations - Jan Lukas Wenzel; Julia Pöhlitz; Muhammad Usman; Thomas Piernicke; Christopher Conrad (European Journal of Agronomy, 2025)

ICT-driven urbanization and energy security risk: Empirical evidence from Group 7 and Emerging 7 economies - Ahmed Usman; Syed Muhammad Muddassir Abbas Naqvi; Ilhan Ozturk; Ali Hassan; Asma Arif (Environmental Impact Assessment Review, 2025)

A highly stretchable, self-healing, self-adhesive polyacrylic acid/chitosan multifunctional composite hydrogel for flexible strain sensors - Rulong Lv; Xuan Cao; Taoyi Zhang; Wenxi Ji; Usman Muhammad; Jing Chen; Yun Wei (Carbohydrate Polymers, 2025)

Changes in the probability of temporally compound wet and dry events in a warmer world: case study in the Upper Jhelum Basin—South Asia - Rubina Ansari; Ana Casanueva; Muhammad Usman Liaqat; Giovanna Grossi (Regional Environmental Change, 2025)
Temporal compound events (TCEs), such as the consecutive occurrence of two complementary extremes of the hydrological spectrum (floods and droughts), exhibit a volatile hydrological cycle that exacerbate the challenges associated with water resources management. This study makes use of bias-corrected climate models output from three modeling experiments (CMIP6, CORDEX, and CORDEX-CORE), to examine moderate to extreme wet and dry events and their temporal compounding over the Upper Jhelum Basin (UJB), under low, medium, and high emission scenarios for two future periods (2040–2059 and 2080–2099). Standardized Precipitation Evapotranspiration Index (SPEI) is used to quantify the meteorological wet and dry events that are the main driver of the hydrologic floods and droughts. The two types of TCEs considered in the current study are wet-to-dry (W-to-D) events and dry-to-wet (D-to-W) events in the adjacent month. Results indicate that (1) under warming conditions, wet and dry events are expected to become more frequent and severe whereas duration of the events exhibits distinct change signals depending on the specific location. (2) The basin is more prone to D-to-W TCEs dominated in the southwest of the region, which was not found to be hotspot historically neither for dry nor for wet extreme events. (3) CORDEX and CORDEX-CORE ensembles show varying climate change signals with no specific spatial pattern whereas the CMIP6 ensemble shows stronger change signals and divides the region into two distinct parts, i.e., northeast and southwest.

Significance of Selenium in Improving the Yield and Quality of Quinoa Under Drought - Muhammad Usman Aslam; Muhammad Aown Sammar Raza; Rashid Iqbal; Salman Ahmad; Imran Haider; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Saltanat Aghayeva; Nazim S. Gruda (Journal of Soil Science and Plant Nutrition, 2025)

Harnessing the Duo Effect of Plant Growth-Promoting Rhizobacteria and Organic Amendments in the Phytoremediation of Cadmium: a Review - Muhammad Junaid Sarwar; Muhammad Shabaan; Muhaimen Ayyub; Zahir Ahmad Zahir; Hafiz Naeem Asghar; Kashiuf Asif; Aqsa Shareef; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)

Transcriptome analysis of the taproot meristem region in contrasting orange carrot breeding lines under varying levels of drought stress - Usman Khalid Chaudhry; Muhammad Daniyal Junaid; Ali Fuat Gökçe; Zahide Neslihan Öztürk (Acta Physiologiae Plantarum, 2025)

Food security in Punjab, Pakistan: rural views on climate disasters and their impacts - Muhammad Usman; Asghar Ali; Sajjad Ahmad Baig; Magdalena Radulescu; Azhar Abbas; Rimsha Akram (Environment, Development and Sustainability, 2025)

In-silico evaluation of Cassia occidentalis phytochemicals for Plasmodium falciparum plasmepsin V inhibition: Revealing antimalarial potential - Aliyu Usman Maaji; Ramgopal Dhakar; Pankaj Kumar Teli; Umesh Garu; Umar Aliyu Adamu; Saminu Saminu Muhammad; Khalipha Ali Jubril; Fatima Idris Sambo (South African Journal of Botany, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Towards a green economy: Investigating the impact of sustainable finance, green technologies, and environmental policies on environmental degradation - Muhammad Ahsan Iqbal; Wasim Abbas Shaheen; Suheela Shabir; Usman Ullah; Ienciu Ionel-Alin; Marius-Ioan Mihut; António Raposo; Heesup Han (Journal of Environmental Management, 2025)

A ternary dumbbell MoS2 tipped Zn0.1Cd0.9S nanorods visible light driven photocatalyst for simultaneous hydrogen production with organics degradation in wastewater - Muhammad Tayyab; Yaoshu Xie; Xianjun Tan; Muhammad Usman; Man-Chung Tang; Season Si Chen (Chemical Engineering Journal, 2025)

Estimating water surface elevation for a wetland using integrated multi-sourced remote sensing data - Muhammad Usman; Lloyd H. C. Chua; Kim N. Irvine; Lihoun Teang (Wetlands Ecology and Management, 2025)
Surface water plays an important role in understanding the hydrological behaviour of a wetland and is crucial for the sustainability of wetland ecosystems. Remote sensing increasingly is used for the estimation of surface water levels in larger inland waterbodies. However, there are few investigations that have employed multi-sourced remote sensing data for water level predictions in wetlands, which was the motivation for undertaking this study. Sentinel-2 and Landsat-8 are among the latest satellites providing optical imagery with high spatial resolution and coverage that are available in the public domain. Different water indices have been applied to estimate surface water levels using these satellite image sources; however, what index to use for a particular application requires thorough, site-specific analysis. In this study, the Normalized Difference Water Index (NDWI), two versions of the Modified Normalized Difference Water Index (MNDWI), and the Water Ratio Index (WRI) were used to estimate water levels in a constructed wetland, as part of an effort to better guide regulation and decision-making for a local management agency. The satellite data were complemented with high resolution aerial photogrammetric images and LiDAR data to assess the accuracy of water level predictions provided by the satellite images. The photogrammetric images were used as reference datasets while the LiDAR data supported the development of area-elevation curves for the wetland. Accuracy assessment between the satellite and reference images was performed using the Kappa co-efficient (K). MNDWI performed better than the other water indices for both satellite data sources; however, the optimum threshold was different for each satellite (− 0.35 for Sentinel-2 and − 0.25 for Landsat-8). K values for the optimum threshold ranged between 0.72 and 0.77 for Sentinel-2 and 0.73 and 0.87 for Landsat-8. The water levels estimated using the remotely sensed data were assessed against in situ, continuously measured water levels using multiple efficiency evaluation metrics including R 2 , RMSE, and SSE. Estimated water levels with Sentinel-2 and Landsat-8 resulted in an R 2 of 0.86 and 0.88, RMSE of 0.04 m and 0.06 m, and an SSE of 0.02 m and 0.06 m, respectively. These results show that even for a small wetland, it is possible to use satellite imagery to estimate water levels with high accuracy.

Optimization of Extreme Learning Machine with Metaheuristic Algorithms for Modelling Water Quality Parameters of Tamburawa Water Treatment Plant in Nigeria - Sani I. Abba; Quoc Bao Pham; Anurag Malik; Romulus Costache; Muhammad Sani Gaya; Jazuli Abdullahi; Sagiru Mati; A. G. Usman; Gaurav Saini (Water Resources Management, 2025)

A Global Perspective on the Biology, Impacts and Management Options of Leptochloa chinensis, a Noxious Weed of Direct-seeded Rice—A Review - Muhammad Ishfaq; Zarina Batool; Usman Zulfiqar; Muhammad Ahmad; Fasih Ullah Haider; Nasim Ahmed; Saddam Hussain; Shakeel Ahmed Anjum; Nadeem Akbar (Journal of Crop Health, 2025)

Ameliorative Effects of Silica on Growth, Antioxidant Response, and Metal Uptake in Chromium-Exposed Wheat - Khadija Ali; Muhammad Nadeem; Asia Khan; Rafia Mustafa; Muhammad Shabaan; Usman Zulfiqar; Sadam Hussain; Jawaher Alkahtani (Journal of Crop Health, 2025)

Exposure to spaceflight enhances the virulence of Purpureocillium lilacinum against Tetranychus cinnabarinus: modulation of the host’s enzyme activities and microbiome - Xiaoxiao Wang; Fangzhao Yi; Chengli Zou; Qi Yan; Muhammad Hamid Bashir; Waqar Ahmed; Syed Usman Mahmood; Jianhui Wu; Shaukat Ali (Archives of Microbiology, 2025)

Flood vulnerability assessment of buildings using geospatial data and machine learning classifiers - Tze Huey Tam; Muhammad Zulkarnain Abd Rahman; Sobri Harun; Ismaila Usman Kaoje; Mohd Radhie Mohd Salleh; Mohd Asraff Asmadi (Acta Geophysica, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Evaluation of mechanical responses of asphalt mixtures incorporating plastic waste as additives by different compaction efforts and mixing temperatures for a sustainable mixture - Siti Nur Naqibah Kamarudin; Muhammad Naqiuddin Mohd Warid; Mohd Zul Hanif Mahmud; Haryati Yaacob; Kabiru Usman Rogo; Mohd Khairul Afzan Mohd Lazi (Environmental Science and Pollution Research, 2025)

The Baroch Nala section (NE Pakistan): A new PETM standard for the eastern Tethys - Mubashir Ali; Giovanni Coletti; Eduardo Garzanti; Thierry Adatte; Sébastien Castelltort; Pietro Sternai; Andrea Benedetti; Elisa Malinverno; Luca Mariani; Jorge E. Spangenberg; Suleman Khan; Daniela Basso; et al. (Marine and Petroleum Geology, 2025)

Unlocking the structure-activity relationship of hierarchical MFI zeolites towards the hydrocracking of HDPE - Muhammad Usman Azam; Auguste Fernandes; Maria João Ferreira; Alan J. McCue; Inês Graça; Waheed Afzal (Fuel, 2025)

MXenes: Transforming advanced materials through electrochemical reduction reactions – Opportunities and challenges - Tahir Rasheed; Sameera Shafi; Muhammad Tuoqeer Anwar; Rabia Ahmad; Muhammad Sheraz Ahmad; Muhammad Usman; Khaled Fahmi Fawy (Chemical Engineering Journal, 2025)

Biotransformation of chloramphenicol by enriched bacterial consortia and the newly isolated bacterial strain Bordetella sp. C3: Detoxifying biotransformation pathway and its potential application in agriculture - Yuanliang Wang; Yujiang Luo; Zewen Tan; Xingjun Lu; Li Zhao; Muhammad Usman Ghani; Weimin Sun; Youhua Ren (Bioresource Technology, 2025)

Sustainable bioenergy potential of peat-moss derived hydrothermal aqueous phase: Insights into methane production and organic transformation - Muhammad Usman; Gang Luo; Mohamed Gamal El-Din (Bioresource Technology, 2025)

Impact of biogenic zinc oxide nanoparticles on physiological and biochemical attributes of pea (Pisum sativum L.) under drought stress - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Muhammad Iqbal; Faisal Mahmood; Muhammad Umair Hassan (Physiology and Molecular Biology of Plants, 2025)

H2S and SO2 toxic gases removal using date palm-tree branches based activated carbon: experimental findings and machine learning (ML) modeling - Usman M. Ismail; Minaam Hussaini; Muhammad S. Vohra (Environment, Development and Sustainability, 2024)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Carbonaceous materials for adsorptive removal of perfluoroalkyl and polyfluoroalkyl substances (PFAS) and regeneration of spent adsorbents - Aaifa Chaudhary; Muhammad Usman; Stefan Haderlein; Khalil Hanna (Journal of Water Process Engineering, 2024)

Unveiling the biosorption performance of silk fibroin fiber for Pb(II) and Cr(VI) removal: Machine learning and DFT analysis - Muhammad Usman Farooq; Hammad Khan; Muhammad Arshad; Muhammad Usama; Mohammad Ilyas Khan; Sajjad Hussain; Ali Hamid (Journal of Water Process Engineering, 2024)

Efficient removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) from aqueous solution using modified biochar: Preparation, performance, and mechanistic insights - Waqas Niaz; Dahai Zhang; Zia Ahmad; Nan Shen; Waqas Haider; Imran Ali; Muhammad Usman; Abdul Majid; Sheikh Fahad Javaid; Muhammad Ahsan Amjed; Xianguo Li (Journal of Environmental Chemical Engineering, 2024)

Icewine fingerprint involved in latitude under climate change - Wanxia Sun; Zichun Zhu; Li Wang; Ruixuan Ren; Lei Wang; Muhammad Usman; Jiyuan Wang; Yiwen Zhu; Xunju Liu; Songtao Jiu; Philippe Gallusci; Shiping Wang; et al. (Food Research International, 2024)

Frontier of metal-organic framework nanofillers for pre-eminent membrane distillation applications - Nagendra Kumar Jilagam; Gaurav Vaghela; Tina Chakrabarty; Jiaxin Guo; Muhammad Usman Farid; Sanghyun Jeong; Ho Kyon Shon; Alicia Kyoungjin An; Bhaskar Jyoti Deka (Desalination, 2024)

Heterojunction interface engineering enabling high transmittance and record efficiency in Sb2S3 semitransparent solar cell - Muhammad Ishaq; Xuerui Li; Safdar Mehmood; Yi-Ming Zhong; Adil Mansoor; Usman Ali Shah; Shuo Chen; Yuexing Chen; Zhuanghao Zheng; Guangxing Liang (Chemical Engineering Journal, 2024)

Elucidating the bioremediation potential of laccase and peroxidase enzymes from Bacillus ligniniphilus L1 in antibiotic degradation: A computationally guided study - Muhammad Zohaib Nawaz; Hafiz Rameez Khalid; Muhammad Usman Mirza; Lingxia Xu; Syed Zeeshan Haider; Khalid A. Al-Ghanim; Damià Barceló; Daochen Zhu (Bioresource Technology, 2024)

Overexpression of Gossypium arboreum 3-ketoacyl-CoA synthase 6 (GaKCS6) gene enhanced leaf epicuticle wax in Gossypium hirsutum L. and improved tolerance against whitefly - Muhammad Umair Majid; Rabiah Ashraf; Basit Jabbar; Usman Arif; Fatima Batool; Sameera Hassan; Bushra Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

Insights Into the Morphological Analysis, Phytochemical Profile and Antimicrobial Activities of the Multi-Walled Carbon Nanotubes-Induced In Vitro Sugarcane - Aneela Iqbal; Muhammad Usman; Karim Gul; Atta Ullah; Syed Muhammad Shafi Shah; Hazir Rahman; Raham Sher Khan (Sugar Tech, 2024)

Three new species of the genus Candolleomyces (Psathyrellaceae) from Pakistan - Muhammad Haqnawaz; Muhammad Usman; Nadia Fatima; Abdul Rehman Niazi; Abdul Nasir Khalid (Plant Systematics and Evolution, 2024)

Association between the variations in metabolic pathways and oral cancer risk: results from a Pakistani case-control study - Arifa Shabbir; Muhammad Usman Rashid; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Naila Malkani (Molecular Biology Reports, 2024)

Association of polymorphism of NLRP3, ICAM-1, PTPN22, INS genes in childhood onset type 1 diabetes in a Pakistani population - Anjum Jabeen; Samreen Riaz; Muhammad Usman; Asia Parveen; Maryam Mukhtar; Abdul Wajid; Atif Hanif; Andleeb Batool (Molecular Biology Reports, 2024)

Predominance of MGMT promoter methylation among Pakistani glioblastoma patients - Noor Muhammad; Samir Fasih; Bilal Malik; Shahid Hameed; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2024)

Unveiling the sweetness: evaluating yield and quality attributes of early generation sweet corn (Zea mays subsp. sachharata) inbred lines through morphological, biochemical and marker-based approaches - Shah Mohammad Usman; Raheel Shafeeq Khan; Asif Bashir Shikari; Nida Yousuf; Showkat Ahmad Waza; Shabir Hussain Wani; Muhammad Ashraf Bhat; F. Shazia; Faroq Ahmad Sheikh; Asma Majid (Molecular Biology Reports, 2024)

Biological role and regulation of circular RNA as an emerging biomarker and potential therapeutic target for cancer - Ayman Saleem; Muhammad Umer Khan; Tazeen Zahid; Iqra Khurram; Muhammad Usman Ghani; Inam Ullah; Rakhtasha Munir; Daniela Calina; Javad Sharifi-Rad (Molecular Biology Reports, 2024)

Enhancement of Antioxidants’ Enzymatic Activity in the Wheat Crop by Shewanela sp. Mediated Zinc Oxide Nanoparticles Against Heavy Metals Contaminated Wastewater - Irfan Haidri; Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Usman Shafqat; Sadia Mustafa; Faisal Mahmood (Journal of Soil Science and Plant Nutrition, 2024)

Synergistic Application of Bacterial Consortium and Organic Amendments Improves the Growth and Seed Quality of Mash Bean (Vigna Mungo L.) - Kashiuf Asif; Muhammad Shabaan; Waqas Mahmood; Hafiz Naeem Asghar; Zahir Ahmad Zahir; Usman Zulfiqar; Sadam Hussain; Walid Soufan (Journal of Soil Science and Plant Nutrition, 2024)

Plant Biostimulants: Mechanisms and Applications for Enhancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Kanza Asif; Humaira Ashraf; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Rehana Sardar; Fasih Ullah Haider (Journal of Soil Science and Plant Nutrition, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Optimizing the design of a multi-stage tangential roller threshing unit using CFD modeling and experimental studies - Saddam Hussain; Xingpeng Lei; Hongqi Wu; Hao Li; Haiyan Song; Decong Zheng; Wang Jiawei; Anbang Li; Muhammad Usman Farid; Abdul Ghafoor (Computers and Electronics in Agriculture, 2024)

Molecular phenomena associated with the formation of fibrous structure of plant-based meat analogues - Muhammad Ijaz Ahmad; Shahzad Farooq; Usman Ali; Sami Ullah; Chunbao Li; Hui Zhang (Trends in Food Science & Technology, 2024)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Enhanced activation of peroxymonosulfate by nanomagnetic CoFe2O4-CeO2/g-C3N4 composites as a heterogeneous catalyst for metronidazole degradation - Adeel Ahmed; Muhammad Usman; Muhammad Rafiq; Muhammad Adnan; Raza Ullah; Hailin Cong; Bing Yu (Journal of Water Process Engineering, 2024)

Distributed modelling of snow and ice melt in the Naltar Catchment, Upper Indus basin - Muhammad Usman Liaqat; Roberto Ranzi (Journal of Hydrology, 2024)

Erratum to “Improved project control for sustainable development of construction sector to reduce environment risks” [J. Clean. Product. (2019) 118214] - Summaira Malik; Fareena Fatima; Asma Imran; Lai Fatt Chuah; Jirí Jaromír Klemes; Imran Hameed Khaliq; Saira Asif; Muhammad Aslam; Farrukh Jamil; Abdullah Khan Durrani; Majid Majeed Akbar; Muhammad Shahbaz; et al. (Journal of Cleaner Production, 2024)

Effects of geochemical compositional heterogeneities on hydrocarbon expulsion and thermal maturation: An analog study of Maastrichtian source rocks from Jordan - Muhammad Usman; Sebastian Grohmann; Israa S. Abu-Mahfouz; Volker Vahrenkamp; Ralf Littke (International Journal of Coal Geology, 2024)

Syntrophic propionate degradation in anaerobic digestion facilitated by hydrochar: Microbial insights as revealed by genome-centric metatranscriptomics - Zhijian Shi; Chao Zhang; Meichen Sun; Muhammad Usman; Yong Cui; Shicheng Zhang; Bingjie Ni; Gang Luo (Environmental Research, 2024)

Does conflict aggravate energy poverty? - Usman Khalid; Muhammad Shafiullah; Sajid M. Chaudhry (Energy Policy, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Microplastic assessment in remote and high mountain lakes of Gilgit Baltistan, Pakistan - Maryem Mehboob; Rachid Dris; Bruno Tassin; Johnny Gasperi; Muhammad Usman Khan; Riffat N. Malik (Chemosphere, 2024)

Recent progress in electro-Fenton technology for the remediation of pharmaceutical compounds in aqueous environments - Uzma Razzaq; Thanh-Binh Nguyen; Muhammad Usman Saleem; Van-Re Le; Chiu-Wen Chen; Xuan-Thanh Bui; Cheng-Di Dong (Science of The Total Environment, 2024)

Improving flood and drought management in transboundary Upper Jhelum Basin-South Asia - Rubina Ansari; Muhammad Usman Liaqat; Giovanna Grossi (Science of The Total Environment, 2024)

Adsorptive removal of cationic dyes from wastewater using a novel sodium alginate-based iron oxide nanocomposite hydrogel: DFT and advanced statistical physics modelling - Muhammad Umar; Muhammad Usman Farooq; Muhammad Arshad; Muhammad Usama; Feryal Akbal; Sajjad Hussain; Hammad Khan (Process Safety and Environmental Protection, 2024)

Experimental investigation of the wake of tandem cylinders using pivoted flapping mechanism for piezoelectric flag - Muhammad Mahad Shah; Rizwan Mahmood; Usman Latif; Emad Uddin; Adnan Munir; Ming Zhao; Hafiz Hamza Riaz (Ocean Engineering, 2024)

Machine learning modeling and statistical optimization of dye removal from contaminated water using CTAB-functionalized graphene oxide - Sally AlNaimat; Usman M. Ismail; Ahmed I. Ibrahim; Abdimalik Muse; Kashif Faheem; Mohamed Mustafa; Muhammad S. Vohra; Sagheer A. Onaizi (Water, Air, & Soil Pollution, 2024)

Low doses of entomopathogens matter hugely, gateway to resistance development and retarded growth in Helicoverpa armigera - Mirza Abdul Qayyum; Zhuo Zhihang; Waqas Wakil; Habib Ali; Abid Ali; Muhammad Usman Ghazanfar; Muhammad Yasin; Xu Danping; Hasham S. Almoallim; Mohammad Javed Ansari; Muhammad Tahir; Kashif Ali; et al. (Journal of Plant Diseases and Protection, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Green product development (GPD): a systematic literature review and future research directions - Hafiz Muhammad Usman Khizar; Kinaan Khalid; Safeer Haider; Jingbo Yuan (Environment, Development and Sustainability, 2024)

First report of Pythium aphanidermatum causing stem and root rot disease on sesame (Sesamum indicum L.) in Punjab, Pakistan - Nasir Ahmed Rajput; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Owais Iqbal; Muhammad Usman Ali; Muhammad Wahab; Hadeed Ahmad (Journal of Plant Pathology, 2024)

Efficient PFAS removal from contaminated soils through combined washing and adsorption in soil effluents - Muhammad Usman; Aaifa Chaudhary; Khalil Hanna (Journal of Hazardous Materials, 2024)

Modeling homogeneous ignition processes of clustering solid particle clouds in isotropic turbulence - Pooria Farmand; Hendrik Nicolai; Muhammad Usman; Lukas Berger; Antonio Attili; Michael Gauding; Christian Hasse; Heinz Pitsch (Fuel, 2024)

Mitigating cadmium exposure risk in rice with foliar nano-selenium: Investigations through Caco-2 human cell line in-vivo bioavailability assay - Bilal Hussain; Xianyuan Yin; Qiang Lin; Yasir Hamid; Muhammad Usman; Muhammad Laeeq-ur-Rehman Hashmi; Min Lu; Muhammad Imran Taqi; Zhenli He; Xiao e Yang (Environmental Pollution, 2024)

Resilient mechanism of strigolactone (GR24) in regulating morphological and biochemical status of maize under salt stress - Iqra Iftikhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Shamsa Rana; Fozia Farhat; Hira Farooq; Kamran Ahmad; Muhammad Jamil; Fasih Ullah Haider; Saltanat Aghayeva (Biocatalysis and Agricultural Biotechnology, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Nano-Selenium: A Green Promising Approach against Abiotic Stresses in Plants - Mariam Fatima; Asia Maqbool; Rehana Sardar; Muhammad Faisal Maqsood; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Silicon and Zinc Attenuates Drought Tolerance in Eruca sativa L. Through Increasing Chlorophyll Pigments, Osmoprotectants, and Modulating Defense Mechanisms - Iqbal Hussain; Atif Ayub; Airish Nayab; Muhammad Arslan Ashraf; Muhammad Arslan Ashraf; Sadam Hussain; Manzer H. Siddiqui; Muhammad Azeem Sabir; Usman Zulfiqar; Tanveer Hussain Khan (Journal of Plant Growth Regulation, 2024)

Correction: Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Retraction Note: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation - Syed Ahmed Shah; Muhammad Sohail; Muhammad Usman Minhas; Nisar-ur-Rehman; Shahzeb Khan; Zahid Hussain; Mudassir; Arshad Mahmood; Mubeen Kousar; Asif Mahmood (Drug Delivery and Translational Research, 2024)

Determination of volatile organic compounds (VOCs) in indoor work environments by solid phase microextraction-gas chromatography-mass spectrometry - Wadir Mario Valentino Marchesiello; Giuseppina Spadaccino; Muhammad Usman; Donatella Nardiello; Maurizio Quinto (Environmental Science and Pollution Research, 2024)
Volatile organic compounds (VOCs) are continuously emitted into the atmosphere from natural and anthropogenic sources and rapidly spread from the atmosphere to different environments. A large group of VOCs has been included in the class of air pollutants; therefore, their determination and monitoring using reliable and sensitive analytical methods represents a key aspect of health risk assessment. In this work, an untargeted approach is proposed for the evaluation of the exposure to volatile organic compounds of workers in an engine manufacturing plant by GC–MS measurements, coupled with solid-phase microextraction (SPME). The analytical procedure was optimized in terms of SPME fiber, adsorption time, desorption time, and temperature gradient of the chromatographic run. For the microextraction of VOCs, the SPME fibers were exposed to the air in two different zones of the manufacturing factory, i.e., in the mixing painting chamber and the engine painting area. Moreover, the sampling was carried out with the painting system active and running (system on) and with the painting system switched off (system off). Overall, 212 compounds were identified, but only 17 were always present in both zones (mixing painting chamber and engine painting area), regardless of system conditions (on or off). Finally, a semi-quantitative evaluation was performed considering the peak area value of the potentially most toxic compounds by multivariate data analyses.

Functionality of wheat straw-derived biochar enhanced its efficiency for actively capping Cd and Pb in contaminated water and soil matrices: Insights through batch adsorption and flow-through experiments - Yasir Hamid; Yonglong Chen; Qiang Lin; Muhammad Haris; Muhammad Usman; Muhammad Saqib Rashid; Ioannis Anastopoulos; Bilal Hussain; Hayssam M. Ali; Fakhir Hannan; Xianyuan Yin; Xiaoe Yang (Chemosphere, 2024)

Managing antimony pollution: Insights into Soil–Plant system dynamics and remediation Strategies - Fasih Ullah Haider; Usman Zulfiqar; Noor ul Ain; Tariq Mehmood; Umed Ali; Luis Carlos Ramos Aguila; Yuelin Li; Kadambot H.M. Siddique; Muhammad Farooq (Chemosphere, 2024)

A novel integrated approach employing Desertifilum tharense BERC-3 for efficient wastewater valorization and recycling for developing peri-urban algae farming system - Muhammad Usman; Aqib Zafar Khan; Sana Malik; Wenlong Xiong; Yongkun Lv; Shen Zhang; Anqi Zhao; A.E. Solovchenko; Md Asraful Alam; Abdulrahman H. Alessa; Muhammad Aamer Mehmood; Jingliang Xu (Chemosphere, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Fungicide resistance in Colletotrichum fructicola and Colletotrichum siamense causing peach anthracnose in China - Mohammad Mazharul Karim; Hafiz Muhammad Usman; Qin Tan; Jia-Jie Hu; Fei Fan; Rafakat Hussain; Chao-Xi Luo (Pesticide Biochemistry and Physiology, 2024)

Modelling the contribution of green technologies, renewable energy, economic complexity, and human capital in environmental sustainability: Evidence from BRICS countries - Qi Feng; Muhammad Usman; Najia Saqib; Urszula Mentel (Gondwana Research, 2024)

Satellite gravimetry observations on the state of groundwater level variability in the Arabian Peninsula Region and the associated socio-economic sustainability challenges - Muhammad Usman; Kosuke Heki (Groundwater for Sustainable Development, 2024)

Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Molecular identification and characterization of iris yellow spot virus (IYSV) and garlic virus X (GVX) infecting Allium species - Muhammad Usman Shahid; Abid Riaz; Tahira Shafique; Mayasar I. Al-zaban; Diaa Abd El-Moneim; Sheikh Mansoor; Yong Suk Hung; Hyeon-Jin Sun (Plant Biotechnology Reports, 2024)

Retraction Note: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2024)

Microbiome analysis reveals alteration in water microbial communities due to livestock activities - Chang Xu; Sijia Lu; Yangji Cidan; Hongzhuang Wang; Guangming Sun; Muhammad Usman Saleem; Farid Shokry Ataya; Yanbin Zhu; Wangdui-Basang; Kun Li (Environmental Science and Pollution Research, 2024)

Synergistic effect of biochar with gypsum, lime, and farm manure on the growth and tolerance in rice plants under different salt-affected soils - Yousef Alhaj Hamoud; Talha Saleem; Muhammad Zia-ur-Rehman; Hiba Shaghaleh; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Faisal Al-Sarraj; Nadiyah M. Alabdallah (Chemosphere, 2024)

Physicochemical properties and performance of non-woody derived biochars for the sustainable removal of aquatic pollutants: A systematic review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Rashid Iqbal; Faisal Zulfiqar; Akash Tariq; Allah Ditta (Chemosphere, 2024)

Molecular and microbial insights towards anaerobic biodegradation of anionic polyacrylamide in oil sands tailings - Jia Li; Muhammad Usman; Muhammad Arslan; Mohamed Gamal El-Din (Water Research, 2024)

Breaking barriers, cultivating sustainability: Discovering the trifecta influence of digitalization, natural resources, and globalization on eco-innovations across 27 European nations - Muhammad Usman; Mihaela Simionescu; Magdalena Radulescu; Daniel Balsalobre-Lorente (Resources Policy, 2024)

Ameliorative potential of eriocitrin against cadmium instigated hepatotoxicity in rats via regulating Nrf2/keap1 pathway - Muhammad Faisal Hayat; Muhammad Zohaib; Muhammad Umar Ijaz; Moazama Batool; Asma Ashraf; Bader O. Almutairi; Usman Atique (Journal of Trace Elements in Medicine and Biology, 2024)

Corrigendum to “Current challenges of hydrothermal treated wastewater (HTWW) for environmental applications and their perspectives: A review” [Environ. Res. 212 Part D (2022) 113532] - Muhammad Usman; Zhijian Shi; Nalok Dutta; Muhammad Awais Ashraf; Bushra Ishfaq; Mohamed Gamal El-Din (Environmental Research, 2024)

A Comparative Analysis Assessing Growth Dynamics of Locally Isolated Chlorella sorokiniana and Chlorella vulgaris for Biomass and Lipid Production with Biodiesel Potential - Hizbullahi Muhammad Usman; Mohd Farizal Kamaroddin; Mohd Helmi Sani; Nik A.N.N. Malek; Armstrong Ighodalo Omoregie; Afifi Zainal (Bioresource Technology, 2024)

Testing the validity of pollution haven and pollution halo hypotheses in BRICMT countries by Fourier Bootstrap AARDL method and Fourier Bootstrap Toda-Yamamoto causality approach - Oguzhan Ozcelik; Hasan Bardakci; Abdulkadir Barut; Muhammad Usman; Narasingha Das (Air Quality, Atmosphere & Health, 2024)

Prediction and optimization of emissions in cement manufacturing plant under uncertainty by using artificial intelligence-based surrogate modeling - Muhammad Usman; Iftikhar Ahmad; Muhammad Ahsan; Hakan Caliskan (Environment, Development and Sustainability, 2024)

Ecological impacts and potential hazards of nickel on soil microbes, plants, and human health - Muhammad Rizwan; Kamal Usman; Mohammed Alsafran (Chemosphere, 2024)

Cutting-edge developments in MXene-derived functional hybrid nanostructures: A promising frontier for next-generation water purification membranes - Tahir Rasheed; Darim Badur Ferry; Zeenat Fatima Iqbal; Muhammad Imran; Muhammad Usman (Chemosphere, 2024)

Emerging trends to replace pesticides with nanomaterials: Recent experiences and future perspectives for ecofriendly environment - Hong Wang; Muhammad Jafir; Muhammad Irfan; Tanveer Ahmad; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Yousef Alhaj Hamoud; Hiba Shaghaleh (Journal of Environmental Management, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

Geomechanical modeling of CO2 sequestration: A review focused on CO2 injection and monitoring - Sikandar Khan; Yehia Khulief; Ruben Juanes; Salem Bashmal; Muhammad Usman; Abdullatif Al-Shuhail (Journal of Environmental Chemical Engineering, 2024)

Tailored design of CO2-selective mixed-matrix membranes using nitrile-functionalized COFs as 2D nanofillers - Bosirul Hoque; Mohd Yusuf Khan; Aamir Hanif; Mahmoud Abdelnaby; Aasif Helal; Abuzar Khan; Muhammad Usman; Qasem Ahmed Drmosh (Journal of Environmental Chemical Engineering, 2024)

Adsorptive removal of heavy metals from aqueous solutions: Progress of adsorbents development and their effectiveness - Usman M. Ismail; Muhammad S. Vohra; Sagheer A. Onaizi (Environmental Research, 2024)

Insight into the wheat residues-derived adsorbents for the remediation of organic and inorganic aquatic contaminants: A review - Muthanna J. Ahmed; Ioannis Anastopoulos; Dimitrios Kalderis; Muhammad Haris; Muhammad Usman (Environmental Research, 2024)

Engineering ZIF-67 loaded nanofibrous membrane with thermal stabilization treatment for efficient photocatalytic CO2 reduction - Pengfei Lin; Xiwei Qu; Bhaskar Jyoti Deka; Chao Hu; Lei Zhao; Dongyun Wu; Chunhai Yi; Min Wei Boey; Muhammad Usman Farid; Alicia Kyoungjin An; Jiaxin Guo (Chemical Engineering Journal, 2024)

Silicon nanoparticles: A novel approach in plant physiology to combat drought stress in arid environment - Muhammad Nazim; Xiangyi Li; Shazia Anjum; Fiaz Ahmad; Muqarrab Ali; Murad Muhammad; Khurram Shahzad; Lisha Lin; Usman Zulfiqar (Biocatalysis and Agricultural Biotechnology, 2024)

Evolution and Trends of Water Scarcity Indicators: Unveiling Gaps, Challenges, and Collaborative Opportunities - Zafar Hussain; Zongmin Wang; Haibo Yang; Muhammad Arfan; Wusen Wang; Muhammad Faisal; Muhammad Imran Azam; Muhammad Usman (Water Conservation Science and Engineering, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Evaluation of Bacillus spp. as biocontrol agents against chili leaf spot caused by Xanthomonas vesicatoria - Sadia Aziz; Saleem Akhtar Jamshed; Tariq Mukhtar; Gulshan Irshad; Shahzada Sohail Ijaz; Muhammad Usman Raja (Journal of Plant Diseases and Protection, 2024)

First principle study of X2GaAgCl6 (X = Cs, Rb) double perovskites: structural, mechanical, vibrational, electronic, optical, SLME, thermoelectric, and thermodynamic properties for solar cell applications - Zia Ur Rehman; Muhammad Awais Rehman; Muhammad Rashid Khan; Bushra Rehman; Surajudeen Sikiru; Muhammad Rizwan; Mohammed Chafi; Muhammad Usman (Environmental Science and Pollution Research, 2024)

Impact of human capital and natural resources on environmental quality in South Asia - Nazish Tariq; Minhaj Ali; Muhammad Usman (Environment, Development and Sustainability, 2024)
This study examines the importance of human capital and natural resources on environmental quality in South Asia by using panel data that ranges from 1975 to 2021. Advanced cointegration approaches establish the long-term linkages between human capital, natural resources, economic growth, economic growth squared, urban population, industrial value added, and ecological footprint. To explore the long and short-run association among these variables, this study applied the panel autoregressive distributed lags (ARDL) model. The outcome designates that human capital has a negative and significant alliance with environmental quality, whereas economic growth and economic growth square affect environmental quality positively and negatively, confirming the existence of the environmental Kuznets curve (EKC) hypothesis. Urban population growth and natural resources have significant negative associations with environmental pollution, whereas industrial value added increases the pollution levels in South Asia. Lastly, the outcome of the interaction between human capital and natural resource rent on the ecological footprint has a significant positive effect. This study recommends that South Asian nations improve their human capital to promote industrial modernization, expansion of green technology, and energy-efficient habits. Utilizing natural resources also helps South Asian nations maintain a clean ecosystem. Additionally, South Asian nations ought to vigilantly track the negative consequences of industrialization on the atmosphere. Thus, ecological sustainability requires human capital and natural resources.

Exploring nature's filters: Peat-mineral mix for low and high-strength oilfield produced water reclamation - Muhammad Arslan; Muhammad Usman; Mohamed Gamal El-Din (Water Research, 2024)

A systematic review of polycyclic aromatic hydrocarbon pollution: A combined bibliometric and mechanistic analysis of research trend toward an environmentally friendly solution - Olive Mekontchou Yemele; Zhenhua Zhao; Jackson Nkoh Nkoh; Ervice Ymele; Muhammad Usman (Science of The Total Environment, 2024)

Analyzing the asymmetric FinTech services under natural resources, and renewable energy in the future environmental performance: New insights from STIRPAT model framework - Xiaoyang Shu; Muhammad Usman; Paiman Ahmad; Muhammad Irfan (Resources Policy, 2024)

New insights from the STIPART model on how environmental-related technologies, natural resources and the use of the renewable energy influence load capacity factor - Yan Sun; Muhammad Usman; Magdalena Radulescu; Ugur Korkut Pata; Daniel Balsalobre-Lorente (Gondwana Research, 2024)

Efficient oxygen evolution using conductive cobalt-based metal-organic framework - Munzir H. Suliman; Lolwah Tawfiq Alfuhaid; Abuzar Khan; Muhammad Usman; Aasif Helal (Fuel, 2024)

Temperature-dependent transformation of microbial community: A systematic approach to analyzing functional microbes and biogas production - Ali Bahadur; Lu Zhang; Wei Guo; Wasim Sajjad; Nikhat Ilahi; Abhishek Banerjee; Shah Faisal; Muhammad Usman; Tuo Chen; Wei Zhang (Environmental Research, 2024)

Bacteria associated with Comamonadaceae are key arsenite oxidizer associated with Pteris vittata root - Duanyi Huang; Xiaoxu Sun; Muhammad Usman Ghani; Baoqin Li; Jinchan Yang; Zhenyu Chen; Tianle Kong; Enzong Xiao; Huaqing Liu; Qi Wang; Weimin Sun (Environmental Pollution, 2024)

A review of breakthroughs in biodiesel production with transition and non-transition metal-doped CaO nano-catalysts - Rabiah Amal; Muhammad Usman (Biomass and Bioenergy, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

Hydrogen from sewage sludge: Production methods, influencing factors, challenges, and prospects - Usman Khan; Muhammad Bilal; Hossain Md. Adil; Nnabodo Darlington; Ahsan Khan; Nouman Khan; I. Ihsanullah (Science of The Total Environment, 2024)

A fuzzy classification method based on rules learning for shaded and unshaded hotspot faults on photovoltaic modules - Junaid Ali Khan; Shengxue Tang; Borui Ji; Fahad Khan; Muhammad Adeel Khan; Usman Khan Khalil; Irshad Ullah (Journal of Cleaner Production, 2024)

Investigating the quantum size effects of multi-walled carbon nanotubes (MWCNTs) in photocatalytic fermentative biohydrogen production - Hina Ramzan; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Muneeb Ur Rahman; Fuhua Shen; Zhiping Zhang; Reeta Rani Singhania; Farzana Jabeen; Waheed Afzal; Nadeem Tahir (Journal of Cleaner Production, 2024)

Effect of NaClO disinfectant treatment on the yields, components and combustion characteristics of typical medical waste pyrolysis products - Tong Zhang; Aijun Li; Yongda Huang; Su Lei; Muhammad Usman; Yuhang Zheng; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Response of microbial communities to the changes in grazing intensity and season in a typical steppe - Muhammad Usman; Lan Li; Mengyuan Wang; Zhen Wang; An Hu; Liyuan Shi; Fujiang Hou (Environmental Research, 2024)

Technological advancements in water heating approaches for membrane distillation desalination process: From bulk to localized heating - Muhammad Usman Farid; Jehad A. Kharraz; Samriddhi Sharma; Rabia Jalil Khan; Noman Khalid Khanzada; Bhaskar Jyoti Deka; Manoj Kumar Nallapaneni; Shaurhat S. Chopra; Shao-Yuan Leu; Shadi W. Hasan; Nidal Hilal; Alicia K.J. An (Desalination, 2024)

Taxonomy and phylogeny reveal two novel species of genus Lepiota (Agaricaceae, Agaricales) from Punjab, Pakistan - Amatu Rehman; Muhammad Usman; Najam Ul Sehar Afshan; Abdul Nasir Khalid (Plant Systematics and Evolution, 2024)

Biochar: Black Gold for Sustainable Agriculture and Fortification Against Plant Pathogens—A Review - Usman Arshad; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Ali; Muhammad Nadeem Shah; Muhammad Jabran; Muhammad Amjad Ali (Journal of Crop Health, 2024)

A review of the potential involvement of small RNAs in transgenerational abiotic stress memory in plants - Muhammad Daniyal Junaid; Usman Khalid Chaudhry; Beyazıt Abdurrahman Şanlı; Ali Fuat Gökçe; Zahide Neslihan Öztürk (Functional & Integrative Genomics, 2024)

Genetic biofortification: advancing crop nutrition to tackle hidden hunger - Usman Zulfiqar; Amman Khokhar; Muhammad Faisal Maqsood; Muhammad Shahbaz; Nargis Naz; Maheen Sara; Sana Maqsood; Sajila Sahar; Saddam Hussain; Muhammad Ahmad (Functional & Integrative Genomics, 2024)

Self-assembled micelles loaded with itraconazole as anti-Acanthamoeba nano-formulation - Komal Rao; Muhammad Abdullah; Usman Ahmed; Hashi Isse Wehelie; Muhammad Raza Shah; Ruqaiyyah Siddiqui; Naveed A. Khan; Bader S. Alawfi; Ayaz Anwar (Archives of Microbiology, 2024)

Retraction Note: The role of monetary and fiscal policies in determining environmental pollution: Revisiting the N-shaped EKC hypothesis for China - Tang Zhengxia; Mohammad Haseeb; Muhammad Usman; Mohd Shuaib; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2024)

Retraction Note: The shadow economy in South Asia: dynamic effects on clean energy consumption and environmental pollution - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman; Zubaria Andlib (Environmental Science and Pollution Research, 2024)

Linking energy-based circularity with environment in high-income economies - Muhammad Usman; Syed Asif Ali Naqvi; Sofia Anwar; Abdul Majeed Nadeem (Environmental Science and Pollution Research, 2024)

Multi-objective calibration and uncertainty analysis for the event-based modelling of flash floods - Muhammad Nabeel Usman; Jorge Leandro; Karl Broich; Markus Disse (Hydrological Sciences Journal, 2024)

Temperature drives microbial communities in anaerobic digestion during biogas production from food waste - Tuo Chen; Lu Zhang; Wei Guo; Wei Zhang; Wasim Sajjad; Nikhat Ilahi; Muhammad Usman; Shah Faisal; Ali Bahadur (Environmental Science and Pollution Research, 2024)

Promoting the suitability of graphitic carbon nitride and metal oxide nanoparticles: A review of sulfonamides photocatalytic degradation - Zakariyya Uba Zango; Muhammad Abubakar Lawal; Fahad Usman; Abdelmoneim Sulieman; Hanan Akhdar; M.H. Eisa; Osamah Aldaghri; Khalid Hassan Ibnaouf; Jun Wei Lim; Kuan Shiong Khoo; Yoke Wang Cheng (Chemosphere, 2024)

Depositional and diagenetic controls on reservoir properties of the lower Cambrian Khewra Sandstone, eastern salt range, Sub-Himalaya, Pakistan - Shoukat Husain Khan; Ying-Ming Sheng; Salvatore Critelli; Massimo Civitelli; Muhammad Saleem Mughal; Usman Basharat (Marine and Petroleum Geology, 2024)

Sustainable porous graphene/Co-MOF for the removal of water pollutants: Combined theoretical and experimental studies - Zahira Bano; Muhammad Akram; Naveed Zafar Ali; Muhammad Usman Khan; Fengyun Wang; Linrui Li; Mingzhu Xia (Journal of Water Process Engineering, 2024)

Optimization of multi-stage micellar-enhanced flocculation process for removal of Levofloxacin hemihydrate in wastewater - Fiza Bukhtawar; Muhammad Usman; Atta Ul Haq; Muhammad Saeed; Atif Saleem (Journal of Water Process Engineering, 2024)

Substation of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2024)

Simultaneous solar steam and electricity generation from biochar based photothermal membranes - Abdul Ghaffar; Muhammad Usman; Munir Ullah Khan; Muhammad Hassan (Journal of Cleaner Production, 2024)

Provenance history, depositional conditions andtectonic settings during late Cenomanian – early Turonian time in the Gongola Sub-Basin of the Upper Benue Trough Nigeria: Evidence from major and trace elements geochemistry of the Kanawa shales from the Pindiga Formation - Usman Abubakar; Simon V. Hohl; Musa Bappah Usman; Abubakar S. Maigari; Milan Stafford Tchouatcha; Raymond Peter Tabale; Abdulwahab Muhammad Bello; Auwalu Dalha; Shehu Mukkafa (Journal of African Earth Sciences, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Dual layer hollow fiber photocatalytic membrane based on TiO2-WO3@GO composite with catalytic memory and enhanced anti-fouling and self-cleaning properties for oilfield-produced water treatment - Ojo Samuel; Asmat Ullah Khan; Roziana Kamaludin; Mohd Hafiz Dzarfan Othman; Tonni Agustiono Kurniawan; Aniqa Imtiaz; Mohammed Faleh Al-Ogaili; Jamilu Usman; Mustapha Salisu Muhammad; Bello Abdulkareem; Obinna Emmanuel Ezenkwa; Mohd Hafiz Puteh; et al. (Chemical Engineering Journal, 2024)

Retraction Note: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2024)

Advanced network pharmacology and molecular docking-based mechanism study to explore the multi-target pharmacological mechanism of Cymbopogon citratus against Alzheimer's disease - Kinza Fatima; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Asif; Asma Haque; Muhammad Qasim; Mubarak A. Alamri; Ziyad Tariq Muhseen; Fatima Noor; Muhammad Sadaqat (South African Journal of Botany, 2024)

Assessing the effectiveness of 3, 4-dimethylpyrazole phosphate (DMPP) inhibitor in mitigating N2O emissions from contrasting Cd-contaminated soils - Muhammad Laeeq Ur Rehman Hashmi; Yasir Hamid; Muhammad Usman; Jipeng Luo; Sangar Khan; Tang Sheng; Nabila Bano; TalhaTufail Bhatti; Tingqiang Li (Science of The Total Environment, 2024)

Does environmental policy stringency reduce trade in energy resources? Insights from coal, petroleum, and gas - Ahmed Usman; Sana Ullah; Ilhan Ozturk; Sidra Sohail; Muhammad Tayyab Sohail (Resources Policy, 2024)

Woody biomass derived nano lignin-enabled membrane with high structural stability for efficient wastewater treatment - Rabia Jalil Khan; Chun Yin Lau; Muhammad Usman Farid; Md Khairul Islam; Alicia Kyoungjin An; Jiang Yi; Shao-Yuan Leu (Process Safety and Environmental Protection, 2024)

Electro-sorption and -desorption characteristics of electrically conductive polyacrylonitrile membranes to remove aqueous natural organic matter in dead-end ultrafiltration system - Muhammad Usman; Sarah Glass; Tomi Mantel; Volkan Filiz; Mathias Ernst (Journal of Water Process Engineering, 2024)

Simultaneous biodegradation of Teflaro contained wastewater and electricity generation in an air–cathode microbial fuel cell - Peng Cheng; Yingchuan Zhang; Xinlan Ying; Hongli Ma; Yanlei Zhang; Meiru Liu; Muhammad Usman; Xiangping Tan; Liqun Jiang (Fuel, 2024)

Modified carbon paste electrode with choline proline in enhancing the performance of water electrolysis system for hydrogen production - Muhammad Usman; Fakrul Shahril Ezanie Zulkefli; Mohd Dzul Hakim Wirzal; Shafiq M. Hizam; Aliya Nurzafira Nor Zaidi; Muhammad Syaamil Saad (Fuel, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Sustainable humidity control in the built environment: Recent research and technological advancements in thermal driven dehumidification systems - Muhammad Usman Saeed Akhtar; Sulaiman O. Fadlallah; Muhammad Imran Khan; Faisal Asfand; Sami G. Al-Ghamdi; Rakesh Mishra (Energy and Buildings, 2024)

Climatic influence on sediment distribution and transport in the Thar Desert (Sindh and Cholistan, Pakistan) - Muhammad Usman; Peter D. Clift; Guido Pastore; Giovanni Vezzoli; Sergio Andò; Marta Barbarano; Pieter Vermeesch; Eduardo Garzanti (Earth-Science Reviews, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Efficacy of Green Synthesized Silver Based Nanomaterials Against Early Blight of Tomato Caused by Alternaria solani - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Shahbaz Talib Sahi; Mohsin Shad; Nian Lili; Shahid Iqbal; Asif Mahmood Arif; Usama Ahmad; Khurram Shehzad Khan; Muhammad Asif; Fasih Ullah Haider (Journal of Crop Health, 2024)

Analyzing employees’ green behavioral intention in the hospitality industry: a multilevel model - Bilal Khalid; Khurram Shahzad; Muhammad Usman Anwar Baig (Environment, Development and Sustainability, 2024)

The right information for the right career selection: can it assist Japan to achieve agricultural sustainability? - Muhammad Usman; Jeffry Joseph Gayman; Akinori Sawaya; Kenichi Horiguchi; Mari Igarashi; Abdul Malik (Environment, Development and Sustainability, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Corrigendum to “Effect of exogenous application of biogenic silicon sources on growth, yield, and ionic homeostasis of maize (Zea mays L.) crops cultivated in alkaline soil” [Chemosphere 341, November (2023) 140019] - Arwa Abdulkreem AL-Huqail; Ali Rizwan; Muhammad Zia-ur-Rehman; Haifa Abdulaziz Sakit Al-Haithloul; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Naveeda Majid; Yousef Alhaj Hamoud; Muhammad Rizwan; Amany H.A. Abeed (Chemosphere, 2024)

Towards the vision of going green in South Asian region: The role of technological innovations, renewable energy and natural resources in ecological footprint during globalization mode - Lingli Qing; Muhammad Usman; Magdalena Radulescu; Mohammad Haseeb (Resources Policy, 2024)

How can natural resource dependence, environmental-related technologies and digital trade protect the environment: Redesigning SDGs policies for sustainable environment? - Muhammad Zubair Ashraf; Wei Wei; Muhammad Usman; Shahid Mushtaq (Resources Policy, 2024)

Amentoflavone mediated hepatoprotection to counteract paraquat instigated hepatotoxicity via modulating Nrf2/keap1 pathway: A biochemical, inflammatory, apoptotic and histopathological study - Muhammad Umar Ijaz; Naila Ghafoor; Muhammad Faisal Hayat; Bader O. Almutairi; Usman Atique (Pesticide Biochemistry and Physiology, 2024)

Use of iron-bearing waste materials in laundry wastewater treatment - Yara Arbid; Muhammad Usman; N. Tan Luong; Baptiste Mathon; Bruno Cedat; Jean-François Boily; Khalil Hanna (Journal of Water Process Engineering, 2024)

Determination of microplastic pollution in marine ecosystems and its effective removal using an advanced nanobubble flotation technique - Jehad A. Kharraz; Mingyi Jia; Muhammad Usman Farid; Noman Khalid Khanzada; Nidal Hilal; Shadi W. Hasan; Alicia Kyoungjin An (Journal of Water Process Engineering, 2024)

Corporate social responsibility in the United Arab Emirates and globally: A cross-national comparison - Dima Rachid Jamali; Ifzal Ahmad; Mohamed Aboelmaged; Muhammad Usman (Journal of Cleaner Production, 2024)

New insights into the environmental application of hybrid nanoparticles in metal contaminated agroecosystem: A review - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Muhammad Usman (Journal of Environmental Management, 2024)

Role of nuclear energy, geothermal energy, agriculture, and urbanization in environmental stewardship - Muhammad Ramzan; Ummara Razi; Muhammad Usman; Suleman Sarwar; Amogh Talan; Hardeep Singh Mundi (Gondwana Research, 2024)

Influence of germination and pulse type on texture of high moisture meat analogs - Jun Guo; Muhammad Usman; Gabriel Swanson; Baochen Fang; Jiajia Rao; Bingcan Chen; Minwei Xu (Food Hydrocolloids, 2024)

Harnessing the synergistic impacts of environmental innovations, financial development, green growth, and ecological footprint through the lens of SDGs policies for countries exhibiting high ecological footprints - Najia Saqib; Muhammad Usman; Ilhan Ozturk; Arshian Sharif (Energy Policy, 2024)

Emerging role of lipophagy in liver disorders - Bismillah Nazeer; Muhammad Babar Khawar; Muhammad Usman Khalid; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Ahmad Ali; Hooriya Fatima; Sadia Ahmad (Molecular and Cellular Biochemistry, 2024)

Detection of high-risk human papillomavirus infected cervical biopsies samples by immunohistochemical expression of the p16 tumor marker - Muhammad Shafique; Iqra Shoaib; Bilal Aslam; Rabia Khalid; Imrana Tanvir; Muhammad Hidayat Rasool; Tawaf Ali Shah; Khalid S. Almaary; Mohammed Bourhia; Muhammad Usman Qamar (Archives of Microbiology, 2024)

Spatiotemporal variability of precipitation concentration in Pakistan - Muhammad Zaman; Muhammad Adnan Shahid; Ijaz Ahmad; Yan‐Jun Shen; Muhammad Usman; Muhammad Imran Khan; Muhammad Saifullah (International Journal of Climatology, 2023)
Precipitation is a meteorological variable that plays a vital role in determining water resources and managing water risks. The intensity and frequency of precipitation extremes have increased in recent years; however, the changes in precipitation regimes across Pakistan remain unclear. This study analysed spatial and temporal changes in the precipitation concentration index (PCI) and concentration index (CI) from 100 meteorological stations across Pakistan from 1981 to 2017. Using innovative trend analysis (ITA) and Pettitt's test, we detected trends and change points in the annual and wet season PCI and CI. Additionally, we examined the relationship between PCI/CI values and latitude and altitude. The results revealed that the CI and PCI ranged between 0.48–0.78 and 10–55, respectively, with higher values being more prevalent in the dry and hot zones of the country. The study established a linear relationship between PCI/CI values, latitude and altitude, with higher values at lower altitudes and a decrease in values from south to north. Most stations presented a significant positive ITA trend for PCI and CI from 1981 to 2017, with a change between 1985 and 1995, indicating an overall increase in heavy precipitation events in the area. These findings are crucial for disaster preparedness, water resource planning, the mitigation of drought and flood risks, and conservation efforts.

How ESG reporting is effected by sustainable finance and green innovation: moderating role of sales growth - Fawad Rauf; Wang Wanqiu; Khwaja Naveed; Syed Usman Qadri; Muhammad Sibt e Ali (Environmental Science and Pollution Research, 2023)

Impact of transportation infrastructure and urbanization on environmental pollution: evidence from novel wavelet quantile correlation approach - Muhammad Usman Malik; Zia ur Rehman; Arshian Sharif; Ahsan Anwar (Environmental Science and Pollution Research, 2023)

Effect of multiwalled carbon nanotubes on compressive behavior of concrete at elevated temperature for mass concreting - Kashan Nisar; Muhammad Shahid Siddique; Muhammad Rizwan; Syed Hassan Farooq; Muhammad Usman; Asad Hanif (European Journal of Environmental and Civil Engineering, 2023)

Enhanced lead phytoextraction and soil health restoration through exogenous supply of organic ligands: Geochemical modeling” - Maria Manzoor; Muhammad Shafiq; Iram Gul; Usman Rauf Kamboh; Dong-Xing Guan; Abdulrahman Ali Alazba; Sven Tomforde; Muhammad Arshad (Journal of Environmental Management, 2023)

Efficient heterogeneous activation of peroxymonosulfate by manganese-doped LaCoO3 perovskites for metronidazole degradation: A mechanistic study and reaction pathways - Muhammad Rafiq; Adeel Ahmed; Muhammad Usman; Raza Ullah; Fengyuan Gao; Muhammad Mateen; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Sustainable production of glutamic acid by Enterobacter sp. strain isolated from cheese for potential protein biosynthesis: Optimization by Response Surface Methodology - Hamza Magaji; Shehu Muhammad Auwal; Rufa'i Nasir; Abdulrahman Itopa Suleiman; Shehu Usman; Ahmad Hussaini Jagaba (Bioresource Technology Reports, 2023)

Effective Bioremediation of Cd, Cr, and Pb in Tannery Effluent Using Aspergillus fumigatus and Aspergillus terreus: Synergistic Effects of Using the Two Strains Together - Usman U. Zango; I. I. Muhammad; Varruchi Sharma; Anil K. Sharma (Water, Air, & Soil Pollution, 2023)

Combined Coagulation-Electrocoagulation Treatment of Urban, Peri-urban, and Textile Wastewaters: Process Evaluation and Sludge Setting Characteristics - Suleman Arshad; Waqar Ali Khan; Muhammad Tahir Ishfaq; Muhammad Usman (Water Conservation Science and Engineering, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Changes in Nitrogen-Related Performance Attributes of Winter Wheat Varieties Released Between 1950 and 2020 in Dryland Region of China - Ma Lijuan; Muhammad Fraz Ali; Huang Xiaohu; Peng Zili; Usman Zulfiqar; Wang Rui (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Cowpea landraces in northern Nigeria: overview of seedling drought tolerance - Solihu Kayode Sakariyahu; Sadam Sulaiman Indabo; Aminu Aliyu; Hadiza Usman Muhammad; Hauwa Oziohu Ahmed; Saba Baba Mohammed; Abu Kasim Adamu; Ramatu Enehezeyi Aliyu (Biologia, 2023)

Exploring the impact of public funds and eco-friendly innovations on reducing carbon pollution in North Africa - Ayoub Zeraibi; Magdalena Radulescu; Khurram Shehzad; Muhammad Kamran Khan; Muhammad Usman (Environmental Science and Pollution Research, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Inquiring the impact of rural–urban migration, construction sector, and agriculture irrigated land on environmental degradation: insights from urbanized Asian countries - Feng Guoru; Muhammad Haris Hanif; Usman Saleem Yousaf (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Catalysts for sustainable energy transitions: the interplay between financial development, green technological innovations, and environmental taxes in European nations - Nudrat Fatima; Mahjabeen Usman; Nasir Khan; Muhammad Shahbaz (Environment, Development and Sustainability, 2023)

Effect of exogenous application of biogenic silicon sources on growth, yield, and ionic homeostasis of maize (Zea mays L.) crops cultivated in alkaline soil - Arwa Abdulkreem AL-Huqail; Ali Rizwan; Muhammad Zia-ur-Rehman; Haifa Abdulaziz Sakit Al-Haithloul; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Naveeda Majid; Yousef Alhaj Hamoud; Muhammad Rizwan; AmanyH.A. Abeed (Chemosphere, 2023)

Synergistic effect of β-sitosterol and biochar application for improving plant growth of Thymus vulgaris under heat stress - Khadiga Alharbi; Amir Abdullah Khan; Haifa Abdulaziz Sakit Alhaithloul; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Saeedah Sallum Aloufi; Awatif M. Abdulmajeed; Muhammad Atif Muneer; Suliman M.S. Alghanem; Muhammad Zia-ur-Rehman; Muhammad Usman; Mona H. Soliman (Chemosphere, 2023)

Effects of zinc-enriched amino acids on rice plants (Oryza sativa L.) for adaptation in saline-sodic soil conditions: Growth, nutrient uptake and biofortification of zinc - Saqib Raza; Muhammad Zia-ur-Rehman; Sameera A. Alghamdi; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Rubaz Ahmed; Aisha Abdul Waris; Muhammad Rizwan; Amany H.A. Abeed; Haifa Abdulaziz Sakit Al-Haithloul (South African Journal of Botany, 2023)

Mapping potentially groundwater-dependent vegetation in the Mediterranean biome using global geodata targeting site conditions and vegetation characteristics - Léonard El-Hokayem; Pantaleone De Vita; Muhammad Usman; Andreas Link; Christopher Conrad (Science of The Total Environment, 2023)

Socio- and techno-economic analyses of biodiesel production from sewage sludge in Tokyo, Japan - Muhammad Usman; Shuo Cheng; Sasipa Boonyubol; Muhammad Aziz; Jeffrey S. Cross (Journal of Cleaner Production, 2023)

Sensory profile of pulse-based high moisture meat analogs: A study on the complex effect of germination and extrusion processing - Muhammad Usman; Gabriel Swanson; Bingcan Chen; Minwei Xu (Food Chemistry, 2023)

Retention and transport of PFOA and its fluorinated substitute, GenX, through water-saturated soil columns - Guanhong Liu; Muhammad Usman; Tao Luo; Pierre-François Biard; Kuangfei Lin; H. Chris Greenwell; Khalil Hanna (Environmental Pollution, 2023)

Environmental implications of phosphate-based fertilizer industrial waste and its management practices - Noman Ahmad; Muhammad Usman; Hamaad Raza Ahmad; Muhammad Sabir; Zia Ur Rahman Farooqi; Muhammad Tahir Shehzad (Environmental Monitoring and Assessment, 2023)

Environmental cost of natural resources, globalization, and economic policy uncertainty in the G-7 bloc: do human capital and renewable energy matter? - Awais Dastgeer; Maria Shabir; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Analyzing asymmetric ecological performance under structural change, technological innovation, and trade diversification: fresh insights from the USA - Md Minhazul Islam; Paiman Ahmad; Maria Shabir; Muhammad Usman; Mustafa Kamal (Environmental Science and Pollution Research, 2023)

Microbe-oriented nanoparticles as phytomedicines for plant health management: An emerging paradigm to achieve global food security - Muhammad Noman; Temoor Ahmed; Usman Ijaz; Amir Hameed; Muhammad Shahid; Azizullah; Dayong Li; Fengming Song (Critical Reviews in Food Science and Nutrition, 2023)

Reverse osmosis membrane functionalized with aminated graphene oxide and polydopamine nanospheres plugging for enhanced NDMA rejection and anti-fouling performance - Noman Khalid Khanzada; Shazia Rehman; Jehad A. Kharraz; Muhammad Usman Farid; Muzamil Khatri; Nidal Hilal; Alicia Kyoungjin An (Chemosphere, 2023)

Multiple design and modelling approaches for the optimisation of carbon felt electro-Fenton treatment of dye laden wastewater - Hammad Khan; Sajjad Hussain; Muhammad Amad Ud Din; Muhammad Arshad; Fazal Wahab; Usman Hassan; Abad Khan (Chemosphere, 2023)

Nanobubbles in water and wastewater treatment systems: Small bubbles making big difference - Mingyi Jia; Muhammad Usman Farid; Jehad A. Kharraz; Nallapaneni Manoj Kumar; Shauhrat S. Chopra; Am Jang; John Chew; Samir Kumar Khanal; Guanghao Chen; Alicia Kyoungjin An (Water Research, 2023)

Cotton and drought stress: An updated overview for improving stress tolerance - Sadia Zafar; Hadiqa Afzal; Areeba Ijaz; Athar Mahmood; Atif Ayub; Airish Nayab; Sadam Hussain; Maqsood UL-Hussan; Muhammad Azeem Sabir; Usman Zulfiqar; Faisal Zulfiqar; Anam Moosa (South African Journal of Botany, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Testing the resources curse hypothesis: Unleashing the role of national governance and financial development in OPEC countries - Kaiyuan Hou; Rabia Qammar; Conghao Zhu; Muhammad Usman; Shujaat Abbas (Resources Policy, 2023)

Implications for optimal abatement path through the deployment of natural resources, human development, and energy consumption in the era of digitalization - Atif Jahanger; Muhammad Usman; Rakhshanda Kousar; Daniel Balsalobre-Lorente (Resources Policy, 2023)

Novel thiol-grafted composite of chitosan and rice straw biochar (TH@CT-BC): A two-step fabrication for highly selective adsorption of cadmium from contaminated water - Yasir Hamid; Lei Liu; Muhammad Haris; Muhammad Usman; Qiang Lin; Yonglong Chen; Muhammad Saqib Rashid; Zaid Ulhassan; M. Iftikhar Hussain; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2023)

Reduced graphene oxide supported CoFe2O4 composites with enhanced peroxymonosulfate activation for the removal of sulfamethoxazole: Collaboration of radical and non-radical pathways - Adeel Ahmed; Muhammad Usman; Zhijian Ji; Muhammad Rafiq; Raza Ullah; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Evaluating the determinants of wildlife tolerance in the Kavango-Zambezi Transfrontier Conservation Area in Zimbabwe - Muhammad Faizan Usman; Sebastien Le Bel; Patrice Grimaud; Martin Reinhardt Nielsen (Journal for Nature Conservation, 2023)

Hydrocracking of surgical face masks over Y Zeolites: Catalyst development, process design and life cycle assessment - Muhammad Usman Azam; Auguste Fernandes; Inês Graça; Waheed Afzal (Fuel, 2023)

Depolymerization of lignin: Recent progress towards value-added chemicals and biohydrogen production - Hina Ramzan; Muhammad Usman; Faiqa Nadeem; Muhammad Shahzaib; Muneeb Ur Rahman; Reeta Rani Singhania; Farzana Jabeen; Anil Kumar Patel; Chunyao Qing; Shengyong Liu; Grzegorz Piechota; Nadeem Tahir (Bioresource Technology, 2023)

Triggering photo fermentative biohydrogen production through NiFe2O4 photo nanocatalysts with various excitation sources - Shengyong Liu; Fuhua Shen; Faiqa Nadeem; Muneeb Ur Rahman; Muhammad Usman; Hina Ramzan; Muhammad Shahzaib; Reeta Rani Singhania; Wang Yi; Chunyao Qing; Nadeem Tahir (Bioresource Technology, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Enhancement of photocatalytic activity of Ba-doped CoO for degradation of Emamectin benzoate in aqueous solution - Huma Khalid; Atta ul Haq; Syed Ali Raza Naqvi; Muhammad Usman; Tanveer Hussain Bokhari (Environmental Monitoring and Assessment, 2023)

Split injection strategy control map development through prediction-based calibration approach to improve the biodiesel-fuelled diesel engine characteristics - Ashok Bragadeshwaran; Vignesh Rajasekar; Kaisan Muhammad Usman; Tamilvanan Ayyasamy; Kumaresan Govindasamy (Environmental Science and Pollution Research, 2023)

Urbanization, rural energy-poverty, and carbon emission: unveiling the pollution halo effect in 48 BRI countries - Qi Xu; Salim Khan; Xiaojuan Zhang; Muhammad Usman (Environmental Science and Pollution Research, 2023)

Gum-based nanocomposites for the removal of metals and dyes from waste water - Muhammad Usman; Muhammad Babar Taj; Sónia Alexandra Correia Carabineiro (Environmental Science and Pollution Research, 2023)
The importance of water for all living organisms is unquestionable and protecting its sources is crucial. In order to reduce water contaminants, like toxic metals and organic dyes, researchers are exploring different techniques, such as adsorption, photocatalytic degradation, and electrolysis. Novel materials are also being sought. In particular, biopolymers like guar gum and xanthan gum, that are eco-friendly, non-toxic, reusable, abundant and cost-effective, have enormous potential. Gum-based nanocomposites can be prepared and used for removing heavy metals and colored dyes by adsorption and degradation, respectively. This review explains the significance of gum-based nanomaterials in waste water treatment, including preparative steps, characterization techniques, kinetics models, and the degradation and adsorption mechanisms involved.

Correction to: Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Evaluating the necessity of post-processing techniques on d4PDF data for extreme climate assessment - Luksanaree Maneechot; Yong Jie Wong; Sophal Try; Yoshihisa Shimizu; Khagendra Pralhad Bharambe; Patinya Hanittinan; Teerawat Ram-Indra; Muhammad Usman (Environmental Science and Pollution Research, 2023)

Combination of melatonin and plant growth promoting rhizobacteria improved the growth of Spinacia oleracea L. under the arsenic and cadmium stresses - Mahnoor Asif; Rafiq Ahmad; Arshid Pervez; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Shahzad; Usman Irshad; Arshad Mehmood Abbasi (Physiological and Molecular Plant Pathology, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Effect of iron nanoparticles and conventional sources of Fe on growth, physiology and nutrient accumulation in wheat plants grown on normal and salt-affected soils - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Sidra Anayatullah; Muhammad Rizwan; Hesham F. Alharby; Isam M. Abu Zeid; Nadiyah M. Alabdallah; Shafaqat Ali (Journal of Hazardous Materials, 2023)

Environmental impact assessment of the manufacturing of glass packaging solutions: Comparative scenarios in a developing country - Muhammad Usman Ali Khan; Shamraiz Ahmad; Shahid Ikramullah Butt (Environmental Impact Assessment Review, 2023)

Spatiotemporal pore-water pressure prediction using multi-input long short-term memory - Charles Wang Wai Ng; Muhammad Usman; Haowen Guo (Engineering Geology, 2023)

Transforming Bombax ceiba L. sawdust waste into a valuable growth substrate: An example with sugarcane - Muhammad Yasin; Muhammad Usman Zia; Athar Mahmood; Muhammad Mansoor Javaid; Muhammad Ather Nadeem; Christian Andreasen (Bioresource Technology Reports, 2023)

An Application of Rock Phosphate Increased Soil Cadmium Contamination and Hampered the Morphophysiological Growth of Brassica campestris L - Muhammad Usman Khadim; Ghulam Murtaza; Zia Ur Rahman Farooqi; Tajammal Hussain; Naeem Mahmood; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Soil Erosion Estimation of Mohmand Dam Watershed Using Geo-spatial Techniques in KPK, Pakistan - Muhammad Imran; Muhammad Sanaullah; Usman Ahmad; Luqman Ahmed (Geotechnical and Geological Engineering, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Dynamic linkages between globalization, human capital, and carbon dioxide emissions: empirical evidence from developing economies - Atif Jahanger; Bo Yang; Wei-Chiao Huang; Muntasir Murshed; Muhammad Usman; Magdalena Radulescu (Environment, Development and Sustainability, 2023)

Comparative cyto-genotoxicity and clastogenicity properties of traditional trypanocidal Afrormosia laxiflora and Lonchocarpus laxiflorus plants in Wistar rats - Lovina Chinyere Ogbu; Aliyu Muhammad; Mohammed Aliyu Usman; Musa Bashir; Abdullahi Balarabe Sallau (Toxicology and Environmental Health Sciences, 2023)

Fracture mechanics analysis of a closure head of a PWR reactor pressure vessel the effect of bolt pre-load and thermal stresses - Muhammad Naweed; Usman Tariq Murtaza; Waseem Siddique (Annals of Nuclear Energy, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Asymmetric role of natural resources dependence, industrialization, and foreign direct investment in China’s economic growth - Yongming Huang; Syed Muhammad Faraz Raza; Muhammad Usman (Resources Policy, 2023)

Socially responsible human resources management and employee retention: The roles of shared value, relationship satisfaction, and servant leadership - Nhat Tan Pham; Tran Hoang Tuan; Tri Dinh Le; Phuong Ngoc Duy Nguyen; Muhammad Usman; Gleriani Torres Carbone Ferreira (Journal of Cleaner Production, 2023)

Hydrogen, carbon dioxide, and methane adsorption potential on Jordanian organic-rich source rocks: Implications for underground H2 storage and retrieval - Amer Alanazi; Hussein Rasool Abid; Muhammad Usman; Muhammad Ali; Alireza Keshavarz; Volker Vahrenkamp; Stefan Iglauer; Hussein Hoteit (Fuel, 2023)

An overview on human exposure, toxicity, solid-phase microextraction and adsorptive removal of perfluoroalkyl carboxylic acids (PFCAs) from water matrices - Zakariyya Uba Zango; Baranitharan Ethiraj; Fahad S. Al-Mubaddel; Mohammad Mahtab Alam; Muhammad Abubakar Lawal; Haliru Aivada Kadir; Kuan Shiong Khoo; Zaharaddeen Nasiru Garba; Fahad Usman; Muttaqa Uba Zango; Jun Wei Lim (Environmental Research, 2023)

Microbial insights towards understanding the role of hydrochar in enhancing phenol degradation in anaerobic digestion - Muhammad Usman; Zhijian Shi; Yafan Cai; Shicheng Zhang; Gang Luo (Environmental Pollution, 2023)

Different microplastics in anaerobic paddy soils: Altering methane emissions by influencing organic matter composition and microbial metabolic pathways - Mengyuan Ji; Lurui Xiao; Muhammad Usman; Chao Liu; Wenjing Sang; Laura Treu; Stefano Campanaro; Gang Luo; Yalei Zhang (Chemical Engineering Journal, 2023)

Advances in the catalyzed photo-fermentative biohydrogen production through photo nanocatalysts with the potential of selectivity, and customization - Faiqa Nadeem; Huan Zhang; Nadeem Tahir; Zhiping Zhang; Reeta Rani Singhania; Muhammad Shahzaib; Hina Ramzan; Muhammad Usman; Muneeb Ur Rahman; Quanguo Zhang (Bioresource Technology, 2023)

Role of pretreatment type and microbial mechanisms on enhancing volatile fatty acids production during anaerobic fermentation of refinery waste activated sludge - Qinghong Wang; Wenzhuo Xin; Zhiguo Shao; Muhammad Usman; Jin Li; Pengyin Shang; Yue Kou; Mohamed Gamal El-Din; Chunmao Chen (Bioresource Technology, 2023)

Effects of Saccharomyces cerevisiae live cells and culture on growth and productive performance in lactating Nili-Ravi buffaloes - Mohsin Ali; Saeed Ahmed; Mubashar Ali; Nisar Ahmad; Mohammad Noman Tariq; Muhammad Usman; Ahmad Azeem Sardar (Tropical Animal Health and Production, 2023)

Selection and downscaling of CMIP6 climate models in Northern Nigeria - Idris Muhammad Wada; Haruna Shehu Usman; Amechi S. Nwankwegu; Makhai Nwunuji Usman; Selamawit Haftu Gebresellase (Theoretical and Applied Climatology, 2023)

Holistic expression of miR-17-92 cluster in obesity, kidney diseases, cardiovascular diseases, and diabetes - Maheen Ejaz; Syed Mohammad Usman; Saira Amir; Muhammad Jawad Khan (Molecular Biology Reports, 2023)

Efficacy of γ-Aminobutyric Acid (GABA) on Physio-biochemical Attributes of Lettuce (Lactuca sativa L.) Under Cadmium Toxicity - Zainab Waris; Zahra Noreen; Anis Ali Shah; Sheeraz Usman; Adnan Noor Shah; Muhammad Rizwan; Ryan Casini; Hosam O. Elansary (Journal of Plant Growth Regulation, 2023)

Clinicopathological profile of peritoneal tuberculosis and a new scoring model for predicting mortality: an international ID-IRI study - Alpaslan Tanoglu; Hakan Erdem; Jon S. Friedland; Handan Ankaralı; Jose Fernando Garcia-Goez; Ayse Albayrak; Amani El-Kholy; Sevil Alkan Ceviker; Fatma Amer; Serpil Erol; Ilad Alavi Darazam; Mohammad Mahdi Rabiei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Groundwater quality risk assessment using hydro-chemical and geospatial analysis - Hafiz Umar Farid; Hafiz Usman Ayub; Zahid Mahmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Rana Muhammad Asif Kanwar; Muhammad Mubeen; Pervaiz Sakinder (Environment, Development and Sustainability, 2023)

Elucidating Heavy Metals Concentration and Distribution in Wild Edible Morels and the Associated Soil at Different Altitudinal Zones of Pakistan: a Health Risk Implications Study - Hussain Badshah; Muhammad Usman Khan; Abdul Samad Mumtaz (Biological Trace Element Research, 2023)

Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

RETRACTED ARTICLE: The role of monetary and fiscal policies in determining environmental pollution: Revisiting the N-shaped EKC hypothesis for China - Tang Zhengxia; Mohammad Haseeb; Muhammad Usman; Mohd Shuaib; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Sustainable utilization of apple pomace and its emerging potential for development of functional foods - Muhammad Asif; Tahreem Javaid; Zafar Ullah Razzaq; Muhmmad Kashif Iqbal Khan; Abid Aslam Maan; Saria Yousaf; Ayesha Usman; Sidra Shahid (Environmental Science and Pollution Research, 2023)

Pathway analysis of food security by employing climate change, water, and agriculture nexus in Pakistan: partial least square structural equation modeling - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Khalid Mushtaq; Abdul Ghafoor; Fiza Amjad; Muhammad Hashim; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2023)

Nickel (Ni) phytotoxicity and detoxification mechanisms: A review - Adnan Mustafa; Usman Zulfiqar; Muhammad Zahid Mumtaz; Maja Radziemska; Fasih Ullah Haider; Jiri Holatko; Tereza Hammershmiedt; Muhammad Naveed; Hassan Ali; Antonin Kintl; Qudsia Saeed; Jiri Kucerik; et al. (Chemosphere, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Sinking delta: Quantifying the impacts of saltwater intrusion in the Indus Delta of Pakistan - Hafsa Aeman; Hong Shu; Sawaid Abbas; Hamera Aisha; Muhammad Usman (Science of The Total Environment, 2023)

High-gravity photocatalytic degradation of tetracycline hydrochloride under simulated sunlight - Yibo Zhao; Lu Chang; Yueyang Li; Wenjing He; Keling Liu; Minjie Cui; Muhammad Usman Hameed; Jiyan Xie (Journal of Water Process Engineering, 2023)

Achieving ecological sustainability through technological innovations, financial development, foreign direct investment, and energy consumption in developing European countries - Rong Wang; Muhammad Usman; Magdalena Radulescu; Javier Cifuentes-Faura; Daniel Balsalobre-Lorente (Gondwana Research, 2023)

Effect of wind and solar energy production, and economic development on the environmental quality: Is this the solution to climate change? - Bilal Hussain; Syed Asif Ali Naqvi; Sofia Anwar; Muhammad Usman (Gondwana Research, 2023)

Boosting the electrochemical activities of MnO2 for next-generation supercapacitor application: Adaptation of multiple approaches - Muhammad Usman Khalid; Khadijah Mohammedsaleh Katubi; Sonia Zulfiqar; Z.A. Alrowaili; Muhammad Aadil; M.S. Al-Buriahi; Muhammad Shahid; Muhammad Farooq Warsi (Fuel, 2023)

Exogenous application of low and high molecular weight organic acids differentially affected the uptake of cadmium in wheat-rice cropping system in alkaline calcareous soil - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Muhammad Azhar; Muhammad Rizwan; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Zahoor Ahmad (Environmental Pollution, 2023)

MXene-PVA-TiO2-based photothermal-catalytic membrane with high structural stability for efficient desalination and photodegradation - Jiawei Sun; Muhammad Usman Farid; Min Wei Boey; Yugo Sato; Guanghao Chen; Alicia Kyoungjin An (Chemical Engineering Journal, 2023)

An integrated Metagenomic-Pangenomic strategy revealed native microbes and magnetic biochar cooperation in plasticizer degradation - Mengyuan Ji; Ginevra Giangeri; Muhammad Usman; Chao Liu; Matteo Bosaro; Filippo Sessa; Paolo Canu; Laura Treu; Stefano Campanaro (Chemical Engineering Journal, 2023)

A causal link between financialization and ecological status: a novel framework for Asian countries? - Saeed Ahmad Sabir; Mubeen Abdur Rehman; Muhammad Zahid Javed; Usman Mehmood; Rabia Ishaq (Environmental Science and Pollution Research, 2023)

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

The role of fiscal decentralization and technological innovations in curbing sulfur dioxide emissions: formulating SDGs policies for China - Ayoub Zeraibi; Atif Jahanger; Muhammad Usman; Daniel Balsalobre-Lorente; Tomiwa Sunday Adebayo; Mustafa Kamal (Environment, Development and Sustainability, 2023)

Do farmers’ risk perception, adaptation strategies, and their determinants benefit towards climate change? Implications for agriculture sector of Punjab, Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Magdalena Radulescu; Khalid Mushtaq; Abdulazeez Hudu Wudil; Sajjad Ahmad Baig; Rimsha Akram (Environmental Science and Pollution Research, 2023)

Correction to: The impact of geopolitical risk, governance, technological innovations, energy use, and foreign direct investment on CO2 emissions in the BRICS region - Ijaz Uddin; Muhammad Usman; Najia Saqib; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2023)

Differential response of nano zinc sulphate with other conventional sources of Zn in mitigating salinity stress in rice grown on saline-sodic soil - Rubaz Ahmed; Muhammad Zia-ur-Rehman; Muhammad Sabir; Muhammad Usman; Muhammad Rizwan; Zahoor Ahmad; Hesham F. Alharby; Hassan S. Al-Zahrani; Hameed Alsamadany; Amal Y. Aldhebiani; Yahya M. Alzahrani; Atif A. Bamagoos (Chemosphere, 2023)

Industrial sludge conversion into biochar and reuse in the context of circular economy: Impact of pre-modification processes on pharmaceuticals removal from aqueous solutions - Salah Jellali; Besma Khiari; Majida Al-Harrasi; Yassine Charabi; Jamal Al-Sabahi; Mohammed Al-Abri; Muhammad Usman; Ahmed Al-Raeesi; Mejdi Jeguirim (Sustainable Chemistry and Pharmacy, 2023)

Biodiesel production from wet sewage sludge and reduced CO2 emissions compared to incineration in Tokyo, Japan - Muhammad Usman; Shuo Cheng; Jeffrey S. Cross (Fuel, 2023)

Extraction of dietary fiber and polyphenols from mango peel and its therapeutic potential to improve gut health - Amna Tariq; Amna Sahar; Muhammad Usman; Aysha Sameen; Marriam Azhar; Rimsha Tahir; Rimsha Younas; Muhammad Issa Khan (Food Bioscience, 2023)

Effects of silicon nanoparticles and conventional Si amendments on growth and nutrient accumulation by maize (Zea mays L.) grown in saline-sodic soil - Ali Rizwan; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Muhammad Usman; Sidra Anayatullah; Areej; Hesham F. Alharby; Atif A. Bamagoos; Basmah M. Alharbi; Shafaqat Ali (Environmental Research, 2023)

A review of research trends on the usage of photocatalysis for wastewater treatment: bibliometric analysis - Abdussamad Mukhtar Mohammed; Farhana Aziz; Safia Syazana Mohtar; Shakhawan Ahmad Mhamad; Bello Ahmadu; Mustapha Usman Nasir; Khuzaifa Yahuza Muhammad; Madzlan Aziz (Sustainable Water Resources Management, 2023)

Correction: Comparative studies of enhancing oil recovery optimization for optimum oil feld development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Azizullah Shaikh; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Comparative studies of enhancing oil recovery optimization for optimum oil field development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Effects of Biotic and Abiotic Aging Techniques on Physiochemical and Molecular Characteristics of Biochar and Their Impacts on Environment and Agriculture: A Review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Yanyan Li; Akash Tariq; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2023)

Composted Melia azedarach L. (Chinaberry tree) Sawdust Mixtures Regulate the Sprouting and Growth of Single Bud Node Seedlings of Sugarcane - Mehwish Sultan Ahmed; Muhammad Yasin; Muhammad Usman Zia; Muhammad Ather Nadeem; Sher Muhammad; Athar Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Principles and Applicability of Integrated Remediation Strategies for Heavy Metal Removal/Recovery from Contaminated Environments - Mohammed Alsafran; Muhammad Hamzah Saleem; Hareb Al Jabri; Muhammad Rizwan; Kamal Usman (Journal of Plant Growth Regulation, 2023)
Contamination of agricultural soils with heavy metals present lethal consequences in terms of diverse ecological and environmental problems that entail entry of metal in food chain, soil deterioration, plant growth suppression, yield reduction and alteration in microbial community. Metal polluted soils have become a major concern for scientists around the globe. In more recent times, armed with new knowledge and understanding, removal of heavy metals using different applications has emerged as a solution for waste treatment and contaminant remediation in water and soil. However, the description of metal toxicity to the plants and its removal and degradation from the soil is limited. There are a number of reports in the literature where PGP bacterial inoculation and various chelating agents improves metal accumulation and it’s detoxification in different plant parts without influencing plant growth. Therefore, there is a need to select some useful chemicals which possess the potential to improve plant growth as well as expedite the phytoremediation of metals. In this review, we have discussed the mechanisms possessed by different chelating agents to promote plant growth and phytoremediation of metals. We anticipate that this analysis of interconnected systems will lead to the discovery of new research fields.

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

Emissions and efficiency of an improved conventional liquefied petroleum gas cookstoves in Pakistan - Muhammad Usman; Muhammad Ammar; Muddassir Ali; Muhammad Zafar; Muhammad Zeeshan (Environment, Development and Sustainability, 2023)

Eco-friendly microwave assisted sustainable coloration of silk and wool fabric with Acid Blue 07 dye - Shahid Adeel; Hira Akram; Muhammad Usman; Tanveer Hussain Bokhari; Muhammad Aftab; Meral Ozomay (Environmental Science and Pollution Research, 2023)

The impact of geopolitical risk, governance, technological innovations, energy use, and foreign direct investment on CO2 emissions in the BRICS region - Ijaz Uddin; Muhammad Usman; Najia Saqib; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2023)

Syntrophic consortium with the aid of coconut shell-derived biochar enhances methane recovery from ammonia-inhibited anaerobic digestion - Yafan Cai; Xia Shen; Xingyao Meng; Zehui Zheng; Muhammad Usman; Kai Hu; Xiaoling Zhao (Science of The Total Environment, 2023)

Identification of disinfection by-products (DBP) in thermal water swimming pools applying non-target screening by LC-/GC-HRMS - Muhammad Usman; Jochen Kuckelkorn; Alexander Kämpfe; Christian Zwiener; Thomas A. Wintgens; Volker Linnemann (Journal of Hazardous Materials, 2023)

Interactive effects of polystyrene microplastics and Pb on growth and phytochemicals in mung bean (Vigna radiata L.) - Fu Chen; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Muhammad Usman Akbar; Fahad Mohammed Alzuaibr; Jing Ma; Ali Noman (Journal of Hazardous Materials, 2023)

Genetic analysis of ACE2 peptidase domain in SARS-CoV-2-positive and SARS-CoV-2-negative individuals from Pakistan - Noor Muhammad; Humaira Naeemi; Ayesha Azeem; Rida Sadaqat; Umara Shehzad; Kashif Siddique; Usman Hassan; Aun Raza; Muhammad Usman Rashid (Molecular Biology Reports, 2023)

Performance assessment of gridded climatic data and modeling spatial accuracy ranking matrix for gridded precipitation using a new pixel-based approach: a district-wise case study of Punjab - Muhammad Usman Saleem; Mian Sohail Akram (Arabian Journal of Geosciences, 2023)

Kinetics, thermodynamic studies, and parametric effects of supercritical CO2 extraction of banana peel wastes - Usman Bello; Nurul Aini Amran; Shafirah Samsuri; Muhammad Syafiq Hazwan Ruslan (Sustainable Chemistry and Pharmacy, 2023)

Dual functional materials capable of integrating adsorption and Fenton-based oxidation processes for highly efficient removal of pharmaceutical contaminants - Muhammad Usman; Olivier Monfort; Sridhar Gowrisankaran; Bassim H. Hameed; Khalil Hanna; Mohammed Al-Abri (Journal of Water Process Engineering, 2023)

Pollution Haven or Halo? How European countries leverage FDI, energy, and human capital to alleviate their ecological footprint - Najia Saqib; Ilhan Ozturk; Muhammad Usman; Arshian Sharif; Asif Razzaq (Gondwana Research, 2023)

A novel strategy to reduce trace element supplementation in the semi-solid anaerobic digestion with gradient ammonia concentration: the role of biochar - Yafan Cai; Xingyao Meng; Kai Hu; Xiaoling Zhao; Muhammad Usman; Giovanni Esposito; Xia Shen; Shanshuai Chen (Fuel, 2023)

Zinc oxide nanoparticles in meat packaging: A systematic review of recent literature - Slim Smaoui; Ichraf Chérif; Hajer Ben Hlima; Muhammad Usman Khan; Maksim Rebezov; Muthu Thiruvengadam; Tanmay Sarkar; Mohammad Ali Shariati; Jose Manuel Lorenzo (Food Packaging and Shelf Life, 2023)

Retraction Note: Detection of HPV16 viral load in L2 gene as a related predictor of cervical cancer among women in Dhi-Qar province by qRT-PCR - Abduladheem Turki Jalil; Muhammad Usman Faryad Khan; Hayder Ali Muhammed; Ahmed Abdulhussein Kawen; Balsam Qubais Saeed; Aleksandr Karevskiy (Molecular Biology Reports, 2023)

Methods to convert lignocellulosic waste into biohydrogen, biogas, bioethanol, biodiesel and value-added chemicals: a review - Nalok Dutta; Muhammad Usman; Muhammad Awais Ashraf; Gang Luo; Mohamed Gamal El-Din; Shicheng Zhang (Environmental Chemistry Letters, 2023)

Heterogeneous role of energy utilization, financial development, and economic development in ecological footprint: How far away are developing economies from developed ones - Ijaz Uddin; Atta Ullah; Najia Saqib; Rakhshanda Kousar; Muhammad Usman (Environmental Science and Pollution Research, 2023)

Algae-Mediated Resource Recovery from Urban Wastewater - Muhammad Usman; Mahwish Amin; Iqra Kamal; Ayesha Shahid; Jingliang Xu; Md. Asraful Alam; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf; Raj Boopathy (Current Pollution Reports, 2023)

COVID-19, travel restrictions and environmental consequences - Muhammad Usman; Li Yuyan; Mudassir Husnain; Muhammad Waheed Akhtar (Environment, Development and Sustainability, 2023)

Response mechanisms of anaerobic fermentative sludge to zinc oxide nanoparticles during medium-chain carboxylates production from waste activated sludge - Chao Liu; Muhammad Usman; Mengyuan Ji; Jun Sha; Li Zhou; Bing Yan (Chemosphere, 2023)

Removal of ceftriaxone sodium antibiotic from pharmaceutical wastewater using an activated carbon based TiO2 composite: Adsorption and photocatalytic degradation evaluation - Muneeb Abdullah; Javed Iqbal; Muhammad Saif Ur Rehman; Usman Khalid; Fahad Mateen; Salman Noshear Arshad; Abdullah G. Al-Sehemi; Hamed Algarni; Omar A. Al-Hartomy; Tahir Fazal (Chemosphere, 2023)

Metal pollution and potential human health risk assessment in major seafood items (fish, crustaceans, and cephalopods) - Muhammad Haseeb-ur-Rehman; Alia Bano Munshi; Usman Atique; Shahida Kalsoom (Marine Pollution Bulletin, 2023)

Impact of differential occupational LPG exposure on cardiopulmonary indices, liver function, and oxidative stress in Northwestern city of Nigeria - Abubakar Usman Ismail; Salisu Ahmed Ibrahim; Mahdi Dissi Gambo; Ramlah Farouq Muhammad; Murtala Muhammad Badamasi; Ibrahim Sulaiman (Science of The Total Environment, 2023)

Recent scenario and nexus between natural resource dependence, energy use and pollution cycles in BRICS region: Does the mediating role of human capital exist? - Atif Jahanger; Mohammad Razib Hossain; Muhammad Usman; Joshua Chukwuma Onwe (Resources Policy, 2023)

Assessment of knowledge, perception, practices and drivers of antimicrobial resistance and antimicrobial usage among veterinarians in Pakistan - Ayesha Saman; Mamoona Chaudhry; Muhammad Ijaz; Waseem Shaukat; Muhammad Usman Zaheer; Ana Mateus; Abdul Rehman (Preventive Veterinary Medicine, 2023)

High efficient conversion of Cannabis sativa L. biomass into bioenergy by using green tungsten oxide nano-catalyst towards carbon neutrality - Tehreem Usman Abbasi; Mushtaq Ahmad; Maliha Asma; Rozina; Mamoona Munir; Muhammad Zafar; Khadijah Mohammedsaleh Katubi; Norah Salem Alsaiari; Adel E.M. Yahya; Muhammad Mubashir; Lai Fatt Chuah; Awais Bokhari (Fuel, 2023)

Algae extract delamination of molybdenum disulfide and surface modification with glycidyl methacrylate and polyaniline for the elimination of metal ions from wastewater - Saleem Raza; Muhammad Usman Hameed; Ehsan Ghasali; Asif Hayat; Yasin Orooji; Hongjun Lin; Ceren Karaman; Fatemeh Karimi; Nevin Erk (Environmental Research, 2023)

Exogenous Application of Thiourea Improves the Growth, Seed Yield, and Seed Fatty Acid Profile in Late Sown Camelina - Muhammad Ahmad; Ejaz Ahmad Waraich; Saddam Hussain; Usman Zulfiqar; Fitsum Tilahun Teshome; Manuel Gastelbondo; Muhammad Imran; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Thiourea Application Increases Seed and Oil Yields in Camelina Under Heat Stress by Modulating the Plant Water Relations and Antioxidant Defense System - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Aman Ullah; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Silicon Enhances Morpho–Physio–Biochemical Responses in Arsenic Stressed Spinach (Spinacia oleracea L.) by Minimizing Its Uptake - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Sahar Mumtaz; Muhammad Imran; Muhammad Arslan Ashraf; Muhammad Rizwan; Kamal Usman; Parvaiz Ahmad; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Aqueous Litter Extracts of Native Grass Species Suppress Exotic Plant Species Under Allelopathic Conditions - Muhammad Usman Ghani; Hang Yuan; Mei Tian; Muhammad Kamran; Fujiang Hou (Journal of Plant Growth Regulation, 2023)

Experimental investigation of tuned liquid column ball damper’s position on vibration control of structure using different fluids - Mati Ullah Shah; Syed Waiz Shah; Syed Hassan Farooq; Muhammad Usman; Farhan Ullah (Innovative Infrastructure Solutions, 2023)

Modelling wellbeing of farmers by using nexus of climate change risk perception, adaptation strategies, and their drivers on irrigation water in Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Sajjad Ahmad Baig; Khalid Mushtaq; Azhar Abbas; Rimsha Akram; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Corrigendum to ‘Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis’, Chemosphere, 311, (2023), 1–10, 137102 - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Nanoparticles assisted regulation of oxidative stress and antioxidant enzyme system in plants under salt stress: A review - Muhammad Zia-ur-Rehman; Sidra Anayatullah; Effa Irfan; Syed Makhdoom Hussain; Muhammad Rizwan; Muhammad Irfan Sohail; Muhammad Jafir; Tanveer Ahmad; Muhammad Usman; Hesham F. Alharby (Chemosphere, 2023)

Effect of farmyard manure, elemental sulphur and EDTA on growth and phytoextraction of cadmium by spider plants (Chlorophytum comosum L.) under Cd stress - Muhammad Zia-ur-Rehman; Arisha Mubsher; Muhammad Rizwan; Muhammad Usman; Muhammad Jafir; Muhammad Umair; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Shafaqat Ali (Chemosphere, 2023)

Tumor micro-environment sensitive release of doxorubicin through chitosan based polymeric nanoparticles: An in-vitro study - Muhammad Usman Akram; Naseem Abbas; Muhammad Farman; Suryyia Manzoor; Muhammad Imran Khan; Sameh M. Osman; Rafael Luque; Abdallah Shanableh (Chemosphere, 2023)

Mixed micellar solubilization for procion blue MxR entrapment and optimization of necessary parameters for micellar enhanced ultrafiltration - Amnah Yusaf; Muhammad Usman; Muhammad Ibrahim; Asim Mansha; Atta ul Haq; Hafiza Fatima Rehman; Majid Ali (Chemosphere, 2023)

Two microbial consortia obtained through purposive acclimatization as biological additives to relieve ammonia inhibition in anaerobic digestion - Shilei Wang; Zhi Wang; Muhammad Usman; Zehui Zheng; Xiaoling Zhao; Xingyao Meng; Kai Hu; Xia Shen; Xiaofen Wang; Yafan Cai (Water Research, 2023)

Nonmonotonic effect of CuO nanoparticles on medium-chain carboxylates production from waste activated sludge - Chao Liu; Haiqing Wang; Muhammad Usman; Mengyuan Ji; Jun Sha; Zhenda Liang; Lishan Zhu; Li Zhou; Bing Yan (Water Research, 2023)

Do green entrepreneurial orientation and green knowledge management matter in the pursuit of ambidextrous green innovation: A moderated mediation model - Muhammad Usman Shehzad; Jianhua Zhang; Khawaja Fawad Latif; Khalid Jamil; Abdul Hakeem Waseel (Journal of Cleaner Production, 2023)

Reduction of metronidazole in municipal wastewater and protection of activated sludge system using a novel immobilized Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Wenxue Wang; Saurabh Kulshrestha; Peng Zhang; Muhammad Usman; Simin Zong; Mian Gul Hilal; Yitian Fang; Huawen Han; Xiangkai Li (Bioresource Technology, 2023)

Efficient Regeneration in Sugarcane Using Thin Cell Layer (TCL) Culture System - Aneela Iqbal; Raham Sher Khan; Mubarak Ali Khan; Karim Gul; Muhammad Aizaz; Muhammad Usman; Muhammad Arif (Sugar Tech, 2023)

Individual and Synergic Effects of Phosphorus and Gibberellic Acid on Organic Acids Exudation Pattern, Ultra-Structure of Chloroplast and Stress Response Gene Expression in Cu-Stressed Jute (Corchorus Capsularis L.) - Aishah Alatawi; Xiukang Wang; Muhammad Hamzah Saleem; Muhammad Mohsin; Muzammal Rehman; Kamal Usman; Shah Fahad; Manar Fawzi Bani Mfarrej; Daniel Ingo Hefft; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Evaluation of aerobic biodegradation of phenanthrene using Pseudomonas turukhanskensis: an optimized study - Monika Sharma; El-Sayed Salama; Muhammad Usman; Aman Khan; Muhammad Arif; Xiangkai Li (Biodegradation, 2023)

Alleviation of drought stress and mediated antioxidative defense in wheat through moringa leaf extract hormesis - Muhammad Usman Ibrahim; Abdul Khaliq; Saddam Hussain; Muhammad Zia Ul Haq (Arabian Journal of Geosciences, 2023)

The inclusive analysis of green technology implementation impacts on employees age, job experience, and size in manufacturing firms: empirical assessment - Sajjad Alam; Jianhua Zhang; Muhammad Usman Shehzad; Fredrick Ahenkora Boamah; Bingbing Wang (Environment, Development and Sustainability, 2023)

Correction to: Nexus between environmental vulnerability and agricultural productivity in BRICS: what are the roles of renewable energy, environmental policy stringency, and technology? - Muhammad Ibrahim Shah; Muhammad Usman; Hephzibah Onyeje Obekpa; Shujaat Abbas (Environmental Science and Pollution Research, 2023)

The relevance of international tourism and natural resource rents in economic growth: Fresh evidence from MINT countries in the digital era - Daniel Balsalobre-Lorente; Lucia Ibañez Luzon; Muhammad Usman; Atif Jahanger (Environmental Science and Pollution Research, 2023)

Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis. - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Environmental performance measurement in arts and cultural organisations: Exploring factors influencing organisational changes - Ana Rita Domingues; Muhammad Usman Mazhar; Richard Bull (Journal of Environmental Management, 2023)

Are Mercosur economies going green or going away? An empirical investigation of the association between technological innovations, energy use, natural resources and GHG emissions - Muhammad Usman; Daniel Balsalobre-Lorente; Atif Jahanger; Paiman Ahmad (Gondwana Research, 2023)

Impact of seasons and wastewater cultivation on the biomass and biodiesel production by the Plectonema terebrans BERC10 as a candidate for a multiproduct algal biorefinery - Muhammad Nabeel Haider; Aqib Zafar Khan; Muhammad Usman; Deepanraj Balakrishnan; Muhammad Rizwan Javed; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

RETRACTED: Effect of soil texture and zinc oxide nanoparticles on growth and accumulation of cadmium by wheat: a life cycle study - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Tahir Abbas; Muhammad Ashar Ayub; Asif Naeem; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Muhammad Javid Qamar; Shafaqat Ali (Environmental Research, 2023)

Evaluation of single-phase net metering to meet renewable energy targets: A case study from Pakistan - Muhammad Usman Tahir; Kiran Siraj; Syed Faizan Ali Shah; Naveed Arshad (Energy Policy, 2023)

Defects passivation by solution-processed titanium doping strategy towards high efficiency kesterite solar cells - Umar Farooq; Usman Ali Shah; Muhammad Ishaq; Ju-Guang Hu; Shehzad Ahmed; Shuo Chen; Zhuang-Hao Zheng; Zheng-Hua Su; Ping Fan; Guang-Xing Liang (Chemical Engineering Journal, 2023)

How ICT and globalization interact with the environment: a case of the Chinese economy - Munaza Bibi; Muhammad Kamran Khan; Muhammad Mutasim Billah Tufail; Danish Iqbal Godil; Rimsha Usman; Muhammad Faizan (Environmental Science and Pollution Research, 2023)

The impact of economic uncertainty, economic growth and energy consumption on environmental degradation in MENA countries: Fresh insights from multiple thresholds NARDL approach - Hicham Ayad; Salah Eddin Sari-Hassoun; Muhammad Usman; Paiman Ahmad (Environmental Science and Pollution Research, 2023)

Do financial development, economic growth, energy consumption, and trade openness contribute to increase carbon emission in Pakistan? An insight based on ARDL bound testing approach - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum; Muhammad Rizwan Yaseen; Abdul Majeed Nadeem (Environment, Development and Sustainability, 2023)

Prevalence of FANCM germline variants in BRCA1/2 negative breast and/or ovarian cancer patients from Pakistan - Muhammad Usman Rashid; Noor Muhammad; Umara Shehzad; Faiz Ali Khan; Asif Loya; Ute Hamann (Familial Cancer, 2023)

Assessment of greenhouse gases emissions, global warming potential and net ecosystem economic benefits from wheat field with reduced irrigation and nitrogen management in an arid region of China - Muhammad Kamran; Zhengang Yan; Irshad Ahmad; Qianmin Jia; Muhammad Usman Ghani; Xianjiang Chen; Shenghua Chang; Tengfei Li; Kadambot H.M. Siddique; Shah Fahad; Fujiang Hou (Agriculture, Ecosystems & Environment, 2023)

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Do all renewable energy stocks react to the war in Ukraine? Russo-Ukrainian conflict perspective - Kamel Si Mohammed; Muhammad Usman; Paiman Ahmad; Urangoo Bulgamaa (Environmental Science and Pollution Research, 2022)

How do energy prices and climate shocks affect human health? Insights from BRICS - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Muhammad Usman Ashraf; Muhammad Asif; Muhammad Wasim Akram (Environmental Science and Pollution Research, 2022)

Tree Communication: the Effects of “Wired” and “Wireless” Channels on Interactions with Herbivores - Muhammad Usman Rasheed; Agnès Brosset; James D. Blande (Current Forestry Reports, 2022)
Purpose of Review Approximately 40 years ago, key papers indicating that volatile chemicals released by damaged plants elicited defense-related changes in their neighbors, brought prominence to the idea of plant communication. These studies were conducted with several tree species and the phenomenon observed was dubbed “talking trees.” Today there is a wealth of evidence supporting the idea that plants can send and receive information both above and belowground. However, while early reports of plant-plant communication concerned trees, the literature is now heavily biased towards herbaceous plants. The purpose of this review is to highlight recent research on tree-tree communication with an emphasis on synthesizing knowledge on the ecological relevance of the process. Recent Findings Aboveground, information is often provided in the form of biogenic volatile organic compounds (VOCs), which are released by both undamaged and damaged plants. The blends of VOCs released by plants provide information on their physiological condition. Belowground, information is conveyed through mycorrhizal networks and via VOCs and chemical exudates released into the rhizosphere. Recent findings have indicated a sophistication to tree communication with more effective VOC-mediated interactions between trees of the same versus a different genotype, kin-group, or chemotype. Moreover, common mycorrhizal networks have been shown to convey stress-related signals in intra- and interspecific associations. Together these two forms of communication represent “wireless” and “wired” channels with significance to facilitating plant resistance to herbivores. Summary In this review, we examine tree-tree communication with a focus on research in natural forest ecosystems. We particularly address the effects of tree-tree communication on interactions with herbivorous insects. Aboveground and belowground interactions are both reviewed and suggested implications for forest management and future research are presented.

RETRACTED ARTICLE: Detection of HPV16 viral load in L2 gene as a related predictor of cervical cancer among women in Dhi-Qar province by qRT-PCR - Abduladheem Turki Jalil; Muhammad Usman Faryad Khan; Hayder Ali Muhammed; Ahmed Abdulhussein Kawen; Balsam Qubais Saeed; Aleksandr Karevskiy (Molecular Biology Reports, 2022)

Nitrogen Pollution Originating from Wastewater and Agriculture: Advances in Treatment and Management - Muhammad Usman; Muhammad Sanaullah; Aman Ullah; Shun Li; Muhammad Farooq (Reviews of Environmental Contamination and Toxicology, 2022)

Combinations of Beauveria bassiana and spinetoram for the management of four important stored-product pests: laboratory and field trials - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Mirza Abdul Qayyum; Taha Yaseen; Muhammad Usman Ghazanfar; Muhammad Yasin (Environmental Science and Pollution Research, 2022)
The current study examines the efficacy of the semi-synthetic insecticide spinetoram and entomopathogenic fungi Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae) as wheat protectants against the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), and the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), under laboratory and field trials. One dose of B. bassiana , i.e., 1 × 10 7 conidia/kg wheat, two doses of spinetoram, i.e., spine1: 0.05 ppm (mg/kg wheat), spine2: 0.1 ppm, and their combinations (Bb + spine1, Bb + spine2) were evaluated at 20, 25, and 30 °C. All treatments provided significantly higher mortality at 30 °C compared with the other two temperatures. Maximum mortality levels were observed in the treatments where B. bassiana was combined with the higher dose of spinetoram (0.1 ppm). All treatments reduced progeny production in comparison with the control groups. Maximum progeny reduction was observed at 30 °C, on wheat treated with the Bb + spine2 combination. The combination Bb + spine2 also provided elevated mortality rates in both laboratory and field persistence trials, but at 180 days caused moderate mortality to all tested insect species. Concerning progeny, at laboratory persistence trials, the combination Bb + spine2 exhibited the lowest offspring emergence to all tested species compared to the other treatments and control. Overall, our study showed that R. dominica was the most susceptible species followed by S. granarius , T. castaneum , and T. granarium . Our findings revealed that the combination of B. bassiana and spinetoram may be a useful tool for efficient and advanced integrated pest management strategies for long storage periods under multiple temperatures.

Capturing spatial variability of factors affecting the water allocation plans—a geo-informatics approach for large irrigation schemes - Muhammad Mohsin Waqas; Muhammad Waseem; Sikandar Ali; Jan W. Hopman; Usman Khalid Awan; Syed Hamid Hussain Shah; Adnan Noor Shah (Environmental Science and Pollution Research, 2022)

Clean energy consumption and CO2 emissions: does China reduce some pollution burdens through environmental regulation? - Chuan Zhang; Ruoxi Cao; Muhammad Tariq Majeed; Ahmed Usman (Environmental Science and Pollution Research, 2022)

Exploring the mediating role of environmental strategy, green innovations, and transformational leadership: the impact of corporate social responsibility on environmental performance - Yasir Hussain; Kashif Abbass; Muhammad Usman; Muhammad Rehan; Muhammad Asif (Environmental Science and Pollution Research, 2022)

Underwater image restoration through regularization of coherent structures - Usman Ali; Muhammad Tariq Mahmood (Frontiers in Marine Science, 2022)
Restoration of underwater images plays a vital role in underwater target detection and recognition, underwater robots, underwater rescue, sea organism monitoring, marine geological survey, and real-time navigation. Mostly, physics-based optimization methods do not incorporate structural differences between the guidance and transmission maps (TMs) which affect the performance. In this paper, we propose a method for underwater image restoration by utilizing a robust regularization of coherent structures. The proposed method incorporates the potential structural differences between TM and the guidance map. The optimization of TM is modeled through a nonconvex energy function which consists of data and smoothness terms. The initial TM is taken as a data term whereas the smoothness term contains static and dynamic structural priors. Finally, the optimization problem is solved using majorize-minimize (MM) algorithm. The proposed method is tested on benchmark dataset and its performance is compared with the state-of-the-art methods. The results from the experiments indicate that the proposed regularization scheme adequately improves the TM, which results in high-quality restored images.

Variation in Vortex-Induced Vibration Phenomenon Due to Surface Roughness on Low- and High-Mass-Ratio Circular Cylinders: A Numerical Study - Muhammad Usman Anwar; Niaz Bahadur Khan; Muhammad Arshad; Adnan Munir; Muhammad Nasir Bashir; Mohammed Jameel; Muhammad Faisal Rehman; Sayed M. Eldin (Journal of Marine Science and Engineering, 2022)
Fluid–structure interaction has been widely studied in the last few decades due to its wide range of applications in engineering fields. This phenomenon plays an important design role, for example, in offshore risers, high slender buildings, chimney stacks and heat exchangers. The vortex shedding generated from a bluff body can induce high-amplitude oscillations, known as vortex-induced vibrations (VIVs). This study presents a numerical analysis to investigate the impact of surface roughness on VIV in the crossflow direction of a circular cylinder. The study also investigates the impact of surface roughness with variation in mass ratio from 2.4 to 11 at a high Reynolds number (Re) = 104 using Reynolds-averaged Navier–Stokes (RANS) equations. The study concludes that roughness on a cylinder results in a reduction in amplitude response. Furthermore, the lock-in region is narrower compared to that of a smooth cylinder, irrespective of the mass ratio. However, it is observed that the impact of surface roughness is more significant in high-mass-ratio cylinders where the lock-in region is more squeezed and shifted toward lower reduced velocities. Furthermore, the vortex mode beyond reduced velocities Ur = 5.84 and 7.52 was observed to be 2S for high and low mass ratios, respectively.

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Simultaneously immobilization of Cd and Pb in paddy soil by magnetic modified biochar based on textile dyeing sludge: metal speciation and soil microbial community evolution - Yinzhu Diao; Xiaoxia Wang; Lei Zhou; Yitong Dan; wenjing Sang; Muhammad Usman; Gang Luo; Yalei Zhang (Journal of Soils and Sediments, 2022)

The Interactive Effect of Selenium and Farmyard Manure on Soil Microbial Activities, Yield and Selenium Accumulation by Wheat (Triticum aestivum L.) Grains - Muhammad Usman Khalid; Muhammad Imran; Muhammad Aslam; Muhammad Ashraf (Journal of Plant Growth Regulation, 2022)

Improving Heat Stress Tolerance in Camelina sativa and Brassica napus Through Thiourea Seed Priming - Muhammad Ahmad; Ejaz Ahmad Waraich; Saddam Hussain; Choudhary Muhammad Ayyub; Zahoor Ahmad; Usman Zulfiqar (Journal of Plant Growth Regulation, 2022)

Integration of renewable energy and technological innovation in realizing environmental sustainability: the role of human capital in EKC framework - Najia Saqib; Arshian Sharif; Asif Razzaq; Muhammad Usman (Environmental Science and Pollution Research, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Response of sorghum and millet to poultry and farmyard manure–based biochar treatments - Muhammad Fraz Ali; Ummar Ali; Shahid Bilal; Usman Zulfiqar; Sidra Sohail; Tajamul Hussain (Arabian Journal of Geosciences, 2022)

Molecular level characterization of DOM along a freshwater-to-estuarine coastal gradient in the Florida Everglades - Dennys Leyva; Rudolf Jaffé; Jessica Courson; John S. Kominoski; Muhammad Usman Tariq; Fahad Saeed; Francisco Fernandez-Lima (Aquatic Sciences, 2022)

Nexus between environmental vulnerability and agricultural productivity in BRICS: what are the roles of renewable energy, environmental policy stringency, and technology? - Muhammad Ibrahim Shah; Muhammad Usman; Hephzibah Onyeje Obekpa; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

Eco-friendly acid dyeing of silk and wool fabrics using Acid Violet 49 dye - Muhammad Usama Shabbir; Shahid Adeel; Tanveer Hussain Bokhari; Muhammad Usman; Muhammad Kaleem Khosa; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Modelling impacts of climate change on coastal West African rainfall - Christopher E. Ndehedehe; Muhammad Usman; Onuwa Okwuashi; Vagner G. Ferreira (Modeling Earth Systems and Environment, 2022)

Modeling implications of climate induced streamflow changes on the fish species of the Soan River, Pakistan - Muhammad Usman; Christopher E. Ndehedehe; Burhan Ahmad; Rodrigo Manzanas (Modeling Earth Systems and Environment, 2022)

Thiourea Application Improves the Growth and Seed and Oil Yields in Canola by Modulating Gas Exchange, Antioxidant Defense, and Osmoprotection Under Heat Stress - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Saddam Hussain; Muhammad Umair Yasin; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2022)

RETRACTED ARTICLE: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2022)

Geochemical investigation of low latitude black shale intervals of the Lower to Middle Jurassic succession, Indus Basin, Pakistan - Fahad Ali; Shiqi Zhang; Muhammad Hanif; Mohibullah Mohibullah; Yaxuan Zhang; Muhammad Usman; Sheng Wang; Xueliang Liu; Pengjie Ma; Dongmou Huang (Frontiers of Earth Science, 2022)

Electrical resistivity in the assessment of subsurface lithology and groundwater depth—a case study in Rawalpindi, Pakistan - Faraz ul Haq; Usman Ali Naeem; Ijaz Ahmad; Muhammad Waseem; Mudassar Iqbal (Arabian Journal of Geosciences, 2022)

Effect of Variation in the Mass Ratio on Vortex-Induced Vibration of a Circular Cylinder in Crossflow Direction at Reynold Number = 104: A Numerical Study Using RANS Model - Muhammad Usman Anwar; Maha M. A. Lashin; Niaz B. Khan; Adnan Munir; Mohammed Jameel; Riaz Muhammad; Kamel Guedri; Ahmed M. Galal (Journal of Marine Science and Engineering, 2022)
This study reports on the numerical analysis of the impact of mass ratio on the Vortex-Induced Vibration (VIV) phenomenon of an elastically rigid cylinder, oscillating freely in a crossflow direction. Reynolds-averaged Navier–Stokes (RANS) equations with (k-ω SST) model were used to analyze the flow behavior, amplitude ratio and vortex shedding patterns. The study was performed at constant Reynold number (Re) = 104 with reduced velocity (Ur) ranging from 2 to 14 and mass ratio (m*) of 2.4 and 11. The mass ratio was defined as the ratio between mass of the vibrating cylinder and mass of the fluid displaced. It was found that increasing the mass ratio from 2.4 to 11 resulted in decrease in amplitude response by 80%, 71% and 31% at initial branch, upper to lower transition region and lower branch, respectively. However, the amplitude in the upper branch decreased only 8% at high mass ratio. The peak amplitude observed in the present study was lower than previous experimental and DES results. However, the RANS k-ω SST well captured the vortex shedding modes of 2S, 2P, P + S, and 2T. In 2S mode, two single pairs of vortices were formed, whereas in 2P mode two pairs were generated in single oscillation. Similarly, P + S meant one pair and one individual vortex; whereas 2T mode meant two triplets of vortices generated in one oscillation. The study concluded that increase in mass ratio results in shortening of the lock-in region and decrease in amplitude response.

Immunological characterization of chitosan adjuvanted outer membrane proteins of Salmonella enterica serovar Typhi as multi-epitope typhoid vaccine candidate - Ambreen Ayub; Muhammad Usman; Ayesha Ihsan; Quratul Ain; Asad Bashir Awan; Muhammad Wajid; Aamir Ali; Abdul Haque; Mazhar Iqbal; Yasra Sarwar (Molecular Biology Reports, 2022)

Comparative transcriptomics of drought stress response of taproot meristem region of contrasting purple carrot breeding lines supported by physio-biochemical parameters - Zahide Neslihan Öztürk Gökçe; Ali Fuat Gökçe; Muhammad Daniyal Junaid; Usman Khalid Chaudhry (Functional & Integrative Genomics, 2022)

Correction to: In-Silico analyses of Nonsynonymous Variants in the BRCA1 Gene - Sidra Arshad; Irfan Ishaque; Sidra Mumtaz; Muhammad Usman Rashid; Naila Malkani (Biochemical Genetics, 2022)

Phytochemicals targeting NAFLD through modulating the dual function of forkhead box O1 (FOXO1) transcription factor signaling pathways - Usman Sabir; Hafiz Muhammad Irfan; Alamgeer; Ihtisham Umer; Zahid Rasul Niazi; Hafiz Muhammad Mazhar Asjad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Facile synthesis of nanomaterials as nanofertilizers: a novel way for sustainable crop production - Farwa Basit; Sana Asghar; Temoor Ahmed; Usman Ijaz; Muhammad Noman; Jin Hu; Xinqiang Liang; Yajing Guan (Environmental Science and Pollution Research, 2022)

A critical review with emphasis on recent pieces of evidence of Moringa oleifera biosorption in water and wastewater treatment - Asmaa Benettayeb; Muhammad Usman; Coffee Calvin Tinashe; Traore Adam; Boumediene Haddou (Environmental Science and Pollution Research, 2022)
The increasing demand for using competent and inexpensive methods based on biomaterials, like adsorption and biosorption, has given rise to the low-priced alternative biosorbents. In the past few years, Moringa oleifera (MO) has emerged as a green and low-priced biosorbent for the treatment of contaminated waters with heavy metals and dyes, and given its availability, we can create another generation of effective biosorbents based on different parts of this plant. In this review paper, we have briefed on the application of MO as a miraculous biosorbent for water purification. Moreover, the primary and cutting-edge methods for the purification and modification of MO to improve its adsorption are discussed. It was found that MO has abundant availability in the regions where it is grown, and simple chemical treatments increase the effectiveness of this plant in the treatment of some toxic contaminants. The different parts of this miraculous plant’s “seeds, leaves, or even husks” in their natural form also possess appreciable sorption capacities, high efficiency for treating low metal concentrations, and rapid adsorption kinetics. Thus, the advantages and disadvantages of different parts of MO as biosorbent, the conditions favorable to this biosorption, also, the proposal of a logical mechanism, which can justify the high efficiency of this plant, are discussed in this review. Finally, several conclusions have been drawn from some important works and which are examined in this review, and future suggestions are proposed.

Energy-levels well-matched direct Z-scheme ZnNiNdO/CdS heterojunction for elimination of diverse pollutants from wastewater and microbial disinfection - Muhammad Shahid Nadeem; Tauseef Munawar; Faisal Mukhtar; Sana Batool; Murtaza Hasan; Usman Ali Akbar; Abbas Saeed Hakeem; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Nexus between non-renewable energy production, CO2 emissions, and healthcare spending in OECD economies - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir; Ghulam Yahya Khan; Muhammad Usman (Environmental Science and Pollution Research, 2022)

Investigation of Morchella esculenta and Morchella conica for their antibacterial potential against methicillin-susceptible Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Streptococcus pyogenes - Faiz Ul Haq; Muhammad Imran; Sidrah Saleem; Usman Aftab; Ayesha Ghazal (Archives of Microbiology, 2022)

Trajectory of anti-SARS-COV-2 IgG antibodies from onset of symptoms to 6 months in a cohort of Pakistani patients - Maria Mehmood; Haleema Usman Khan; Muhammad Ihtesham Khan; Ishaq Khan; Rajaa Mohammad Al-Raddadi; Steve Harakeh; Yasar Mehmood Yousafzai (Infectious Diseases, 2022)

Repressors: the gatekeepers of phytohormone signaling cascades - Usman Aziz; Muhammad Saad Rehmani; Lei Wang; Baoshan Xian; Xiaofeng Luo; Kai Shu (Plant Cell Reports, 2022)

Modeling streamflow using multiple precipitation products in a topographically complex catchment - Muhammad Usman; Christopher E. Ndehedehe; Burhan Ahmad; Rodrigo Manzanas; Oluwafemi E. Adeyeri (Modeling Earth Systems and Environment, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

Pharmacological evaluation of anti-arthritic potential of terpinen-4-ol using in vitro and in vivo assays - Sania Aslam; Waqas Younis; Muhammad Nasir Hayat Malik; Shah Jahan; Alamgeer; Ambreen Malik Uttra; Muhammad Usman Munir; Muhammad Roman (Inflammopharmacology, 2022)

Correction to: Novel role of the Mu‑opioid receptor in pancreatic cancer: potential link between opioid use and cancer progression - Muhammad R. Haque; Usman Barlass; Andrew Armstrong; Maliha Shaikh; Faraz Bishehsari (Molecular and Cellular Biochemistry, 2022)

Novel role of the Mu-opioid receptor in pancreatic cancer: potential link between opioid use and cancer progression - Muhammad R. Haque; Usman Barlass; Andrew Armstrong; Maliha Shaikh; Faraz Bishehsari (Molecular and Cellular Biochemistry, 2022)

Laboratory and field studies on the combined application of Beauveria bassiana and fipronil against four major stored-product coleopteran insect pests - Waqas Wakil; Nickolas G. Kavallieratos; Muhammad Usman Ghazanfar; Muhammad Usman (Environmental Science and Pollution Research, 2022)

First report on molecular surveillance based on duplex detection of Anaplasma marginale and Theileria annulata in dairy cattle from Punjab, Pakistan - Farhan Ahmad Atif; Rao Zahid Abbas; Saba Mehnaz; Muhmmad Fiaz Qamar; Kashif Hussain; Muhammad Usman Nazir; Muhammad Arfan Zaman; Aman Ullah Khan; Mourad Ben Said (Tropical Animal Health and Production, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

From the COVID-19 pandemic to corrupt practices: a tale of two evils - Muhammad Usman; Mudassir Husnain; Muhammad Waheed Akhtar; Yameen Ali; Areej Riaz; Aimon Riaz (Environmental Science and Pollution Research, 2022)

Determinants of renewable energy sources in Pakistan: An overview - Umar Suffian Ahmad; Muhammad Usman; Saddam Hussain; Atif Jahanger; Maira Abrar (Environmental Science and Pollution Research, 2022)

The trade-off between economic performance and environmental quality: does financial inclusion matter for emerging Asian economies? - Dong Liu; Yuantao Xie; Muhammad Hafeez; Ahmed Usman (Environmental Science and Pollution Research, 2022)

Environmental pollution and agricultural productivity in Pakistan: new insights from ARDL and wavelet coherence approaches - Muhammad Ramzan; Hafiz Arslan Iqbal; Muhammad Usman; Ilhan Ozturk (Environmental Science and Pollution Research, 2022)

A sustainable generalization of inverse Lindley distribution for wind speed analysis in certain regions of Pakistan - Muhammad Shoaib; Irum Sajjad Dar; Muhammad Ahsan-ul-Haq; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2022)

Cadmium Toxicity in Plants: Recent Progress on Morpho-physiological Effects and Remediation Strategies - Usman Zulfiqar; Aqsa Ayub; Saddam Hussain; Ejaz Ahmad Waraich; Mohamed A. El-Esawi; Muhammad Ishfaq; Muhammad Ahmad; Nauman Ali; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2022)

Morphological, physiological, and biochemical responses of onion (Allium cepa L.) breeding lines to single and combined salt and drought stresses - Zahide Neslihan Öztürk Gökçe; Ali Fuat Gökçe; Muhammad Daniyal Junaid; Usman Khalid Chaudhry (Euphytica, 2022)

Competency of groundwater recharge of irrigated cotton field subjacent to sowing methods, plastic mulch, water productivity, and yield under climate change - Muhammad Saeed; Ahsan Maqbool; Muhammad Adnan Ashraf; Muhammad Arshad; Kashif Mehmood; Muhammad Usman; Muhammad Arslan Farid (Environmental Science and Pollution Research, 2022)
Irrigated agriculture is a foremost consumer of water resources to fulfill the demand for food and fiber with an increasing population under climate changes; cotton is no exception. Depleting groundwater recharge and water productivity is critical for the sustainable cotton crop yield peculiarly in the semiarid region. This study investigated the water productivity and cotton yield under six different treatments: three sowing methods, i.e., flat, ridge, and bed planting with and without plastic mulch. Cotton bed planting without mulch showed maximum water productivity (0.24 kg.m −3 ) and the highest cotton yield (1946 kg.ha −1 ). Plastic mulching may reduce water productivity and cotton yield. HYDRUS-1D unsaturated flow model was used to access the groundwater recharge for 150 days under six treatments after model performance evaluation. Maximum cumulative recharge was observed 71 cm for the flat sowing method without plastic mulch. CanESM2 was used to predict climate scenarios for RCP 2.6, 4.5, and 8.5 for the 2050s and 2080s by statistical downscale modeling (SDSM) using historical data from 1975 to 2005 to access future groundwater recharge flux. Average cumulative recharge flux declined 36.53% in 2050 and 22.91% in 2080 compared to 2017 without plastic mulch. Multivariate regression analysis revealed that a maximum 23.78% reduction in groundwater recharge could influence future climate change. Further study may require to understand the remaining influencing factor of depleting groundwater recharge. Findings highlight the significance of climate change and the cotton sowing method while accessing future groundwater resources in irrigated agriculture.

Do environmental pollutants carrier to COVID-19 pandemic? A cross-sectional analysis - Salman Shamsi; Khalid Zaman; Bushra Usman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Forecasting carbon emissions due to electricity power generation in Bahrain - Mohammed Redha Qader; Shahnawaz Khan; Mustafa Kamal; Muhammad Usman; Mohammad Haseeb (Environmental Science and Pollution Research, 2022)

Recent trends in the use of fly ash for the adsorption of pollutants in contaminated wastewater and soils: Effects on soil quality and plant growth - Muhammad Usman; Ioannis Anastopoulos; Yasir Hamid; Abdul Wakeel (Environmental Science and Pollution Research, 2022)

Removing Hexavalent Chromium by Nano Zero-Valent Iron Loaded on Attapulgite - Yuzhen Wei; Muhammad Usman; Muhammad Farooq; Muhammad Adeel; Fasih Ullah Haider; Zhandong Pan; Weiwei Chen; Hongyan Liu; Liqun Cai (Water, Air, & Soil Pollution, 2022)

Characterization of interannual and seasonal variability of hydro-climatic trends in the Upper Indus Basin - Muhammad Usman Liaqat; Giovanna Grossi; Shabeh ul Hasson; Roberto Ranzi (Theoretical and Applied Climatology, 2022)

Isatin derivatives as broad-spectrum antiviral agents: the current landscape - Tilal Elsaman; Malik Suliman Mohamed; Eyman Mohamed Eltayib; Hatem A. Abdel-aziz; Abualgasim Elgaili Abdalla; Muhammad Usman Munir; Magdi Awadalla Mohamed (Medicinal Chemistry Research, 2022)

Sorghum Water Extract Application Mediates Antioxidant Defense and Confers Drought Stress Tolerance in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Saddam Hussain; Ghulam Murtaza (Journal of Plant Growth Regulation, 2022)

A step towards sustainable path: The effect of globalization on China’s carbon productivity from panel threshold approach - Atif Jahanger; Muhammad Usman; Paiman Ahmad (Environmental Science and Pollution Research, 2022)

Multivariate analysis of accumulation and critical risk analysis of potentially hazardous elements in forage crops - Muhammad Usman; Behzad Murtaza; Natasha Natasha; Muhammad Imran; Ghulam Abbas; Muhammad Amjad; Muhammad Shahid; Sobhy M. Ibrahim; Gary Owens; Ghulam Murtaza (Environmental Monitoring and Assessment, 2022)

Feedstock type, pyrolysis temperature and acid modification effects on physiochemical attributes of biochar and soil quality - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman (Arabian Journal of Geosciences, 2022)

Energy-efficient dynamic channel allocation algorithm in wireless body area network - Muhammad Ashraf; Shahzad Hassan; Saddaf Rubab; Muhammad Attique Khan; Usman Tariq; Seifedine Kadry (Environment, Development and Sustainability, 2022)

Biofertilizer microorganisms accompanying pathogenic attributes: a potential threat - Mohsin Tariq; Farwah Jameel; Usman Ijaz; Muhammad Abdullah; Kamran Rashid (Physiology and Molecular Biology of Plants, 2022)

The dynamic impact of renewable energy sources on environmental economic growth: evidence from selected Asian economies - Muhammad Khalid Anser; Muhammad Usman; Muhammad Sharif; Sana Bashir; Malik Shahzad Shabbir; Ghulam Yahya Khan; Lydia Bares Lopez (Environmental Science and Pollution Research, 2022)

Investigation of antifungal response of NiO and copper-doped NiO thin films against Aspergillus niger and Macrophomina phaseolina fungi - Muzamil Aftab; Muhammad Zakria Butt; Dilawar Ali; Zille Huma Aftab; Muhammad Usman Tanveer; Bakhtawar Fayyaz (Environmental Science and Pollution Research, 2022)

Synthesis and characterization of ZnO decorated reduced graphene oxide (ZnO-rGO) and evaluation of its photocatalytic activity toward photodegradation of methylene blue - Asif Nisar; Muhammad Saeed; Majid Muneer; Muhammad Usman; Iltaf Khan (Environmental Science and Pollution Research, 2022)

Economic assessment of water-saving irrigation management techniques and continuous flooded irrigation in different rice production systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Fahimuddin Shah; Shakeel Ahmad Anjum; Muhammad Farooq (Paddy and Water Environment, 2022)

Depositional Sedimentary Facies, Stratigraphic Control, Paleoecological Constraints, and Paleogeographic Reconstruction of Late Permian Chhidru Formation (Western Salt Range, Pakistan) - Syed Kamran Ali; Hammad Tariq Janjuhah; Syed Muzyan Shahzad; George Kontakiotis; Muhammad Hussain Saleem; Usman Khan; Stergios D. Zarkogiannis; Panayota Makri; Assimina Antonarakou (Journal of Marine Science and Engineering, 2021)
The Upper Indus Basin, in Pakistan’s western Salt Range, is home to the Zaluch Gorge. The sedimentary rocks found in this Gorge, belonging to the Chhidru Formation, were studied in terms of sedimentology and stratigraphy, and provide new insights into the basin paleogeographic evolution from the Precambrian to the Jurassic period. Facies analysis in the Chhidru Formation deposits allowed the recognition of three lithofacies (the limestone facies—CF1, the limestone with clay interbeds facies—CF2, and the sandy limestone facies—CF3) with five microfacies types (mudstone biomicrite—MF-1, wackestone-biomicrite—MF-2, wackestone-biosparite—MF-3, pack-stone-biomicrite—MF-4, and packstone-biosparite—MF-5), as well as their depositional characteristics. The identified carbonate and siliciclastic formations display various facies in a shallow marine environment, with different lithologies, sedimentary features, and energy conditions. It is thought that the depositional characteristics of these microfacies are closer to those of the middle to outer shelf. Because of the progressively coarsening outcrop sequence, this formation seems to be at the very top of the high stand system tract (HST). A modified dynamic depositional model of the Chhidru Formation is further built using outcrop data, facies information, and stratigraphy. According to this concept, the formation was deposited in the middle to inner shelf area of the shallow marine environment, during the Late-Permian period. The Permo-Triassic Boundary (PTB), which is the end of the type-1 series, is marked by this formation’s top.

The effect of GnRH administration/insemination time on follicular growth rate, ovulation intervals, and conception rate of Nili Ravi buffalo heifers in 7 –day-CIDR Co-synch - Sajjad Haider; Ghazanfar Ali Chishti; Muhammad Usman Mehmood; Muhammad Ameen Jamal; Khalid Mehmood; Muhammad Shahzad; Muhammad Zahid Tahir (Tropical Animal Health and Production, 2021)

Quantifying climate-induced drought risk to livelihood and mitigation actions in Balochistan - Muhammad Ashraf; Adnan Arshad; Praharsh M. Patel; Adeel Khan; Huma Qamar; Ristina Siti-Sundari; Muhammad Usman Ghani; Ali Amin; Jamilur Rehman Babar (Natural Hazards, 2021)

Implementation of Vaccinomics and In-Silico Approaches to Construct Multimeric Based Vaccine Against Ovarian Cancer - Muhammad Sufyan; Farah Shahid; Faiza Irshad; Anam Javaid; Muhammad Qasim; Usman Ali Ashfaq (International Journal of Peptide Research and Therapeutics, 2021)

Geological and Geomorphological Characteristics of Hingol National Park (HNP), Balochistan: a Geoheritage Candidate from Southern Pakistan - Muhammad Yaseen; Abbas Ali Naseem; Jawad Ahmad; Afrasiab Khan; Abdullah Khan; Muhammad Alamzeb; Adnan Ahmad; Usman Saeed; Arsalan Ahmad (Geoheritage, 2021)

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

In-Silico Analyses of Nonsynonymous Variants in the BRCA1 Gene - Sidra Arshad; Irfan Ishaque; Sidra Mumtaz; Muhammad Usman Rashid; Naila Malkani (Biochemical Genetics, 2021)

Economic assessment of prospective shale gas play in Pakistan using discounted cashflow model - Faizan Ali; Muhammad Arqam Khan; Naeem ul Hussain Dahraj; Musab Usman; Laiba Sajid Cheema (Arabian Journal of Geosciences, 2021)

Assessment of Microscopic Detection of Malaria with Nested Polymerase Chain Reaction in War-Torn Federally Administered Tribal Areas of Pakistan - Muhammad Faisal Nadeem; Aamer Ali Khattak; Nadia Zeeshan; Usman Ayub Awan; Adnan Yaqoob (Acta Parasitologica, 2021)

Socio-economic and corporate factors and COVID-19 pandemic: a wake-up call - Muhammad Khalid Anser; Sheikh Usman Yousaf; Shabir Hyder; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

Modeling financial development, tourism, energy consumption, and environmental quality: Is there any discrepancy between developing and developed countries? - Muhammad Usman; Muhammad Rizwan Yaseen; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2021)

Arsenate removal from drinking water using by-products from conventional iron oxyhydroxides production as adsorbents coupled with submerged microfiltration unit - Muhammad Usman; Ioannis Katsoyiannis; Josma Henna Rodrigues; Mathias Ernst (Environmental Science and Pollution Research, 2021)
Arsenic is among the major drinking water contaminants affecting populations in many countries because it causes serious health problems on long-term exposure. Two low-cost micro-sized iron oxyhydroxide-based adsorbents (which are by-products of the industrial production process of granular adsorbents), namely, micro granular ferric hydroxide (μGFH) and micro tetravalent manganese feroxyhyte (μTMF), were applied in batch adsorption kinetic tests and submerged microfiltration membrane adsorption hybrid system (SMAHS) to remove pentavalent arsenic (As(V)) from modeled drinking water. The adsorbents media were characterized in terms of iron content, BET surface area, pore volume, and particle size. The results of adsorption kinetics show that initial adsorption rate of As(V) by μTMF is faster than μGFH. The SMAHS results revealed that hydraulic residence time of As(V) in the slurry reactor plays a critical role. At longer residence time, the achieved adsorption capacities at As(V) permeate concentration of 10 μg/L (WHO guideline value) are 0.95 and 1.04 μg/mg for μGFH and μTMF, respectively. At shorter residence time of ~ 3 h, μTMF was able to treat 1.4 times more volumes of arsenic-polluted water than μGFH under the optimized experimental conditions due to its fast kinetic behavior. The outcomes of this study confirm that micro-sized iron oyxhydroxides, by-products of conventional adsorbent production processes, can successfully be employed in the proposed hybrid water treatment system to achieve drinking water guideline value for arsenic, without considerable fouling of the porous membrane.

Use of anomalous topographic features for landslide inventory mapping of Gilgit area, Gilgit-Baltistan, Pakistan - Muhammad Farooq Ahmed; Usman Awan; J. David Rogers (Arabian Journal of Geosciences, 2021)

Facies Analysis and Sedimentary Architecture of Hybrid Event Beds in Submarine Lobes: Insights from the Crocker Fan, NW Borneo, Malaysia - Muhammad Jamil; Numair Ahmed Siddiqui; Nisar Ahmed; Muhammad Usman; Muhammad Umar; Hamad ur Rahim; Qazi Sohail Imran (Journal of Marine Science and Engineering, 2021)
Hybrid event beds represent the combined effect of multiple geological processes, which result in complex depositional geometries and distinct facies distribution in marine environments. Previous work on hybrid event beds highlights the classification, origin, and types of hybrid facies. However, in the present study, we discuss the development of hybrid event beds in submarine lobes with an emphasis on the analysis of proximal to distal, frontal to lateral relationships and evolution during lobe progradation. Detailed geological fieldwork was carried out in the classical deep-marine Late Paleogene Crocker Fan to understand the relationship between the character of hybrid bed facies and lobe architecture. The results indicate that hybrid facies of massive or structureless sandstone with mud clasts, clean to muddy sand, and chaotic muddy sand with oversized sand patch alternations (H1–H3) are well developed in proximal to medial lobes, while distal lobes mainly contain parallel to cross-laminated clean to muddy hybrid facies (H3–H5). Furthermore, lateral lobes have less vertical thickness of hybrid beds than frontal lobes. The development of hybrid beds takes place in the lower part of the thickening upward sequence of lobe progradation, while lobe retrogradation contains hybrid facies intervals in the upper part of stratigraphy. Hence, the development of hybrid beds in submarine lobe systems has a significant impact on the characterization of heterogeneities in deep-marine petroleum reservoirs at sub-seismic levels.

Pharmacological evaluation of the gabapentin salicylaldehyde derivative, gabapentsal, against tonic and phasic pain models, inflammation, and pyrexia - Nisar Ahmad; Fazal Subhan; Nazar Ul Islam; Muhammad Shahid; Naseem Ullah; Rahim Ullah; Muhammad Khurram; Muhammad Usman Amin; Shehla Akbar; Ihsan Ullah; Robert D. E. Sewell (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Correction to: Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab Ismail Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

Effects of tourism, financial development, and renewable energy on environmental performance in EU-28: does institutional quality matter? - Muhammad Sani Musa; Gylych Jelilov; Paul Terhemba Iorember; Ojonugwa Usman (Environmental Science and Pollution Research, 2021)

Analyzing the determinants of clean energy consumption in a sustainability strategy: evidence from EU-28 countries - Muhammad Usman; Zhiqiang Ma; Muhammad Wasif Zafar; Abdul Waheed; Mingxing Li (Environmental Science and Pollution Research, 2021)

Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab I. Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

Evaluating the suitability of two parametric wind speed distributions: a case study from Pakistan - Muhammad Ahsan ul Haq; Sohail Chand; Muhammad Zahir Sajjad; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2021)

Biochar for the Management of Nutrient Impoverished and Metal Contaminated Soils: Preparation, Applications, and Prospects - Ghulam Murtaza; Allah Ditta; Naseer Ullah; Muhammad Usman; Zeeshan Ahmed (Journal of Soil Science and Plant Nutrition, 2021)

A New Sequential Forward Feature Selection (SFFS) Algorithm for Mining Best Topological and Biological Features to Predict Protein Complexes from Protein–Protein Interaction Networks (PPINs) - Haseeb Younis; Muhammad Waqas Anwar; Muhammad Usman Ghani Khan; Aisha Sikandar; Usama Ijaz Bajwa (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Does improvement in the environmental sustainability rating help to reduce the COVID-19 cases? Controlling financial development, price level and carbon damages - Muhammad Khalid Anser; Bushra Usman; Shabir Hyder; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

Climate change during the COVID-19 outbreak: scoping future perspectives - Muhammad Usman; Mudassir Husnain; Aimon Riaz; Areej Riaz; Yameen Ali (Environmental Science and Pollution Research, 2021)

Anaerobic Digestion of Digested Manure Fibers: Influence of Thermal and Alkaline Thermal Pretreatment on the Biogas Yield - Muhammad Usman Khan; Birgitte K. Ahring (BioEnergy Research, 2021)

Foliar Manganese Supply Enhances Crop Productivity, Net Benefits, and Grain Manganese Accumulation in Direct-Seeded and Puddled Transplanted Rice - Usman Zulfiqar; Saddam Hussain; Muhammad Ishfaq; Nauman Ali; Muhammad Umair Yasin; Muhammad Arif Ali (Journal of Plant Growth Regulation, 2021)

Correction to: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

A critical review of state-of-the-art electrocoagulation technique applied to COD-rich industrial wastewaters - Milad Mousazadeh; Elnaz Karamati Niaragh; Muhammad Usman; Saif Ullah Khan; Miguel Angel Sandoval; Zakaria Al-Qodah; Zaied Bin Khalid; Vishakha Gilhotra; Mohammad Mahdi Emamjomeh (Environmental Science and Pollution Research, 2021)

Simulation-based non-linear vibration model for damage detection in RC beams - Muhammad Usman Hanif; Zainah Ibrahim; Mohammed Jameel; Khaled Ghaedi; Huzaifa Hashim (European Journal of Environmental and Civil Engineering, 2021)

Teleconnection of spatial variations of effective onset of rainfall and ENSO\IOD over savanna zones of Nigeria - Ishiaku Ibrahim; Muhammad T. Usman (Theoretical and Applied Climatology, 2021)

Correction to: Heterogeneous effects of remittances and institutional quality in reducing environmental deficit in the presence of EKC hypothesis: a global study with the application of panel quantile regression - Muhammad Usman; Atif Jahanger (Environmental Science and Pollution Research, 2021)

Heterogeneous effects of remittances and institutional quality in reducing environmental deficit in the presence of EKC hypothesis: A global study with the application of panel quantile regression - Muhammad Usman; Atif Jahanger (Environmental Science and Pollution Research, 2021)

Re-evaluating the asymmetric conventional energy and renewable energy consumption-economic growth nexus for Pakistan - Muhammad Afaq Haider Jafri; Huizheng Liu; Ahmed Usman; Qasim Raza Khan (Environmental Science and Pollution Research, 2021)

Impact of economic capabilities and population agglomeration on PM2.5 emission: empirical evidence from sub-Saharan African countries - Summaira Malik; Asim Iqbal; Asma Imran; Muhammad Usman; Muhammad Nadeem; Saira Asif; Awais Bokhari (Environmental Science and Pollution Research, 2021)

CO2 separation by supported liquid membranes synthesized with natural deep eutectic solvents - Usman Saeed; Asim Laeeq Khan; Mazhar Amjad Gilani; Muhammad Aslam; Asad Ullah Khan (Environmental Science and Pollution Research, 2021)

Innovative initiative for effective operation and monitoring using HEC‐RAS modelling of Hakra Branch Canal System, Pakistan * - Muhammad Kamran; Wasif Yousaf; R.L.H.L. Rajapakse; Wakas Kareem Awan; Muhammad Riaz; Nayyar Minhaj Asif; Muhammad Umar; Usman Tehsin Shah (Irrigation and Drainage, 2021)
The Punjab Irrigation System is one of the world's largest contiguous systems, with its entire network extending over nearly 31,000 km in length. The system faces numerous constraints that limit the canal operations and their respective design discharges. Shortage of irrigation water is a contest that normally occurs at canal tail‐end users. The hydraulic performance of open canal networks is not easy to assess; therefore, it is impossible to feed the lateral offtakes with their design shares without changing designed or existing gate openings. To overcome these problems, a Hydrologic Engineering Center's River Analysis System (HEC‐RAS) model has been developed to simulate the flow situation in the canal system. For this study, the Hakra Branch Canal System with a command area of 1.4 million hectares was selected. To recognize model performance, water levels at the head of the canal and tail discharge have been compared with field data. The simulated results show the best‐fit match with field head water levels with coefficients of determination ( R 2 ) of 0.765 and 0.877 and tail discharges of the canal with R 2 = 0.707 and 0.945, for calibration and validation periods, respectively. The hydraulic simulation model is a useful tool for effective canal operation to determine the losses and find out the expected discharge for the tail‐end users. It has been observed that the proportion of excess actual delivery of water to lateral offtakes results in inadequate water supply for the tail‐end users. It is recommended that during the observation of the seasonally discharge table, the irrigation engineer should adjust a factor either in the HEC‐RAS model or in the observed data. It is also recommended to develop an unsteady model for considering sediment transport.

RETRACTED ARTICLE: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2021)

Emissions of biogenic volatile organic compounds (BVOCs) from the rhizosphere of Scots pine (Pinus sylvestris) seedlings exposed to warming, moderate N addition and bark herbivory by large pine weevil (Hylobius abietis) - Muhammad Usman Rasheed; M. Kivimäenpää; A. Kasurinen (Plant and Soil, 2021)
Aims Biogenic volatile organic compound (BVOC) research has been mostly focused on foliar emissions. In this experiment, the main focus was on rhizosphere BVOC emissions of Scots pine seedlings under changing growth conditions. Methods Soil-growing Scots pines were exposed to increased air (0.5°C) and soil (4.0°C) temperature and N addition (30 kg N ha − 1 yr − 1 ) for three growing seasons in a field experiment. In addition to these factors, seedlings were exposed to bark herbivory by large pine weevils in two last seasons. Gas-chromatography and mass-spectrometry was used for analyzing the BVOC samples collected from pine rhizosphere. Results Almost 98 % of BVOCs were non-oxygenated monoterpenes (nMTs), 1 % oxygenated monoterpenes (oMTs), 0.5 % sesquiterpenes (SQTs), and 1 % other BVOCs. In both years, there was an interaction of warming, N addition and bark herbivory on rhizosphere BVOC emissions. In 2015, warming and N addition in single exposures decreased oMT emissions, while herbivory in single exposure increased oMT emissions. In 2016, the three-way interaction showed that the effects of warming, N addition and herbivory on BVOCs were mainly detected in single exposures. In 2016, warming decreased nMT, oMT, SQT and other BVOC emissions; N addition decreased oMT and SQT emissions; and herbivory decreased SQT and other BVOC emissions. Conclusions Warming and N addition in single exposures decreased the rhizosphere BVOC emissions. The effect of bark herbivory on BVOC emissions varied between the years from increase to decrease. It seems that under altered growth conditions Scots pine seedlings may reduce carbon investment to rhizosphere BVOCs.

Renewable energy and non-renewable energy consumption: assessing the asymmetric role of monetary policy uncertainty in energy consumption - Muhammad Tayyab Sohail; Yu Xiuyuan; Ahmed Usman; Muhammad Tariq Majeed; Sana Ullah (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: The shadow economy in South Asia: dynamic effects on clean energy consumption and environmental pollution - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman; Zubaria Andlib (Environmental Science and Pollution Research, 2021)
This study explores the symmetric and asymmetric effects of the shadow economy on clean energy and air pollution of South Asian countries over the period 1991–2019. The short-run ARDL findings for the clean energy model suggest that shadow economy increases clean energy consumption in Pakistan and Sri Lanka, whereas this effect is negative for India and insignificant for other countries. The long-run results indicate the adverse impact only for India and the effects of tax revenue on clean energy are positively significant in Sri Lanka while negatively signiicant in Nepal and Bangladesh. Institutional quality significantly increases clean energy in Pakistan, India, and Nepal. However, in the case of Pakistan and Nepal, institutional quality deteriorated the environmental quality. The results for the pollution model confer that shadow economy increases emissions in Pakistan, decreases in Bangladesh and Nepal, and has no effect in India and Sri Lanka. The nonlinear ARDL results reveal that the positive components of the shadow economy significantly increase clean energy consumption only in Pakistan; however, the negative components of the shadow economy are negatively significant in all countries except Sri Lanka and Nepal. However, the negative component of the informal sector of the economy reduces CO2 emissions in India and increases CO2 emissions in Bangladesh and Nepal. The results offer important policy implications for achieving clean energy and better environmental quality in South Asian countries.

Pakistan management of green transportation and environmental pollution: a nonlinear ARDL analysis - Muhammad Tayyab Sohail; Sana Ullah; Muhammad Tariq Majeed; Ahmed Usman (Environmental Science and Pollution Research, 2021)
Modern advances in nonlinear modeling have exposed that nonlinear models yield more robust results compared with linear models. Research on the effect of air-railway transportation on environmental pollution has now arrived into a new way of asymmetry analysis and captured the real issue among the nexus. This study aims to inspect the asymmetric impact of air-railway transportation on environmental pollution in Pakistan by using annual time series data from 1991 to 2019. The findings show that positive shock in air passenger carried and railway passenger carried increases carbon emissions, which implies that 1% increase in air passenger carried (railway passenger carried) enhances environmental pollution by 0.21% (0.32%) in long run in Pakistan. While positive shock in railway passengers carried increases environmental pollution and negative shock in railway passengers carried decreases the environmental pollution in the short run. The outcomes have also confirmed the short- and long-run asymmetries in Wald statistics. The findings are country-specific and it would be regionally specific.

Molecular docking of alpha-enolase to elucidate the promising candidates against Streptococcus pneumoniae infection - Muhammad Hassan; Atif Amin Baig; Syed Awais Attique; Shafqat Abbas; Fizza Khan; Sara Zahid; Qurat Ul Ain; Muhammad Usman; Nordin Bin Simbak; Mohammad Amjad Kamal; Hanani Ahmad Yusof (DARU Journal of Pharmaceutical Sciences, 2021)

COVID-19 and the emerging research trends in environmental studies: a bibliometric evaluation - Muhammad Usman; Yuh-Shan Ho (Environmental Science and Pollution Research, 2021)

The dynamic linkage between globalization, financial development, energy utilization, and environmental sustainability in GCC countries - Bo Yang; Atif Jahanger; Muhammad Usman; Muhammad Atif Khan (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Comparative analyses of standardised precipitation index and moisture quality index for wet and dry periods monitoring over the savanna zones of Nigeria - Ishiaku Ibrahim; Muhammad T. Usman (Arabian Journal of Geosciences, 2021)

Pomegranate as a source of bioactive constituents: a review on their characterization, properties and applications - Maryam Pirzadeh; Nicola Caporaso; Abdur Rauf; Mohammad Ali Shariati; Zhanibek Yessimbekov; Muhammad Usman Khan; Muhammad Imran; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2021)

Impact of light stimulation during incubation on hatching traits and post-hatch performance of commercial broilers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Abd ur Rehman; Muhammad Usman; Shahid Mehmood; Sohail Ahmad (Tropical Animal Health and Production, 2021)

Molecular epidemiology of Coxiella Brunetii in small ruminants in Punjab, Pakistan: a novel reporting analytical cross sectional study - Muhammad Zahid Iqbal; Aneela Zameer Durrani; Jawaria Ali Khan; Nisar Ahmad; Muhammad Usman; Abdul Jabbar; Amjad Khan; Saba Usman; Ahsan Anjum; Muhammad Husnain (Tropical Animal Health and Production, 2021)

Mating Type and Aggressiveness of Phytophthora infestans (Mont.) de Bary in Potato-Growing Areas of Punjab, Pakistan, 2017–2018 and Identification of Genotype 13_A2 in 2019–2020 - Waqas Raza; Muhammad Usman Ghazanfar; Louise Sullivan; David E. L. Cooke; Louise R. Cooke (Potato Research, 2021)
Samples of blighted potato leaves were collected from fields in six potato-growing districts of the Punjab Province of Pakistan in 2017–2018. A total of 149 isolates of Phytophthora infestans were obtained from six potato cultivars (Asterix, Barsenna, Burana, Caroda, Mazika, Sante). Of these isolates, 73% were A1 mating type, 23% were A2 mating type and 4% were self-fertile. Both mating types of P. infestans occurred in all six districts sampled, but in every case, the A1 mating type predominated. The foliar aggressiveness of 104 of these isolates (weakly pathogenic isolates were excluded) was tested on detached leaflets of potato cv. Caroda, and a composite aggressiveness index (CAI) calculated from lesion area (measured after 10 days), latent period and infection frequency was used to compare isolates. There was no difference in CAI between isolates obtained from different districts or cultivars. The A2 mating type isolates had significantly greater CAIs than A1 isolates but this does not imply a genetic linkage nor a general association between mating type and aggressiveness. It may be that the A2 isolates belonged to an aggressive clonal lineage such as 13_A2 that has been reported in other countries in the region. While it was not possible to test the isolates collected in 2017–2018, genotyping of samples collected in 2019–2020 showed the widespread occurrence of the EU_13_A2 clonal lineage in the same districts of Pakistan and supported this hypothesis. This is the first report of EU_13_A2 from Pakistan. The implications for potato late blight management in the Punjab are discussed.

Influence of Nitrogen Fertilization Pattern on Productivity, Nitrogen Use Efficiencies, and Profitability in Different Rice Production Systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Khawar Jabran; Mohsin Nawaz; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Dynamic relationship between technological innovations, financial development, renewable energy, and ecological footprint: fresh insights based on the STIRPAT model for Asia Pacific Economic Cooperation countries - Muhammad Usman; Nesrine Hammar (Environmental Science and Pollution Research, 2021)

Does meat consumption exacerbate greenhouse gas emissions? Evidence from US data - Muhammad Shafiullah; Usman Khalid; Muhammad Shahbaz (Environmental Science and Pollution Research, 2021)

Spatiotemporal analysis of crop water requirements in Lower Chenab Canal (LCC) Irrigation System for the better management of water resources - Muhammad Usman; Ejaz Hussain; Umair Rabbani; Shahid Ghazi; Syed M. Irteza; Shamaila Gull (Arabian Journal of Geosciences, 2021)

Impact of Urbanization on Groundwater Levels in Rawalpindi City, Pakistan - Faraz ul Haq; Usman Ali Naeem; Hamza Farooq Gabriel; Noor Muhammad Khan; Ijaz Ahmad; Habib Ur Rehman; Muhammad Awais Zafar (Pure and Applied Geophysics, 2021)

Gas Adsorption and Controlling Factors of Shale: Review, Application, Comparison and Challenges - Asadullah Memon; Aifen Li; Bilal Shams Memon; Temoor Muther; Wencheng Han; Muhammad Kashif; Muhammad Usman Tahir; Imran Akbar (Natural Resources Research, 2021)

SARS-COV-2 infection and lung tumor microenvironment - Naila Malkani; Muhammad Usman Rashid (Molecular Biology Reports, 2021)

Phylogeography of subspecies of the sable (Martes zibellina L.) based on mitochondrial genomes: implications for evolutionary history - Bo Li; Jinyao Lu; Vladimir Monakhov; Hui Kang; Yanchun Xu; Boyang An; Muhammad Usman Ghani; Mingzhe Li; Wenwen Peng; Xingna Ma (Mammalian Biology, 2021)

First report of leaf spot of bottle gourd (Lagenaria siceraria) caused by Fusarium equiseti in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Sabin Aslam; Muhammad Amjad Ali; Nasir Ahmad Khan; Yingyan Zhai; Mark L. Gleason (Journal of Plant Pathology, 2021)

Does the modifying role of institutional quality remains homogeneous in GDP-CO2 emission nexus? New evidence from ARDL approach - Usman Mehmood; Salman Tariq; Zia Ul-Haq; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2021)

The determinants of environmental quality in the SAARC region: a spatial heterogeneous panel data approach - Khaizran Khalid; Muhammad Usman; Muhammad Abuzar Mehdi (Environmental Science and Pollution Research, 2021)

Effect of biochar and compost on cadmium bioavailability and its uptake by wheat–rice cropping system irrigated with untreated sewage water: a field study - Muhammad Zia ur Rehman; Maqsooda Waqar; Safdar Bashir; Muhammad Rizwan; Shafaqat Ali; Ahmed Abd El Fattah El Baroudy; Hinnan Khalid; Muhammad Ashar Ayub; Muhammad Usman; Shah Jahan (Arabian Journal of Geosciences, 2021)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Molybdenum Application Regulates Oxidative Stress Tolerance in Winter Wheat Under Different Nitrogen Sources - Muhammad Imran; Xuecheng Sun; Saddam Hussain; Usman Ali; Muhammad Shoaib Rana; Fahd Rasul; Shadab Shaukat; Chengxiao Hu (Journal of Soil Science and Plant Nutrition, 2020)

Correction to: Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

The role of financial development, tourism, and energy utilization in environmental deficit: evidence from 20 highest emitting economies - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

An empirical nexus between economic growth, energy utilization, trade policy, and ecological footprint: a continent-wise comparison in upper-middle-income countries - Muhammad Usman; Rakhshanda Kousar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Fabrication, functionalization and performance of doped photocatalysts for dye degradation and mineralization: a review - Ackmez Mudhoo; Sonam Paliya; Prittam Goswami; Mukesh Singh; Giusy Lofrano; Maurizio Carotenuto; Federica Carraturo; Giovanni Libralato; Marco Guida; Muhammad Usman; Sunil Kumar (Environmental Chemistry Letters, 2020)

Adsorption, degradation, and mineralization of emerging pollutants (pharmaceuticals and agrochemicals) by nanostructures: a comprehensive review - Monika Jain; Ackmez Mudhoo; Deepika Lakshmi Ramasamy; Mahsa Najafi; Muhammad Usman; Runliang Zhu; Gopalakrishnan Kumar; Sutha Shobana; Vinod Kumar Garg; Mika Sillanpää (Environmental Science and Pollution Research, 2020)

Iron Nutrition Improves Productivity, Profitability, and Biofortification of Bread Wheat under Conventional and Conservation Tillage Systems - Usman Zulfiqar; Muhammad Maqsood; Saddam Hussain; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2020)

Correction to: Fluctuating temperatures influence the susceptibility of pest insects to biological control agents - Muhammad Usman Ghazanfar; Steffen Hagenbucher; Jörg Romeis; Giselher Grabenweger; Michael Meissle (Journal of Pest Science, 2020)

Asymmetric effects of inflation instability and GDP growth volatility on environmental quality in Pakistan - Sana Ullah; Nicholas Apergis; Ahmed Usman; Muhammad Zubair Chishti (Environmental Science and Pollution Research, 2020)

The engineering assessments and potential aggregate analysis of mesozoic carbonates of Kohat Hills Range, KP, Pakistan - Gohar Rehman; Guangcheng Zhang; Maqsood Ur Rahman; Naveed Ur Rahman; Tariq Usman; Muhammad Imraz (Acta Geodaetica et Geophysica, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Examining the asymmetric effects of globalization and tourism on pollution emissions in South Asia - Muhammad Zubair Chishti; Sana Ullah; Ilhan Ozturk; Ahmed Usman (Environmental Science and Pollution Research, 2020)

Intracranial hemorrhage complicating anticoagulant prophylactic therapy in three hospitalized COVID-19 patients - Muhammad Usman Ghani; Mukesh Kumar; Usman Ghani; Fnu Sonia; Syed Ali Abbas (Journal of NeuroVirology, 2020)

Citric acid enhanced phytoextraction of nickel (Ni) and alleviate Mentha piperita (L.) from Ni-induced physiological and biochemical damages - Kashaf Ul Khair; Mujahid Farid; Umair Ashraf; Muhammad Zubair; Muhammad Rizwan; Sheharyaar Farid; Hafiz Khuzama Ishaq; Usman Iftikhar; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

MUCO-DIS: a New AFM-Based Nanoscale Dissolution Technique - Muhammad Usman Ghori; Jorabar Singh Nirwan; Taimoor Asim; Younes Chahid; Samia Farhaj; Zara Khizer; Peter Timmins; Barbara R. Conway (AAPS PharmSciTech, 2020)
Mucoadhesion-based drug delivery systems have recently gained interest because of their bio-adhesion capability, which results in enhanced residence time leading to prolonged duration of action with the mucosal surface, potentially improving compliance and convenience. Mucoadhesion testing of these formulations is widely reported; however, this is technically challenging due to the absence of any standard methods and difficulty in conducting mucoadhesion, formulation-mucosal surface interaction, mucosal surface topography and drug release in a single experiment. As these measurements are currently conducted separately, on replicate formulations, results can often be subjective and difficult to correlate. Hence, the aim of the present study was to develop a new AFM-based single-entity ex vivo muco-dissolution (MUCO-DIS) technique to simultaneously evaluate mucoadhesion force, 3D surface topography, polymer dissolution and drug release characteristics. To demonstrate the potential of the current technique, the interactions between model pectin microparticles containing metformin HCl and a range of gastrointestinal mucosal surfaces (gastric, small intestine, large intestine and buccal) were studied. This novel system has not only successfully determined the mucoadhesion force, polymer dissolution and drug release information but has also highlighted the difference in microparticle performance with different mucosal targets. The current work has highlighted the potential of this newly developed MUCO-DIS system and we believe this will be a valuable tool for characterising these popular pharmaceutical formulations. This technique could also provide an opportunity to other scientific fields to evaluate materials, substrate behaviour and their interactions in their hydrated state at nanoscale with real-time chemical and surface mapping.

Fluctuating temperatures influence the susceptibility of pest insects to biological control agents - Muhammad Usman Ghazanfar; Steffen Hagenbucher; Jörg Romeis; Giselher Grabenweger; Michael Meissle (Journal of Pest Science, 2020)

Efficacy of Alternanthera bettzickiana to Remediate Copper and Cobalt Contaminated Soil Physiological and Biochemical Alterations - Amna Khalid; Mujahid Farid; Muhammad Zubair; Muhmmad Rizwan; Usman Iftikhar; Hafiz Khuzama Ishaq; Sheharyaar Farid; Urousa Latif; Kiran Hina; Shafaqat Ali (International Journal of Environmental Research, 2020)

Analysis of asymmetries in the nexus among clean energy and environmental quality in Pakistan - Ahmed Usman; Sana Ullah; Ilhan Ozturk; Muhammad Zubair Chishti; Syeda Maria Zafar (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Composition and source apportionment of saccharides in aerosol particles from an agro-industrial zone in the Indo-Gangetic Plain - Muhammad Usman Alvi; Magdalena Kistler; Imran Shahid; Khan Alam; Farrukh Chishtie; Tariq Mahmud; Anne Kasper-Giebl (Environmental Science and Pollution Research, 2020)

On the asymmetric effects of premature deindustrialization on CO2 emissions: evidence from Pakistan - Sana Ullah; Ilhan Ozturk; Ahmed Usman; Muhammad Tariq Majeed; Parveen Akhtar (Environmental Science and Pollution Research, 2020)

Ammonia inhalation-induced inflammation and structural impairment in the bursa of fabricius and thymus of broilers through NF-κB signaling pathway - Syed Waqas Ali Shah; Muhammad Ishfaq; Muhammad Nasrullah; Abdul Qayum; Muhammad Usman Akhtar; Hyeonsoo Jo; Muhammad Hussain; Xiaohua Teng (Environmental Science and Pollution Research, 2020)

5-Endo-dig cyclizations in organic syntheses - Muhammad Aamir Sajid; Zulfiqar Ali Khan; Sohail Anjum Shahzad; Syed Ali Raza Naqvi; Muhammad Usman (Molecular Diversity, 2020)

In situ immobilization of Cr and its availability to maize plants in tannery waste–contaminated soil: effects of biochar feedstock and pyrolysis temperature - Muhammad Imran Rafique; Adel R. A. Usman; Munir Ahmad; Abdelazeem Sallam; Mohammad I. Al-Wabel (Journal of Soils and Sediments, 2020)

Numerical investigation of the flow characteristics through discontinuous and layered vegetation patches of finite width in an open channel - Usman Ghani; Naveed Anjum; Ghufran Ahmed Pasha; Muhammad Ahmad (Environmental Fluid Mechanics, 2019)

Impact of insect growth regulators on biology and behavior of Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) - Mubasshir Sohail; Syed Saboor Khan; Raza Muhammad; Qadeer Ahmed Soomro; Muhammad Usman Asif; Bhai Khan Solangi (Ecotoxicology, 2019)

Downscaling of CMIP5 Models Output by Using Statistical Models in a Data Scarce Mountain Environment (Mangla Dam Watershed), Northern Pakistan - Naeem Saddique; Christian Bernhofer; Rico Kronenberg; Muhammad Usman (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

Composted Sugarcane By-product Press Mud Cake Supports Wheat Growth and Improves Soil Properties - Muhammad Umer Chattha; Muhammad Umair Hassan; Lorenzo Barbanti; Muhammad Bilal Chattha; Imran Khan; Muhammad Usman; Abid Ali; Muhammad Nawaz (International Journal of Plant Production, 2019)

Saudi Arabia-China-Pakistan Economic Corridor: intergovernmental green initiatives - Asma Naz; Khalid Zaman; Sheikh Usman Yousaf; Abdelmohsen A. Nassani; Abdullah Mohammed Aldakhil; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

Complexing agents for metal removal using ultrafiltration membranes: a review - Mustapha D. Garba; Muhammad Usman; Mohammad A. Jafar Mazumder; Amir Al-Ahmed; Inamuddin (Environmental Chemistry Letters, 2019)

Evaluation of microneedles-assisted in situ depot forming poloxamer gels for sustained transdermal drug delivery - Samiullah Khan; Muhammad Usman Minhas; Ismaiel A. Tekko; Ryan F. Donnelly; Raghu Raj Singh Thakur (Drug Delivery and Translational Research, 2019)

Estimation of Canal Water Deficit Using Satellite Remote Sensing and GIS: A Case Study in Lower Chenab Canal System - Muhammad Mohsin Waqas; Usman Khalid Awan; Muhammad Jehanzeb Masud Cheema; Ishfaq Ahmad; Matlob Ahmad; Sikandar Ali; Syed Hamid Hussain Shah; Allah Bakhsh; Muhammad Iqbal (Journal of the Indian Society of Remote Sensing, 2019)

Influence of injection timing and exhaust gas recirculation (EGR) rate on lemon peel oil–fuelled CI engine - Ashok Bragadeshwaran; Nanthagopal Kasianantham; Muhammad Usman Kaisan; Dandu Madhu Sudan Reddy; Kunnappilly Murukesh Aravind; Navneet Paul; Inas Muhammed Ali; Arun Jose; Tobith Chungath (Environmental Science and Pollution Research, 2019)

Engineered biochar composites with zeolite, silica, and nano-zerovalent iron for the efficient scavenging of chlortetracycline from aqueous solutions - Munir Ahmad; Adel R. A. Usman; Muhammad Imran Rafique; Mohammad I. Al-Wabel (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: pH-responsive CAP-co-poly(methacrylic acid)-based hydrogel as an efficient platform for controlled gastrointestinal delivery: fabrication, characterization, in vitro and in vivo toxicity evaluation - Syed Ahmed Shah; Muhammad Sohail; Muhammad Usman Minhas; Nisar-ur-Rehman; Shahzeb Khan; Zahid Hussain; Mudassir; Arshad Mahmood; Mubeen Kousar; Asif Mahmood (Drug Delivery and Translational Research, 2019)

Natural and synthetic polymer-based smart biomaterials for management of ulcerative colitis: a review of recent developments and future prospects - Muhammad Sohail; Mudassir; Muhammad Usman Minhas; Shahzeb Khan; Zahid Hussain; Marcel de Matas; Syed Ahmed Shah; Samiullah Khan; Mubeen Kousar; Kaleem Ullah (Drug Delivery and Translational Research, 2019)

pH/Thermo-Dual Responsive Tunable In Situ Cross-Linkable Depot Injectable Hydrogels Based on Poly(N-Isopropylacrylamide)/Carboxymethyl Chitosan with Potential of Controlled Localized and Systemic Drug Delivery - Samiullah Khan; Naveed Akhtar; Muhammad Usman Minhas; Syed Faisal Badshah (AAPS PharmSciTech, 2019)

Seismic vulnerability of non-ductile RC buildings in Pakistan through stochastic analysis of design/construction deficiencies - Muhammad Usman Ali; Shaukat Ali Khan; Muhammad Yousaf Anwar; Uzair Maqbool (Bulletin of Earthquake Engineering, 2019)

N-(2-hydroxyphenyl)acetamide and its gold nanoparticle conjugation prevent glycerol-induced acute kidney injury by attenuating inflammation and oxidative injury in mice - Rehan Ahmed Siddiqui; Shabana Usman Simjee; Nurul Kabir; Muhammad Ateeq; M. Raza Shah; Syed Saad Hussain (Molecular and Cellular Biochemistry, 2019)

Correction to: Preparation, optimization and pharmacological evaluation of 99mTc-4-hydroxy-3-(2-hydroxy-3-methoxybenzylideneamino) benzoic acid complex: as a novel potential radiopharmaceutical agent with hepatobiliary excretion - Muhammad Usman Akbar; Tanveer Hussain Bokhari; Samina Roohi; Khalid Mahmood Zia; Muhammad Razeen Ahmad; Saira Hina; Muhammad Sohaib (Molecular Biology Reports, 2018)

Preparation, optimization and pharmacological evaluation of 99mTc- 4-hydroxy-3-(2-hydroxy-3-methoxybenzylideneamino) benzoic acid complex: as a novel potential radiopharmaceutical agent with hepatobiliary excretion - Muhammad Usman Akbar (Molecular Biology Reports, 2018)

Deadly outbreak of chickenpox at district Faisalabad, Pakistan: possible causes, and preventive way forward - Muhammad Zubair Yousaf; Sadia Zia; Khalid Mahmood Anjum; Usman Ali Ashfaq; Muhammad Imran; Samia Afzal; Muhammad Sarfaraz Iqbal (Molecular Biology Reports, 2018)

Phytohormones enhanced drought tolerance in plants: a coping strategy - Abid Ullah; Hakim Manghwar; Muhammad Shaban; Aamir Hamid Khan; Adnan Akbar; Usman Ali; Ehsan Ali; Shah Fahad (Environmental Science and Pollution Research, 2018)

Experimental study of methyl tert-butyl ether as an oxygenated additive in diesel and Calophyllum inophyllum methyl ester blended fuel in CI engine - Ashok Bragadeshwaran; Nanthagopal Kasianantham; Saravanan Ballusamy; Kavalipurapu Raghu Tarun; Arumuga Perumal Dharmaraj; Muhammad Usman Kaisan (Environmental Science and Pollution Research, 2018)

Sustainable survival under climatic extremes: linking flood risk mitigation and coping with flood damages in rural Pakistan - Azhar Abbas; T. S. Amjath-Babu; Harald Kächele; Muhammad Usman; M. Amjed Iqbal; Muhammad Arshad; M. Adnan Shahid; Klaus Müller (Environmental Science and Pollution Research, 2018)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Tea waste as a potential biowaste for removal of hexavalent chromium from wastewater: equilibrium and kinetic studies - Usman Khalil; Muhammad Bilal Shakoor; Shafaqat Ali; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Preparation and Evaluation of Skin Wound Healing Chitosan-Based Hydrogel Membranes - Sarfaraz Ahmad; Muhammad Usman Minhas; Mahmood Ahmad; Muhammad Sohail; Orva Abdullah; Syed Faisal Badshah (AAPS PharmSciTech, 2018)

Epigallocatechin Gallate as an anti-obesity therapeutic compound: an in silico approach for structure-based drug designing - Muhammad Shahid Javaid; Noreen Latief; Bushra Ijaz; Usman Ali Ashfaq (Natural Product Research, 2018)

Pluronic-Based Mixed Polymeric Micelles Enhance the Therapeutic Potential of Curcumin - Muhammad Usman Akbar; Khalid Mahmood Zia; Ahsan Nazir; Jamshed Iqbal; Syeda Abida Ejaz; Muhammad Sajid Hamid Akash (AAPS PharmSciTech, 2018)

Performance evaluation of 1-D numerical model HEC-RAS towards modeling sediment depositions and sediment flushing operations for the reservoirs - Habib-ur-Rehman; Muhammad Asif Chaudhry; Usman Ali Naeem; Hashim Nisar Hashmi (Environmental Monitoring and Assessment, 2018)

Medicinal plant phytochemicals and their inhibitory activities against pancreatic lipase: molecular docking combined with molecular dynamics simulation approach - Bilal Ahmed; Usman Ali Ashfaq; Muhammad Usman Mirza (Natural Product Research, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Optimizing Irrigation Deficit of Multipurpose Cascade Reservoirs - Muhammad Usman Rashid; Abid Latif; Muhammad Azmat (Water Resources Management, 2018)

Effect of breeding method and season on pregnancy rate and embryonic and fetal losses in lactating Nili-Ravi buffaloes - Arslan Qayyum; Usman Arshad; Muhammad Rizwan Yousuf; Nasim Ahmad (Tropical Animal Health and Production, 2018)

Immunomodulatory and therapeutic role of Cinnamomum verum extracts in collagen-induced arthritic BALB/c mice - Mirza Muhammad Fahd Qadir; Attya Bhatti; Muhammad Usman Ashraf; Mansur Abdullah Sandhu; Sidrah Anjum; Peter John (Inflammopharmacology, 2018)

Role of circulatory microRNAs in the pathogenesis of hepatitis C virus - Iqra Almas; Samia Afzal; Muhammad Idrees; Muhammad Usman Ashraf; Iram Amin; Muhammad Shahid; Khadija Zahid; Sadia Zahid (VirusDisease, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

Application of chemical oxidation to remediate HCH-contaminated soil under batch and flow through conditions - Muhammad Usman; Oriane Tascone; Victoria Rybnikova; Pierre Faure; Khalil Hanna (Environmental Science and Pollution Research, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

Impacts of changing climate and snow cover on the flow regime of Jhelum River, Western Himalayas - Muhammad Azmat; Umar Waqas Liaqat; Muhammad Uzair Qamar; Usman Khalid Awan (Regional Environmental Change, 2017)

Population pharmacokinetics of meropenem in elderly patients: dosing simulations based on renal function - Muhammad Usman; Otto R. Frey; Georg Hempel (European Journal of Clinical Pharmacology, 2017)

Predicting Peak Flows in Real Time through Event Based Hydrologic Modeling for a Trans-Boundary River Catchment - Muhammad Adnan Shahid; Piero Boccardo; Muhammad Usman; Adriana Albanese; Muhammad Uzair Qamar (Water Resources Management, 2017)

Incorporation of estradiol benzoate to CIDR protocol improves the reproductive responses in crossbred dairy heifers - Muhammad Usman Mehmood; Ahmad Qamar; Abdul Sattar; Liaquat Ahmad; Nasim Ahmad (Tropical Animal Health and Production, 2017)

Haematology and blood chemistry references values for clinically healthy red-wattled lapwing (Vanellus indicus) - Sajid Umar; Kiran Aqil; Rizwan Qayyum; Muhammad Younus; Qamar-un-Nisa; Shahzad Ali; Muhammad Ali Shah; Muhammad Irfan; Muhammad Usman; Asif Ali; Akbar Ali; Adnan Ayan; et al. (European Journal of Wildlife Research, 2016)

Antiviral phytochemicals identification from Azadirachta indica leaves against HCV NS3 protease: an in silico approach - Usman Ali Ashfaq; Asma Jalil; Muhammad Tahir ul Qamar (Natural Product Research, 2016)

A study on the enhancing earthquake frequency in northern Pakistan: is the climate change responsible? - Muhammad Usman (Natural Hazards, 2016)

Purification and biochemical properties of SDS-stable low molecular weight alkaline serine protease from Citrullus colocynthis - Muhammad Bashir Khan; Hidayatullah Khan; Muhammad Usman Shah; Sanaullah Khan (Natural Product Research, 2016)

Enhanced degradation of benzene by percarbonate activated with Fe(II)-glutamate complex - Xiaori Fu; Xiaogang Gu; Shuguang Lu; Zhouwei Miao; Minhui Xu; Xiang Zhang; Muhammad Danish; Hang Cui; Usman Farooq; Zhaofu Qiu; Qian Sui (Environmental Science and Pollution Research, 2016)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Mass burden and estimated flux of heavy metals in Pakistan coast: sedimentary pollution and eco-toxicological concerns - Usman Ali; Riffat Naseem Malik; Jabir Hussain Syed; Ch. Tahir Mehmood; Laura Sánchez-García; Azeem Khalid; Muhammad Jamshed Iqbal Chaudhry (Environmental Science and Pollution Research, 2015)

Genetic analysis of post-weaning growth traits of Thalli sheep under tropical conditions - Asghar Hussain; Pervez Akhtar; Safdar Ali; Khalid Javed; Muhammad Younas; Abdul Shakoor; Usman Waheed (Tropical Animal Health and Production, 2014)

Synthesis, molecular docking and antiviral screening of novel N′-substitutedbenzylidene-2-(4-methyl-5,5-dioxido-3-phenylbenzo[e]pyrazolo[4,3-c][1,2]thiazin-1(4H)-yl)acetohydrazides - Sana Aslam; Matloob Ahmad; Muhammad Makshoof Athar; Usman Ali Ashfaq; John M. Gardiner; Catherine Montero; Mervi Detorio; Masood Parvez; Raymond F. Schinazi (Medicinal Chemistry Research, 2014)

Expression line approach to recombinant human epidermal growth factor into the yeast, Pichia pastoris from Huh-7 cell line - Mohsin Ahmad Khan; Faidad Khan; Nadeem Ahmad; Muhammad Islam Khan; Ahmad Usman Zafar; Tayyab Husnain (Molecular Biology Reports, 2014)

Myoloid-Related Protein 8, an Endogenous Ligand of Toll-Like Receptor 4, Is Involved in Epileptogenesis of Mesial Temporal Lobe Epilepsy Via Activation of the Nuclear Factor-κB Pathway in Astrocytes - Na Gan; Lifen Yang; Ahmed Omran; Jing Peng; Liwen Wu; Fang He; Ciliu Zhang; Qiulian Xiang; Huimin Kong; Yupin Ma; Muhammad Usman Ashhab; Xiaolu Deng; et al. (Molecular Neurobiology, 2014)

Synthesis of chemically cross-linked polyvinyl alcohol-co-poly (methacrylic acid) hydrogels by copolymerization; a potential graft-polymeric carrier for oral delivery of 5-fluorouracil - Muhammad Usman Minhas; Mahmood Ahmad; Liaqat Ali; Muhammad Sohail (DARU Journal of Pharmaceutical Sciences, 2013)
Background of the Study The propose of the present work was to develop chemically cross-linked polyvinyl alcohol-co-poly(methacrylic acid) hydrogel (PVA-MAA hydrogel) for pH responsive delivery of 5-Fluorouracil (5-FU). Methods PVA based hydrogels were prepared by free radical copolymerization. PVA has been cross-linked chemically with monomer (methacrylic acid) in aqueous medium, cross-linking agent was ethylene glycol di-methacrylate (EGDMA) and benzoyl peroxide was added as reaction initiator. 5-FU was loaded as model drug. FTIR, XRD, TGA and DSC were performed for characterization of copolymer. Surface morphology was studied by SEM. pH sensitive properties were evaluated by swelling dynamics and equilibrium swelling ratio at low and higher pH. Results FTIR, XRD, TGA and DSC studies confirmed the formation of new copolymer. Formulations with higher MAA contents showed maximum swelling at 7.4 pH. High drug loading and higher drug release has been observed at pH 7.4. Conclusions The current study concludes that a stable copolymeric network of PVA was developed with MAA. The prepared hydrogels were highly pH responsive. This polymeric network could be a potential delivery system for colon targeting of 5-FU in colorectal cancers.

Expressions of Tumor Necrosis Factor Alpha and MicroRNA-155 in Immature Rat Model of Status Epilepticus and Children with Mesial Temporal Lobe Epilepsy - Muhammad Usman Ashhab; Ahmed Omran; Huimin Kong; Na Gan; Fang He; Jing Peng; Fei Yin (Journal of Molecular Neuroscience, 2013)

Expression Patterns of miR-124, miR-134, miR-132, and miR-21 in an Immature Rat Model and Children with Mesial Temporal Lobe Epilepsy - Jing Peng; Ahmed Omran; Muhammad Usman Ashhab; Huimin Kong; Na Gan; Fang He; Fei Yin (Journal of Molecular Neuroscience, 2013)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

Effects of interactions among Metarhizium anisopliae, Bacillus thuringiensis and chlorantraniliprole on the mortality and pupation of six geographically distinct Helicoverpa armigera field populations - Waqas Wakil; M. Usman Ghazanfar; Tahira Riasat; Mirza Abdul Qayyum; Sohail Ahmed; Muhammad Yasin (Phytoparasitica, 2013)

The anti-arthritic and anti-oxidative effect of NBD (6-nitro-1,3-benzodioxane) in adjuvant-induced arthritis (AIA) in rats - Syed Uzair Ali Shah; Nadeem Ashraf; Zahid H. Soomro; Muhammad Raza Shah; Nurul Kabir; Shabana Usman Simjee (Inflammation Research, 2012)

Three Dimensional Load Analysis of Tunnel Linings Including Weathering Processes of the Shotcrete - Muhammad Usman; Christian Volderauer; Gunter Gschwandtner; Robert Galler (BHM Berg- und Hüttenmännische Monatshefte, 2011)

Synthesis of a New Tri-Branched PEG-IFNα2 and Its Impact on Anti Viral Bioactivity - Muhammad Farooq Sabar; Mustansara Yaqub; Mohsin Ahmad Khan; Nadeem Ahmad; Muhammad Usman Ghani; Mariam Shahid (International Journal of Peptide Research and Therapeutics, 2010)

Evaluation of pollution load of Lahore Canal by quantification of various pollutants through physicochemical characterisation - Muhammad Waseem Mumtaz; Muhammad Hanif; Hamid Mukhtar; Zahoor Ahmed; Sumaira Usman (Environmental Monitoring and Assessment, 2010)

Evaluation of the Acute Toxicity of Profenofos and Its Effects on the Behavioral Pattern of Fingerling Common Carp (Cyprinus carpio L., 1758) - Muhammad Ismail; Rahat Ali; Tayyaba Ali; Usman Waheed; Qaiser Mahmood Khan (Bulletin of Environmental Contamination and Toxicology, 2009)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for improving growth and yield of wheat (Triticum aestivum L.) under salt-stressed conditions - Zahir Ahmad Zahir; Usman Ghani; Muhammad Naveed; Sajid Mahmood Nadeem; Hafiz Naeem Asghar (Archives of Microbiology, 2009)

A Conceptual Framework for Enhancing the Utility of Rainfall Hazard Forecasts for Agriculture in Marginal Environments - Muhammad T. Usman; Emma Archer; Peter Johnston; Mark Tadross (Natural Hazards, 2005)